Acrylic rubber with excellent injection moldability and Banbury processability
Patent Information
- Application Number
- KR1020227044055
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2021-06-04
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-06-04
Smart Images

Figure 112022135030189-PCT00004_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to acrylic rubber, a method for manufacturing the same, a rubber composition, and a rubber crosslinker, and more specifically, to an acrylic rubber having a highly balanced combination of injection moldability, Banbury processability, strength characteristics, resistance to permanent deformation of compression, and water resistance, a method for manufacturing the same, a rubber composition comprising the acrylic rubber, and a rubber crosslinker formed by crosslinking the same. Background Technology
[0002] Acrylic rubber is a polymer composed mainly of acrylic acid esters. It is generally known as a rubber with excellent heat resistance, oil resistance, and ozone resistance, and is widely used in fields such as automotive.
[0003] For example, Patent Document 1 (Japanese Published Patent Application No. Hei 11-12427) describes a method in which 100 parts of a monomer component comprising ethyl acrylate, butyl acrylate, methoxyethyl acrylate, acrylonitrile, and monomers that introduce carbon-carbon double bonds into the side chain, such as allyl methacrylate or cyclopentenyloxyethyl acrylate, 4 parts sodium lauryl sulfate, 0.25 parts p-menthane hydroperoxide as an organic radical generator, 0.01 parts ferrous sulfate, 0.025 parts sodium ethylenediamine tetraacetate, 0.04 parts sodium formaldehyde sulfoxylate, and 0.01 to 0.05 parts t-dodecyl mercaptan as a chain transfer agent are introduced into a nitrogen-substituted autoclave and, at a reaction temperature of 30°C until the conversion rate of the monomer mixture reaches 100% An acrylic rubber and a crosslinking composition having excellent extrusion processability and scorch properties are disclosed, wherein the resulting latex is reacted, added to a 0.25% aqueous calcium chloride solution to coagulate it, the coagulated product is thoroughly washed with water, dried at about 90°C for 3 hours, and crosslinked with an organic peroxide such as 1,3-bis(t-butylperoxyisopropyl)benzene. However, the acrylic rubber obtained by the present method had problems such as insufficient injection moldability and Banbury processability, as well as poor storage stability, resistance to permanent compression deformation, water resistance, and strength properties.
[0004] In addition, Patent Document 2 (Japanese Published Patent Application No. Hei 5-86137) discloses a method for manufacturing acrylic rubber in which polymerization is initiated by an organic radical generator and a chain transfer agent is added to a monomer emulsion and continuously administered. Specifically, one-fifth of a mixture of a monomer mixture containing crosslinkable monomers such as 2-(2-cyanoethoxy)ethyl acrylic acid, ethyl acrylate, n-butyl acrylate, vinyl chloroacetate, and allyl glycidyl ether, and an appropriate amount of n-dodecyl mercaptan is mixed and stirred with half of 1 part by weight of polyoxyethylene lauryl ether, 4 parts by weight of sodium lauryl sulfate, 0.7 parts by weight of disodium hydrogen phosphate, and 0.3 parts by weight of sodium dihydrogen phosphate to form an emulsion, and after heating to 15°C, 0.005 parts by weight of sodium iron(II) ethylenediamine tetraacetate, 0.02 parts by weight of tetrasodium ethylenediamine tetraacetate, 0.02 parts by weight of longalite, and 0.02 parts by weight of sodium hydrosulfite are added, and a 0.2% by weight aqueous solution of tert-butyl hydroperoxide, an organic radical generator, is mashed Polymerization is initiated by dropping at a rate of 1.5 parts, and while maintaining the temperature at 15°C, an emulsion consisting of a mixture of the remaining monomer and n-dodecyl mercaptan and an aqueous solution of an emulsifier is dropped over 3 hours to carry out the polymerization reaction until the monomer conversion rate reaches 96-99%. Additionally, it is described that the obtained copolymer latex is immersed in an aqueous calcium chloride solution at 85°C to isolate the copolymer, and after thorough washing, drying is performed to obtain the desired copolymer rubber, and sulfur crosslinking is performed. However, the acrylic rubber obtained by this method had problems such as insufficient injection moldability, as well as poor storage stability, water resistance, and strength properties.
[0005] In addition, Patent Document 3 (International Publication No. 2019 / 188709 Pamphlet) discloses a method for producing acrylic rubber by adding monomer components consisting of ethyl acrylate, butyl acrylate, methoxyethyl acrylate, and monobutyl fumarate, water, and sodium lauryl sulfate, repeating vacuum degassing and nitrogen purging, then adding sodium aldehyde sulfoxylate and cumene hydroperoxide, an organic radical generator, to initiate emulsion polymerization at atmospheric pressure and room temperature, carrying out emulsion polymerization until the polymerization conversion rate reaches 95 wt%, then coagulating with an aqueous calcium chloride solution and dehydrating and drying with an extrusion dryer equipped with a screw. However, the acrylic rubber obtained by this method had problems with poor injection moldability, storage stability, and water resistance.
[0006] In addition, Patent Document 4 (International Publication No. 2018 / 117037 Pamphlet) discloses a method for producing acrylic rubber by introducing monomer components consisting of ethyl acrylate and monon-butyl fumarate, water, and sodium dodecyl sulfate, performing vacuum degassing and nitrogen substitution three times to sufficiently remove oxygen, adding azobis(isobutyronitrile) and ethyl-2-methyl-2-phenyltellanylpropionate, which are organic radical generators, initiating a polymerization reaction at 50 degrees under atmospheric pressure, polymerizing until a polymerization conversion rate of 89% is reached, then coagulating with a calcium chloride solution, washing, and drying. However, the acrylic rubber obtained by this method had problems with poor injection moldability, Banbury processability, storage stability, and water resistance.
[0007] Meanwhile, regarding a method for manufacturing acrylic rubber using an inorganic radical generator, for example, Patent Document 5 (Japanese Published Patent Application No. 2019-119772), a monomer component consisting of ethyl acrylate, butyl acrylate, methoxyethyl acrylate, and monobutyl maleate is prepared into a monomer emulsion using pure water and sodium lauryl sulfate and polyoxyethylene dodecyl ether as emulsifiers; a portion of the monomer emulsion is introduced into a polymerization reactor and cooled to 12°C under a nitrogen stream; then, the remaining monomer emulsion, ferrous sulfate, sodium ascorbate, and an aqueous potassium persulfate solution as an inorganic radical generator are continuously added dropwise over a period of 3 hours; and thereafter, emulsion polymerization is carried out for 1 hour while maintaining the temperature at 23°C until the polymerization conversion rate reaches 97 wt%; after that, the temperature is raised to 85°C, and sodium sulfate is continuously added to separate the mixture by coagulation and filtration. A method is disclosed in which a crumb is obtained, the crumb is washed with water four times, washed with acid once, and washed with pure water once, and then an acrylic rubber sheet is continuously produced using an extrusion dryer equipped with a screw, and crosslinked with an aliphatic polyamine compound such as hexamethylenediaminecarbamate. However, the sheet acrylic rubber obtained by this method has problems such as poor injection moldability and storage stability, and also poor water resistance of the crosslinked material.
[0008] Patent Document 6 (Japanese Published Patent Application No. Hei 1-135811) discloses a method for producing acrylic rubber and crosslinking with sulfur by emulsifying 1 / 4 of a monomer mixture consisting of monomer components comprising ethyl acrylate, caprolactone addition-type acrylic acid ester, cyanoethyl acrylate, and vinyl chloroacetate, and n-dodecyl mercaptan as a chain transfer agent with sodium lauryl sulfate, polyethylene glycol nonylphenyl ether, and distilled water, initiating polymerization by adding sodium sulfite and ammonium persulfate as an inorganic radical generator, maintaining the temperature at 60°C and dropping the remainder of the monomer mixture and a 2% aqueous solution of ammonium persulfate for 2 hours, continuing polymerization for another 2 hours after dropping, and then introducing the latex with a polymerization conversion rate of 96-99% into an aqueous sodium chloride solution at 80°C to coagulate, followed by sufficient washing and drying. However, the acrylic rubber obtained by this method had problems with poor injection moldability, storage stability, and water resistance.
[0009] Patent Document 7 (Japanese Published Patent Application No. Sho 62-64809) discloses a sulfur-vulcanizable acrylic rubber characterized by a copolymer having a monomer composition comprising 50 to 99.9 weight% of at least one compound among alkyl acrylates and alkoxyalkyl acrylates, 0.1 to 20 weight% of a dihydrodicyclopentenyl group-containing ester of an unsaturated carboxylic acid, and 0 to 20 weight% of at least one of other monovinyl, monovinylidene, and monovinylene unsaturated compounds, wherein the number average molecular weight (Mn) equivalent to polystyrene using tetrahydrofuran as the developing solvent is 200,000 to 1,200,000, and the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) is 10 or less. As a specific example, an acrylic rubber is disclosed having a number average molecular weight (Mn) of 530,000 to 1,150,000, a weight average molecular weight (Mw) of 3,540,000 to 6,260,000, and a ratio of weight average molecular weight (Mw / Mn) of 4.7 to 8. Furthermore, as shown in the examples and comparative examples, when the amount of chain transfer agent is small, the number average molecular weight (Mn) is large at 5 million, and the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) narrows to 1.4; conversely, when the amount of chain transfer agent is large, the number average molecular weight (Mn) is small at 200,000, and the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) widens extremely to 17. However, the acrylic rubber obtained by this method has poor injection moldability, and in the crosslinking reaction, sulfur as a crosslinking agent and a vulcanization accelerator are added and kneaded with a roller, then 100 kg / cm² 2There was a problem that long-term crosslinking was required in the vulcanization press at 170°C for 15 minutes, and in the gear oven at 175°C for 4 hours, and furthermore, the crosslinked material obtained had problems such as reduced water resistance, reduced compression permanent deformation resistance and strength characteristics, and also reduced physical properties after deterioration due to heat. Prior art literature
[0010] Japanese Published Patent Application No. Hei 11-12427 Japanese Published Patent Application No. 2019-119772 International Publication No. 2019 / 188709 Pamphlet International Publication No. 2018 / 117037 Pamphlet Japanese Published Patent Application No. 2019-119772 Japanese Published Patent Application No. Hei 1-135811 Japanese Published Patent Application No. Sho 62-64809 The problem to be solved
[0011] The present invention is made in consideration of the actual state of such prior art and aims to provide an acrylic rubber with highly balanced injection moldability, Banbury processability, water resistance, compression resistance, and strength characteristics, a method for manufacturing the same, a rubber composition including the acrylic rubber, and a rubber crosslinked product formed by crosslinking the same. means of solving the problem
[0012] The inventors, having conducted diligent research in consideration of the above problem, have discovered that an acrylic rubber having specific reactive groups, a specific weight-average molecular weight (Mw) and a specific ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn) (Mw / Mn), and specific gel content, ash content, or ash content, exhibits highly excellent injection moldability, Banbury processability, water resistance, resistance to permanent deformation, and strength characteristics. In particular, it has been discovered that the injection moldability of the acrylic rubber of the present invention is significantly superior in any of the characteristics of shape forming ability, fusion ability, and release ability.
[0013] The inventors have also discovered that acrylic rubber having reactive groups capable of reacting with crosslinking agents such as carboxyl groups, epoxy groups, or chlorine atoms, and having a weight average molecular weight (Mw) within a specific range, has highly excellent resistance to permanent deformation and strength characteristics. The inventors have also discovered that in GPC measurements of acrylic rubber having such reactive groups, tetrahydrofuran used in the GPC measurements of radical reactive acrylic rubber copolymerized with ethyl acrylate and dihydrodicyclopentenyl acrylate, etc., of the prior art could not be sufficiently dissolved, and thus could not clearly and reproducibly measure each molecular weight or molecular weight distribution. However, by using a specific solvent with a higher SP value than tetrahydrofuran as the developing solvent, it can be clearly dissolved and reproducibly measured, and furthermore, by specifying each characteristic value, the injection moldability, water resistance, resistance to permanent deformation, and strength characteristics of the acrylic rubber can be highly controlled.
[0014] The inventors have discovered that in order to highly balance the strength characteristics and injection moldability of acrylic rubber, it is important to have the weight-average molecular weight (Mw) of the acrylic rubber in a slightly larger range and to ensure that the ratio of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) (Mw / Mn) falls within a specific range. They found that to manufacture such acrylic rubber, using only emulsion polymerization with an organic radical generator results in a narrow ratio of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) (Mw / Mn), which leads to poor injection moldability; however, they discovered that this can be achieved by adding a chain transfer agent in batches during polymerization. On the other hand, it was found that acrylic rubber emulsion polymerized using an inorganic radical generator has an excessively wide ratio of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) (Mw / Mn), resulting in poor injection moldability.
[0015] The inventors have also discovered that by drying the acrylic rubber using a specific extrusion dryer under specific shear conditions, the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn) can be widened without damaging the weight average molecular weight (Mw) of the acrylic rubber, and furthermore, an acrylic rubber with highly balanced injection moldability, Banbury processability, strength characteristics, and resistance to permanent deformation of compression can be produced.
[0016] Regarding Banbury processability, the inventors have discovered that the gel amount of a specific solvent-insoluble component is correlated. The gel amount of acrylic rubber occurs during emulsion polymerization and increases rapidly when the polymerization conversion rate is increased to improve strength characteristics, making it difficult to control and thus worsening the Banbury processability of acrylic rubber. However, they have discovered that by performing emulsion polymerization in the presence of a chain transfer agent at the end of the polymerization reaction, gelation can be prevented to some extent and Banbury processability can be improved. Furthermore, by melt-kneading and extrusion-drying in a screw-type twin-screw extrusion dryer in a state that is substantially free of moisture (moisture content less than 1 weight%), the gel amount of a specific solvent-insoluble component that increased rapidly during emulsion polymerization is lost, and the variation in gel amount is reduced, thereby significantly improving Banbury processability without damaging the strength characteristics of the acrylic rubber obtained.
[0017] Regarding water resistance, the inventors have discovered that the ash content and ash components have a significant influence. In particular, although it is considerably difficult to remove ash from acrylic rubber manufactured using large amounts of emulsifiers or coagulants, they have discovered that by coagulating using a specific method, the cleaning efficiency of the generated moisture crumbs and the ash removal efficiency during dehydration can be significantly improved, thereby reducing the ash content of the acrylic rubber and significantly improving its water resistance. In particular, the inventors have discovered that by increasing the proportion of specific particle sizes of the moisture crumbs generated during the coagulation process and performing cleaning, dehydration, and drying, the water resistance of the obtained acrylic rubber can be significantly improved without damaging properties such as injection moldability, strength characteristics, and resistance to permanent compression deformation. Furthermore, the inventors have discovered that if a specific emulsifier is used during the emulsion polymerization of acrylic rubber, or if a specific coagulant is used when coagulating the emulsion polymerization solution, the water resistance of the acrylic rubber is excellent, and at the same time, the release properties from molds and the like are significantly increased.
[0018] The inventors have also discovered that acrylic rubber with a high specific gravity and no air content exhibits excellent injection moldability, water resistance, strength characteristics, and resistance to permanent deformation under compression, while simultaneously having significantly superior storage stability. It has been discovered that acrylic rubber with excellent storage stability due to not containing air (high specific gravity) can have its specific gravity slightly increased and its storage stability improved by compressing the dry rubber—which is dried directly after washing and dehydrating the water crumb generated in the coagulation reaction—with a high-pressure baler or the like. Preferably, acrylic rubber with significantly superior storage stability can be manufactured by extruding the dry rubber, which is dried in a state without air under reduced pressure in a specific extrusion dryer, from the water crumb generated in the coagulation process into a sheet. The inventors have also discovered that storage stability can be further improved by using acrylic rubber with a specific pH that is polymerized under conditions where the emulsion polymerization solution does not become neutral, and that storage stability of the acrylic rubber can be further improved by forming it into a sheet or bale shape.
[0019] The inventors have also discovered that an acrylic rubber with excellent injection moldability, water resistance, compression resistance, and strength properties can be efficiently produced by emulsifying a specific monomer component containing a monomer containing a specific reactive group with water and an emulsifier, initiating emulsion polymerization in the presence of a redox catalyst consisting of an organic radical generator such as diisopropylbenzene hydroperoxide and a reducing agent, performing emulsion polymerization by adding a chain transfer agent in batches during polymerization without initially adding the chain transfer agent, coagulating the emulsion polymerized liquid by a specific method, and dehydrating the hydrate crumb generated in the coagulation reaction before entering a drying process after washing.
[0020] The inventors have also discovered that in a rubber composition comprising the acrylic rubber, filler, and crosslinking agent of the present invention, incorporating carbon black or silica as the filler results in excellent injection moldability, Banbury processability, and short-term crosslinking properties, and furthermore, highly excellent water resistance, strength properties, and resistance to permanent compression deformation of the crosslinked product. The inventors have also discovered that, as the crosslinking agent, it is preferable to be an organic compound, a polyvalent compound, or an ionic crosslinking compound, and, for example, a polyvalent ionic organic compound having multiple ionic reactive groups that react with ionic reactive groups of acrylic rubber such as amine groups, epoxy groups, carboxyl groups, or thiol groups, results in excellent injection moldability, Banbury processability, and short-term crosslinking properties, and furthermore, highly excellent water resistance, strength properties, and resistance to permanent compression deformation of the crosslinked product.
[0021] Based on these findings, the inventors have completed the present invention.
[0022] Thus, according to the present invention, an acrylic rubber is provided having at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom, having a weight average molecular weight (Mw) of 1 million to 5 million, a ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) (Mw / Mn) of 1.5 to 3, a gel content of 50 weight% or less, an ash content of 0.0001 to 0.3 weight%, and a total amount of sodium, sulfur, calcium, magnesium, and phosphorus in the ash of 80 weight% or more.
[0023] In the acrylic rubber of the present invention, it is preferable that it comprises at least one bonding unit derived from a (meth)acrylic acid ester selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, a bonding unit derived from a monomer containing at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group and a chlorine atom, and, if necessary, other bonding units derived from monomers.
[0024] In the acrylic rubber of the present invention, it is preferable that at least one bonding unit derived from a (meth)acrylic acid ester selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters is 50 to 99.99 weight%, a bonding unit derived from a monomer containing at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom is 0.01 to 10 weight%, and a bonding unit derived from other monomers is 0 to 40 weight%.
[0025] In the acrylic rubber of the present invention, it is preferable that the reactive group is an ionic reactive group.
[0026] In the acrylic rubber of the present invention, it is preferable that the gel amount is 10 weight% or less.
[0027] In the acrylic rubber of the present invention, it is preferable that all values of the gel amount measured at 20 arbitrary points are within the range of (average value ± 5) weight%.
[0028] In the acrylic rubber of the present invention, it is preferable that the gel amount is the amount insoluble in methyl ethyl ketone.
[0029] In the acrylic rubber of the present invention, it is preferable that the ash content is 0.2 weight% or less.
[0030] In the acrylic rubber of the present invention, it is preferable that the specific gravity is 0.8 or higher.
[0031] In the acrylic rubber of the present invention, it is preferable that the pH is 6 or lower.
[0032] In the acrylic rubber of the present invention, it is preferable that the complex viscosity ([η]100℃) at 100℃ is 15,000[Pa·s] or less.
[0033] In the acrylic rubber of the present invention, it is preferable that it be in the form of a sheet or a bale.
[0034] The acrylic rubber of the present invention is preferably obtained by emulsion polymerization using a phosphate ester salt or a sulfate ester salt as an emulsifier, and is preferably obtained by solidifying the emulsion polymerized solution using an alkali metal salt or a Group 2 metal salt of the periodic table as a coagulant and drying it. Furthermore, the acrylic rubber of the present invention is preferably obtained by melt mixing and drying after solidification, and it is preferable that the melt mixing and drying are performed in a state that substantially does not contain moisture, and that the melt mixing and drying are performed under reduced pressure. Additionally, in the acrylic rubber of the present invention, it is preferable that it is cooled at a cooling rate of 40°C / hr or more after the melt mixing and drying.
[0035] In the acrylic rubber of the present invention, it is preferable to use a water crumb having a ratio of 50% by weight or more of particles with a diameter in the range of 710 μm to 6.7 mm that has been washed, dehydrated, and dried.
[0036] According to the present invention, an emulsification process for emulsifying an acrylic rubber monomer component comprising a monomer having at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom with water and an emulsifier, and
[0037] An emulsion polymerization process that initiates polymerization in the presence of a redox catalyst comprising an organic radical generator and a reducing agent, and continues polymerization by batchly adding a chain transfer agent during polymerization to obtain an emulsion polymerization solution, and
[0038] A coagulation process in which the obtained emulsion polymer is added to a stirring coagulation liquid to coagulate and produce a hydrated crumb, and
[0039] A cleaning process for cleaning the generated function crumb, and
[0040] A dehydration process for dehydrating washed moisture crumbs to a moisture content of 1 to 50 weight percent, and
[0041] Drying process for drying dehydrated crumb to less than 1 weight percent
[0042] A method for manufacturing acrylic rubber including is provided.
[0043] The method for manufacturing acrylic rubber according to the present invention is preferably a method for manufacturing acrylic rubber that manufactures said acrylic rubber.
[0044] In the method for manufacturing acrylic rubber according to the present invention, the dehydration process and the drying process preferably involve using a screw-type twin-screw extrusion dryer having a dehydration barrel with a dehydration slit, a drying barrel under reduced pressure, and a die at the tip of the cleaned moisture crumb to dehydrate the moisture content to 1 to 40 weight% in the dehydration barrel, and then drying it to less than 1 weight% in the drying barrel and extruding the dried rubber from the die.
[0045] In the method for manufacturing acrylic rubber according to the present invention, it is preferable that the stirring speed of the coagulating liquid being stirred is 200 rpm or higher.
[0046] In the method for manufacturing acrylic rubber according to the present invention, it is preferable that the circumferential speed of the coagulating liquid being stirred is 1 m / s or more.
[0047] In the method for manufacturing acrylic rubber according to the present invention, in the emulsion polymerization process, it is preferable to perform emulsion polymerization using a phosphate ester salt or a sulfate ester salt as an emulsifier.
[0048] In the method for manufacturing acrylic rubber according to the present invention, it is preferable to solidify the polymerization solution produced in the emulsion polymerization process by using an alkali metal salt or a Group 2 metal salt of the periodic table as a coagulant, and then dry it.
[0049] In the method for manufacturing acrylic rubber according to the present invention, it is preferable to contact the polymerization solution produced in the emulsion polymerization process with a coagulant to coagulate it, and then perform melt mixing and drying.
[0050] In the method for manufacturing acrylic rubber according to the present invention, it is preferable that the melt mixing and drying are performed in a state that substantially does not contain moisture.
[0051] In the method for manufacturing acrylic rubber according to the present invention, it is preferable that the melt mixing and drying are performed under reduced pressure.
[0052] In the method for manufacturing acrylic rubber according to the present invention, it is preferable to cool the acrylic rubber after melt mixing and drying at a cooling rate of 40°C / hr or higher.
[0053] In the method for manufacturing acrylic rubber of the present invention, it is preferable to wash, dehydrate, and dry a moisture crumb having a particle size in the range of 710 μm to 6.7 mm and a ratio of 50 weight% or more.
[0054] According to the present invention, a rubber composition comprising a rubber component including the acrylic rubber, a filler, and a crosslinking agent is also provided.
[0055] In the rubber composition of the present invention, it is preferable that the filler is a reinforcing filler. In addition, in the rubber composition of the present invention, it is preferable that the filler is a carbon black. In addition, in the rubber composition of the present invention, it is preferable that the filler is a silica.
[0056] In the rubber composition of the present invention, it is preferable that the crosslinking agent is an organic crosslinking agent. Furthermore, in the rubber composition of the present invention, it is preferable that the crosslinking agent is a polyvalent compound. Furthermore, in the rubber composition of the present invention, it is preferable that the crosslinking agent is an ionic crosslinkable compound. Furthermore, in the rubber composition of the present invention, it is preferable that the crosslinking agent is an ionic crosslinkable organic compound. Furthermore, in the rubber composition of the present invention, it is preferable that the crosslinking agent is a polyvalent ionic organic compound.
[0057] In the rubber composition of the present invention, it is preferable that the ion of the ionic crosslinkable compound, ionic crosslinkable organic compound, or polyvalent ionic organic compound used as the crosslinking agent is at least one ionic reactive group selected from the group consisting of amino groups, epoxy groups, carboxyl groups, and thiol groups.
[0058] In the rubber composition of the present invention, it is preferable that the crosslinking agent is at least one polyvalent ionic compound selected from the group consisting of polyvalent amine compounds, polyvalent epoxy compounds, polyvalent carboxylic acid compounds, and polyvalent thiol compounds.
[0059] In the rubber composition of the present invention, it is preferable that the content of the crosslinking agent be in the range of 0.001 to 20 parts by weight per 100 parts by weight of the rubber component.
[0060] The rubber composition of the present invention preferably comprises an anti-aging agent. In the rubber composition of the present invention, it is preferable that the anti-aging agent is an amine-based anti-aging agent.
[0061] According to the present invention, a method for preparing a rubber composition is provided, wherein a rubber component comprising the above-mentioned acrylic rubber, a filler, and, if necessary, an anti-aging agent are mixed, and then a crosslinking agent is mixed.
[0062] According to the present invention, a rubber crosslinked material is also provided, which is formed by crosslinking the rubber composition. In the rubber crosslinked material of the present invention, it is preferable that the crosslinking of the rubber composition is performed after molding. In addition, in the rubber crosslinked material of the present invention, it is preferable that the crosslinking of the rubber composition involves primary crosslinking and secondary crosslinking. Effects of the invention
[0063] According to the present invention, an acrylic rubber having highly balanced injection moldability, Banbury processability, water resistance, compression resistance, and strength characteristics, an efficient method for manufacturing the same, a high-quality rubber composition comprising the acrylic rubber, and a rubber crosslinked with the same are provided. Brief explanation of the drawing
[0064] FIG. 1 is a schematic diagram showing an example of an acrylic rubber manufacturing system used in the manufacture of acrylic rubber according to one embodiment of the present invention. Figure 2 is a diagram showing the configuration of the screw-type extruder of Figure 1. Figure 3 is a diagram showing the configuration of a return-type cooling device used as the cooling device of Figure 1. Specific details for implementing the invention
[0065] The acrylic rubber of the present invention is characterized by having at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, having a weight average molecular weight (Mw) of 1 million to 5 million, a ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) (Mw / Mn) of 1.5 to 3, a gel content of 50 weight% or less, an ash content of 0.0001 to 0.3 weight%, and a total amount of sodium, sulfur, calcium, magnesium, and phosphorus in the ash of 80 weight% or more.
[0066] Reactive period
[0067] The acrylic rubber of the present invention is characterized by having at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms.
[0068] There is no particular limitation on at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, but it is preferable that it be an ionic reactive group, more preferably an epoxy group, a carboxyl group, and particularly preferably a carboxyl group, as this can significantly improve the short-term crosslinking ability and the resistance to permanent compression deformation or water resistance of the crosslinked material.
[0069] The content of at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms of the acrylic rubber of the present invention is not specifically limited and can be appropriately selected according to the purpose of use. When the weight ratio of the reactive group itself is typically in the range of 0.001 to 5 weight%, preferably 0.01 to 3 weight%, more preferably 0.05 to 1 weight%, and particularly preferably 0.1 to 0.5 weight%, the processability, crosslinkability, and strength characteristics when used as a crosslinked material, as well as characteristics such as resistance to permanent deformation of compression, resistance to oil, resistance to cold, and resistance to water, are highly balanced and suitable.
[0070] The acrylic rubber of the present invention having at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms may be one in which at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms is introduced into the acrylic rubber as a post-reaction, but preferably, an acrylic rubber copolymerized with a monomer containing said reactive group is suitable.
[0071] <Monomer Components>
[0072] The monomer component of the acrylic rubber of the present invention is not particularly limited as long as it is a monomer component constituting a conventional acrylic rubber having the reactive group, but preferably comprises an acrylic rubber monomer component containing at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms; more preferably, comprises at least one (meth)acrylic acid ester selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, a monomer containing at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, and other monomers capable of copolymerization as needed. Meanwhile, in the present invention, "(meth)acrylic acid ester" is used as a general term for esters of acrylic acid and / or methacrylic acid.
[0073] As for the (meth)acrylate alkyl ester, it is not particularly limited, but typically (meth)acrylate alkyl esters having an alkyl group having 1 to 12 carbon atoms, preferably (meth)acrylate alkyl esters having an alkyl group having 1 to 8 carbon atoms, and more preferably (meth)acrylate alkyl esters having an alkyl group having 2 to 6 carbon atoms are used.
[0074] Specific examples of (meth)acrylate alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. Among these, ethyl (meth)acrylate and n-butyl (meth)acrylate are preferred, and ethyl acrylate and n-butyl acrylate are more preferred.
[0075] As for the (meth)acrylic acid alkoxyalkyl ester, it is not particularly limited, but typically a (meth)acrylic acid alkoxyalkyl ester having an alkoxyalkyl group having 2 to 12 carbon atoms, preferably a (meth)acrylic acid alkoxyalkyl ester having an alkoxyalkyl group having 2 to 8 carbon atoms, and more preferably a (meth)acrylic acid alkoxyalkyl ester having an alkoxyalkyl group having 2 to 6 carbon atoms is used.
[0076] Specific examples of (meth)acrylate alkoxyalkyl esters include (meth)acrylate methoxymethyl, (meth)acrylate methoxyethyl, (meth)acrylate methoxypropyl, (meth)acrylate methoxybutyl, (meth)acrylate ethoxymethyl, (meth)acrylate ethoxyethyl, (meth)acrylate propoxyethyl, (meth)acrylate butoxyethyl, etc. Among these, (meth)acrylate methoxyethyl, (meth)acrylate ethoxyethyl, etc. are preferred, and methoxyethyl acrylic acid and ethoxyethyl acrylic acid are more preferred.
[0077] At least one (meth)acrylic acid ester selected from the group consisting of these (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters is used individually or in combination of two or more types, and when the proportion of these in the total monomer components is typically in the range of 50 to 99.99 weight%, preferably 62 to 99.95 weight%, more preferably 74 to 99.9 weight%, particularly preferably 80 to 99.5 weight%, and most preferably 87 to 99 weight%, the weather resistance, heat resistance, and oil resistance of the acrylic rubber are highly excellent and suitable.
[0078] As for the monomer containing at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, there are no specific limitations and it is appropriately selected according to the purpose of use. Preferably, when it is a monomer having a reactive group related to ionic reactivity, more preferably a monomer having carboxyl groups and epoxy groups, and even more preferably a monomer having carboxyl groups, it is suitable because the short-term crosslinking ability and the resistance to permanent compression deformation or water resistance of the crosslinked material can be highly improved.
[0079] There are no specific limitations on the monomer having a carboxyl group, but an ethylene unsaturated carboxylic acid can be suitably used. Examples of ethylene unsaturated carboxylic acids include ethylene unsaturated monocarboxylic acid, ethylene unsaturated dicarboxylic acid, and ethylene unsaturated dicarboxylic acid monoester. Among these, an ethylene unsaturated dicarboxylic acid monoester is particularly preferred because it can further improve the resistance to permanent deformation in compression when acrylic rubber is used as a rubber crosslinker.
[0080] There are no particular limitations on the ethylenically unsaturated monocarboxylic acid, but an ethylenically unsaturated monocarboxylic acid having 3 to 12 carbon atoms is preferred, and examples include acrylic acid, methacrylic acid, α-ethylacrylic acid, crotonic acid, cinnamic acid, etc.
[0081] There are no specific limitations on the ethylenedimethyl dicarboxylic acid, but an ethylenedimethyl dicarboxylic acid having 4 to 12 carbon atoms is preferred, and examples include butenedionic acids such as fumaric acid and maleic acid, itaconic acid, citraconic acid, etc. Meanwhile, the ethylenedimethyl dicarboxylic acid also includes those existing as anhydrous forms.
[0082] The above ethylenically unsaturated dicarboxylic acid monoester is not particularly limited, but typically, an ethylenically unsaturated dicarboxylic acid having 4 to 12 carbon atoms and an alkyl monoester having 1 to 12 carbon atoms, preferably an ethylenically unsaturated dicarboxylic acid having 4 to 6 carbon atoms and an alkyl monoester having 2 to 8 carbon atoms, more preferably an alkyl monoester having 2 to 6 carbon atoms of a butenedionic acid having 4 carbon atoms.
[0083] Specific examples of ethylenically unsaturated dicarboxylic acid monoesters include butenedionic acid monoalkyl esters such as monomethyl fumarate, monoethyl fumarate, monon-butyl fumarate, monomethyl maleate, monoethyl maleate, monon-butyl maleate, monocyclopentyl fumarate, monocyclohexyl fumarate, monocyclohexanyl fumarate, monocyclopentyl maleate, and monocyclohexyl maleate; and itaconic acid monoalkyl esters such as monomethyl itaconate, monoethyl itaconate, monon-butyl itaconate, and monocyclohexyl itaconate. Among these, monon-butyl fumarate and monon-butyl maleate are preferred, and monon-butyl fumarate is particularly preferred.
[0084] Examples of monomers having epoxy groups include epoxy group-containing (meth)acrylic acid esters such as (meth)acrylic acid glycidyl; epoxy group-containing vinyl ethers such as allylglycidyl ether and vinylglycidyl ether; etc.
[0085] Monomers having a chlorine atom are not particularly limited, but examples include, for instance, unsaturated alcohol esters of saturated carboxylic acids containing a chlorine atom, chloroalkyl esters of (meth)acrylic acid, chloroacyloxyalkyl esters of (meth)acrylic acid, (chloroacetylcarbamoyloxy)alkyl esters of (meth)acrylic acid, unsaturated ethers containing a chlorine atom, unsaturated ketones containing a chlorine atom, aromatic vinyl compounds containing a chloromethyl group, unsaturated amides containing a chlorine atom, and unsaturated monomers containing a chloroacetyl group.
[0086] Specific examples of unsaturated alcohol esters of saturated carboxylic acids containing chlorine atoms include vinyl chloroacetate, vinyl 2-chloropropionate, and allyl chloroacetate. Specific examples of chloroalkyl esters of (meth)acrylic acid include chloromethyl (meth)acrylic acid, 1-chloroethyl (meth)acrylic acid, 2-chloroethyl (meth)acrylic acid, 1,2-dichloroethyl (meth)acrylic acid, 2-chloropropyl (meth)acrylic acid, 3-chloropropyl (meth)acrylic acid, and 2,3-dichloropropyl (meth)acrylic acid. Specific examples of (meth)acrylic acid chloroacyloxyalkyl esters include (meth)acrylic acid 2-(chloroacetoxy)ethyl, (meth)acrylic acid 2-(chloroacetoxy)propyl, (meth)acrylic acid 3-(chloroacetoxy)propyl, (meth)acrylic acid 3-(hydroxychloroacetoxy)propyl, etc. Examples of (meth)acrylic acid (chloroacetylcarbamoyloxy)alkyl esters include (meth)acrylic acid 2-(chloroacetylcarbamoyloxy)ethyl, (meth)acrylic acid 3-(chloroacetylcarbamoyloxy)propyl, etc. Specific examples of chlorine atom-containing unsaturated ethers include chloromethylvinyl ether, 2-chloroethylvinyl ether, 3-chloropropylvinyl ether, 2-chloroethylallyl ether, 3-chloropropylallyl ether, etc. Specific examples of chlorine atom-containing unsaturated ketones include 2-chloroethylvinyl ketone, 3-chloropropylvinyl ketone, 2-chloroethylallyl ketone, etc. Specific examples of chloromethyl group-containing aromatic vinyl compounds include p-chloromethylstyrene, m-chloromethylstyrene, o-chloromethylstyrene, p-chloromethyl-α-methylstyrene, etc. Specific examples of chlorine atom-containing unsaturated amides include N-chloromethyl(meth)acrylamide, etc. In addition, specific examples of chloroacetyl group-containing unsaturated monomers include 3-(hydroxychloroacetoxy)propylallyl ether, p-vinylbenzyl chloroacetate ester, etc.
[0087] Monomers containing at least one reactive group selected from the group consisting of these carboxyl groups, epoxy groups, and chlorine atoms are each used alone or in combination of two or more, and the proportion of the monomer in the total composition is typically in the range of 0.01 to 10 weight%, preferably 0.05 to 8 weight%, more preferably 0.1 to 6 weight%, particularly preferably 0.5 to 5 weight%, and most preferably 1 to 3 weight%.
[0088] As for monomers other than those mentioned above that can be used together with each of the above monomers as needed (abbreviated as “other monomers” in the present invention), there are no particular limitations as long as they are copolymerizable with the above monomers, and examples include aromatic vinyls such as styrene, α-methylstyrene, and divinylbenzene; ethylenically unsaturated nitriles such as acrylonitrile and methacrylonitrile; acrylamide-based monomers such as acrylamide and methacrylamide; and olefin-based monomers such as ethylene, propylene, vinyl acetate, ethyl vinyl ether, and butyl vinyl ether.
[0089] These other monomers are each used alone or in combination of two or more types, and the proportion of the total monomer components is typically limited to a range of 0 to 40 weight%, preferably 0 to 30 weight%, more preferably 0 to 20 weight%, particularly preferably 0 to 15 weight%, and most preferably 0 to 10 weight%.
[0090] Acrylic Rubber
[0091] The acrylic rubber of the present invention has at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, preferably composed of the monomer component, and is also characterized by having a weight average molecular weight (Mw), a ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) (Mw / Mn), a gel amount, an ash amount, and an ash component amount.
[0092] The monomer of the acrylic rubber of the present invention comprises a bonding unit from a monomer containing at least one (meth)acrylic acid ester selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, and other monomers included as necessary, wherein the respective proportion in the acrylic rubber is such that the bonding unit derived from at least one (meth)acrylic acid ester selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters is typically in the range of 50 to 99.99 wt%, preferably 62 to 99.95 wt%, more preferably 74 to 99.9 wt%, particularly preferably 80 to 99.5 wt%, and most preferably 87 to 99 wt%, and at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms The monomer-derived bonding units contained therein are typically in the range of 0.01 to 10 wt%, preferably 0.05 to 8 wt%, more preferably 0.1 to 6 wt%, particularly preferably 0.5 to 5 wt%, and most preferably 1 to 3 wt%, and other monomer-derived bonding units are typically in the range of 0 to 40 wt%, preferably 0 to 30 wt%, more preferably 0 to 20 wt%, particularly preferably 0 to 15 wt%, and most preferably 0 to 10 wt%. When the monomer composition of the acrylic rubber is within this range, properties such as short-term crosslinkability, resistance to permanent compression deformation, weather resistance, heat resistance, and oil resistance are highly balanced and suitable.
[0093] When the weight average molecular weight (Mw) of the acrylic rubber of the present invention is in the range of 1 million to 5 million, preferably 1.1 million to 4 million, more preferably 1.2 million to 3 million, particularly preferably 1.5 million to 2.5 million, and most preferably 1.6 million to 2.2 million, the injection moldability, strength characteristics, and resistance to permanent deformation of the acrylic rubber are highly balanced and suitable. If the weight average molecular weight (Mw) of the acrylic rubber is excessively large, the injection moldability decreases, and if it is excessively small, the strength characteristics or resistance to permanent deformation of the acrylic rubber decreases, and neither is desirable.
[0094] The number average molecular weight (Mn) of the acrylic rubber of the present invention is not particularly limited, but is typically in the range of 300,000 to 1,500,000, preferably 350,000 to 1,300,000, more preferably 400,000 to 1,100,000, particularly preferably 500,000 to 1,000,000, and most preferably 550,000 to 750,000, at which point the injection moldability, strength characteristics, and resistance to permanent deformation of the acrylic rubber are highly balanced and suitable.
[0095] The z-average molecular weight (Mz) of the acrylic rubber of the present invention is not specifically limited and can be appropriately selected according to the purpose of use, but is typically 1.5 million or more, preferably 2 million or more, more preferably 2.5 million or more, and particularly preferably 3 million or more. Furthermore, when the z-average molecular weight (Mz) of the acrylic rubber of the present invention is in the range of typically 1.5 million to 6 million, preferably 1.8 million to 5.5 million, more preferably 2 million to 5 million, particularly preferably 2.2 million to 4.5 million, and most preferably 2.5 million to 4 million, the injection moldability, Banbury processability, strength characteristics, and resistance to permanent deformation of the acrylic rubber are highly balanced and suitable.
[0096] When the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the acrylic rubber of the present invention is in the range of 1.5 to 3, preferably 1.8 to 2.7, more preferably 2 to 2.6, and particularly preferably 2.2 to 2.6, the injection moldability of the acrylic rubber and the strength characteristics and resistance to permanent deformation in the case of crosslinking are highly balanced and suitable. In particular, when the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the acrylic rubber of the present invention is in this range, any of the characteristics of the shape forming ability, fusion ability, and release ability of the injection moldability of the acrylic rubber are significantly superior, and furthermore, the strength characteristics and resistance to permanent deformation in the case of crosslinking are also highly balanced and suitable. If the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the acrylic rubber is excessively large or excessively small, the injection moldability deteriorates, and neither is desirable.
[0097] The molecular weight distribution of the acrylic rubber of the present invention, focusing on the high molecular weight region, is not particularly limited, but is suitable when the ratio of the z-average molecular weight (Mz) to the weight-average molecular weight (Mw) (Mz / Mw) is typically 1.3 or higher, preferably 1.4 or higher, more preferably 1.5 or higher, particularly preferably 1.6 or higher, and most preferably 1.7 or higher, as this prevents deterioration of mold release properties or shape-forming properties (burr generation) when the weight-average molecular weight (Mw) becomes excessively small. The molecular weight distribution (Mz / Mw) of the acrylic rubber of the present invention, focusing on the high molecular weight region, is also suitable when it is typically 4 or lower, preferably 3 or lower, more preferably 2.5 or lower, particularly preferably 2.2 or lower, and most preferably 2 or lower, as this prevents deterioration of shape-forming properties (insufficient shape) or fusion properties when the weight-average molecular weight (Mw) becomes excessively large. When the molecular weight distribution (Mz / Mw) of the acrylic rubber of the present invention, centered on the high molecular weight region, is in the range of typically 1.3 to 3, preferably 1.4 to 2.5, more preferably 1.5 to 2.2, particularly preferably 1.6 to 2, and most preferably 1.7 to 1.9, it is suitable for highly improving injection moldability and Banbury processability without damaging the strength characteristics of the acrylic rubber.
[0098] Although there are no specific limitations on the measurement of the molecular weight (Mn, Mw, Mz) and molecular weight distribution (Mw / Mn, Mz / Mw) of the acrylic rubber of the present invention, each characteristic is more accurately determined and suitable when the absolute molecular weight (Mn, Mw, Mz) and absolute molecular weight distribution (Mw / Mn, Mz / Mw) are obtained by the GPC-MALS method.
[0099] The measuring solvent of the GPC-MALS method for measuring the molecular weight (Mn, Mw, Mz) and molecular weight distribution (Mw / Mn, Mz / Mw) of the acrylic rubber of the present invention is not particularly limited as long as it can dissolve and measure the acrylic rubber of the present invention, but a dimethylformamide-based solvent is suitable. The dimethylformamide-based solvent used is not particularly limited as long as it has dimethylformamide as the main component, but 100% dimethylformamide or a polar substance added to dimethylformamide can be used. The proportion of dimethylformamide in the dimethylformamide-based solvent is 90% by weight or more, preferably 95% by weight or more, and more preferably 97% by weight or more. The compound added to dimethylformamide is not particularly limited, but in the present invention, a solution in which lithium chloride is added to dimethylformamide at a concentration of 0.05 mol / L and 37% concentrated hydrochloric acid at a concentration of 0.01% is particularly suitable.
[0100] When the gel content of the acrylic rubber of the present invention is 50% by weight or less, preferably 30% by weight or less, more preferably 15% by weight or less, particularly preferably 10% by weight or less, and most preferably 5% by weight or less as the amount insoluble in methyl ethyl ketone, the processability and injection moldability during mixing with Banbury, etc. are highly improved and suitable.
[0101] When the gel amount of the acrylic rubber of the present invention is measured at 20 random points, the values are not particularly limited, but when all 20 points fall within the range of (average value ± 5) weight%, preferably when all 20 points fall within the range of (average value ± 3) weight%, there is no deviation in processability, and various physical properties of the rubber mixture or rubber crosslinked product are stabilized and suitable. Meanwhile, the fact that the gel amount of the acrylic rubber is measured at 20 random points means that all 20 points fall within the range of average value ± 5. This implies that all 20 measured gel amounts fall within the range of (average value - 5) to (average value + 5) weight%. For example, if the average value of the measured gel amount is 20 weight%, it means that all 20 measured values fall within the range of 15 to 25 weight%.
[0102] The acrylic rubber of the present invention is suitable for highly balanced Banbury processability and strength characteristics when the hydrate crumb generated in the coagulation reaction is melt-kneaded and dried in a screw-type twin-screw extrusion dryer in a state where almost all water has been removed (water content less than 1 weight%).
[0103] The ash content of the acrylic rubber of the present invention is 0.3 weight% or less, preferably 0.2 weight% or less, more preferably 0.18 weight% or less, particularly preferably 0.15 weight% or less, and most preferably 0.13 weight% or less. When within this range, the water resistance, storage stability, strength characteristics, processability, and injection moldability of the acrylic rubber are highly balanced and suitable.
[0104] The lower limit of the ash content of the acrylic rubber of the present invention is not specifically limited and can be appropriately selected according to the purpose of use. When it is typically 0.0001 weight% or more, preferably 0.0005 weight% or more, more preferably 0.001 weight% or more, particularly preferably 0.005 weight% or more, and most preferably 0.01 weight% or more, the metal adhesion of the rubber is reduced, resulting in excellent workability, and also the injection moldability, particularly the release properties, are excellent, making it suitable.
[0105] The ash content of the acrylic rubber of the present invention, when water resistance, storage stability, strength characteristics, processability, workability, and injection moldability are highly balanced, is typically in the range of 0.0001 to 0.3 weight%, preferably 0.0005 to 0.2 weight%, more preferably 0.001 to 0.18 weight%, particularly preferably 0.005 to 0.15 weight%, and most preferably 0.01 to 0.13 weight%.
[0106] When the total amount of sodium, magnesium, calcium, phosphorus, and sulfur in the ash of the acrylic rubber of the present invention is 80 weight% or more, preferably 90 weight% or more, more preferably 95 weight% or more, the water resistance of the acrylic rubber and the fusion and release properties of injection molding are highly improved and suitable.
[0107] The total amount of magnesium and phosphorus in the ash of the acrylic rubber of the present invention is not specifically limited and can be appropriately selected according to the purpose of use, but when it is typically 30 weight% or more, preferably 50 weight% or more, more preferably 70 weight% or more, particularly preferably 80 weight% or more, and most preferably 90 weight% or more, the water resistance, strength characteristics, and the fusion, release, and processability of the acrylic rubber in injection molding are highly balanced and suitable.
[0108] The amount of magnesium in the ash of the acrylic rubber of the present invention is not specifically limited and is appropriately selected according to the purpose of use, but is typically in the range of 10 weight% or more, preferably 15 to 60 weight%, more preferably 20 to 50 weight%, particularly preferably 25 to 45 weight%, and most preferably 30 to 40 weight%.
[0109] The phosphorus content in the ash of the acrylic rubber of the present invention is not specifically limited and is appropriately selected according to the purpose of use, but is typically in the range of 10 weight% or more, preferably 20 to 90 weight%, more preferably 30 to 80 weight%, particularly preferably 40 to 70 weight%, and most preferably 50 to 60 weight%.
[0110] The ratio of magnesium to phosphorus ([Mg] / [P]) in the ash of the acrylic rubber of the present invention is not specifically limited and can be appropriately selected according to the purpose of use. When the ratio is in the range of 0.4 to 2.5 by weight, preferably 0.45 to 1.2, more preferably 0.45 to 1, particularly preferably 0.5 to 0.8, and most preferably 0.55 to 0.7, the water resistance, strength characteristics, and the fusion, release, and processability of the acrylic rubber are highly balanced and suitable.
[0111] Here, the ash content in acrylic rubber is mainly derived from the emulsifier used when emulsifying monomer components for emulsion polymerization and the coagulant used when coagulating the emulsion polymerization solution, but the total ash content and the content of each component in the ash content vary not only under the conditions of the emulsion polymerization process and the coagulation process, but also under various conditions of subsequent processes.
[0112] In order for the water resistance, strength characteristics, injection molding fusion, mold release, and processability of acrylic rubber to be highly balanced, it is particularly suitable to use an anionic emulsifier, a cationic emulsifier, or a nonionic emulsifier described below, preferably an anionic emulsifier, and more preferably a phosphate ester salt or a sulfate ester salt as an emulsifier. The water resistance of acrylic rubber is uniquely correlated with the amount of ash in the acrylic rubber and the total amount of sodium, magnesium, calcium, phosphorus, and sulfur in the ash, and by using the above emulsifier, the water resistance, strength characteristics, injection molding fusion, mold release, and processability of acrylic rubber can be further highly balanced, which is suitable.
[0113] In order for the water resistance, strength characteristics, injection molding fusion, mold release, and processability of acrylic rubber to be highly balanced, it is particularly suitable to use the metal salt described below as a coagulant, preferably an alkali metal salt or a Group 2 metal salt of the periodic table. The water resistance of acrylic rubber is uniquely correlated with the amount of ash in the acrylic rubber and the total amount of sodium, magnesium, calcium, phosphorus, and sulfur in the ash; by using the above coagulant, the water resistance, strength characteristics, injection molding fusion, mold release, and processability of acrylic rubber are further highly balanced and suitable.
[0114] The glass transition temperature (Tg) of the acrylic rubber of the present invention may be appropriately selected according to the intended use of the acrylic rubber, but it is suitable because processability and cold resistance are excellent when it is typically 20°C or lower, preferably 10°C or lower, and more preferably 0°C or lower. The lower limit of the glass transition temperature (Tg) of the acrylic rubber is not particularly limited, but is typically -80°C or higher, preferably -60°C or higher, and more preferably -40°C or higher. By setting the glass transition temperature above the above lower limit, oil resistance and heat resistance can be made better, and by setting it below the above upper limit, processability, crosslinkability, and cold resistance can be made better.
[0115] The complex viscosity ([η]100°C) of the acrylic rubber of the present invention at 100°C is not subject to any particular limitation and can be appropriately selected according to the purpose of use. Typically, when it is in the range of 15,000 [Pa·s] or less, preferably 1,000 to 10,000 [Pa·s], more preferably 2,000 to 8,000 [Pa·s], particularly preferably 3,000 to 5,000 [Pa·s], and most preferably 3,500 to 4,000 [Pa·s], it is suitable because it has excellent processability, oil resistance, injection moldability, and shape retention.
[0116] The ratio of the complex viscosity at 100°C ([η]100°C) and the complex viscosity at 60°C ([η]60°C) of the acrylic rubber of the present invention ([η]100°C / [η]60°C) is not specifically limited and can be appropriately selected according to the purpose of use, but is typically 0.5 or higher, preferably 0.6 or higher, and more preferably 0.7 or higher. The ratio of the complex viscosity at 100°C ([η]100°C) and the complex viscosity at 60°C ([η]60°C) of the acrylic rubber of the present invention ([η]100°C / [η]60°C) is also, typically in the range of 0.5 to 0.99, preferably 0.55 to 0.95, more preferably 0.6 to 0.9, particularly preferably 0.65 to 0.85, and most preferably 0.7 to 0.8, when the processability, oil resistance, and shape retention are highly balanced and suitable.
[0117] The specific gravity of the acrylic rubber of the present invention is not particularly limited, but is typically 0.7 or higher, preferably 0.8 or higher, more preferably 0.9 or higher, particularly preferably 0.95 or higher, and most preferably 1 or higher, at which point it contains almost no air, resulting in excellent storage stability and suitability. Furthermore, the specific gravity of the acrylic rubber molded body of the present invention is typically in the range of 0.7 to 1.6, preferably 0.8 to 1.5, more preferably 0.9 to 1.4, particularly preferably 0.95 to 1.3, and most preferably 1.0 to 1.2, at which point productivity, storage stability, and stability of the crosslinking characteristics of the crosslinker are highly balanced and suitability. When the specific gravity of the acrylic rubber is excessively low, it indicates a large amount of air in the acrylic rubber, which significantly affects storage stability, including oxidative degradation, and is therefore undesirable.
[0118] Meanwhile, the specific gravity of the acrylic rubber of the present invention is the mass divided by the volume including voids, that is, the mass measured in air divided by the buoyancy, and is typically measured in accordance with Method A of JIS K6268 Crosslinked Rubber-Density Measurement.
[0119] The acrylic rubber of the present invention is also suitable because the moisture crumb generated in the coagulation reaction is dried under reduced pressure by a screw-type twin-screw extrusion dryer, or melt-mixed and dried under reduced pressure, and the properties of storage stability, injection moldability, and strength are particularly excellent and highly balanced.
[0120] The water content of the acrylic rubber of the present invention is not specifically limited and is appropriately selected according to the purpose of use. Typically, when it is less than 1 weight%, preferably 0.8 weight% or less, and more preferably 0.6 weight% or less, the vulcanization characteristics of the acrylic rubber are optimized and characteristics such as heat resistance and water resistance are highly improved and suitable.
[0121] The pH of the acrylic rubber of the present invention is not specifically limited and can be appropriately selected according to the purpose of use, but when it is typically in the range of 6 or less, preferably 2 to 6, more preferably 2.5 to 5.5, and most preferably 3 to 5, the storage stability of the acrylic rubber is highly improved and suitable.
[0122] The Mooney viscosity (ML1+4, 100°C) of the acrylic rubber of the present invention is not specifically limited and can be appropriately selected according to the purpose of use, but when it is typically in the range of 10 to 150, preferably 20 to 100, and more preferably 25 to 70, the processability and strength characteristics of the acrylic rubber are highly balanced and suitable.
[0123] The shape of the acrylic rubber of the present invention is not particularly limited and can be appropriately selected according to the purpose of use. For example, it may be in powder form, crumb form, strand form, sheet form, bale form, etc., but preferably, when it is in sheet form or bale form, it is suitable because it has excellent workability and storage stability.
[0124] When the acrylic rubber of the present invention is in sheet form, the thickness is not specifically limited and is appropriately selected according to the purpose of use; typically, when it is in the range of 1 to 40 mm, preferably 2 to 35 mm, more preferably 3 to 30 mm, and most preferably 5 to 25 mm, workability, storage stability, and productivity are highly balanced and suitable. The width of the sheet-type acrylic rubber of the present invention is appropriately selected according to the purpose of use; typically, when it is in the range of 300 to 1200 mm, preferably 400 to 1000 mm, and more preferably 500 to 800 mm, it is particularly suitable for excellent handling. The length of the sheet-type acrylic rubber of the present invention is not specifically limited, but typically, when it is in the range of 300 to 1200 mm, preferably 400 to 1000 mm, and more preferably 500 to 800 mm, it is particularly suitable for excellent handling.
[0125] When the acrylic rubber of the present invention is in the form of a bale, the size is not specifically limited and is appropriately selected according to the purpose of use; the width is typically in the range of 100 to 800 mm, preferably 200 to 500 mm, more preferably 250 to 450 mm; the length is typically in the range of 300 to 1,200 mm, preferably 400 to 1,000 mm, more preferably 500 to 800 mm; and the height (thickness) is typically in the range of 50 to 500 mm, preferably 100 to 300 mm, more preferably 150 to 250 mm. In addition, the shape of the bale-shaped acrylic rubber of the present invention is not limited and is appropriately selected according to the purpose of use of the acrylic rubber bale; in many cases, a rectangular shape is suitable.
[0126] Method for manufacturing acrylic rubber
[0127] The above method for manufacturing acrylic rubber is not particularly limited, but includes, for example, an emulsification process of emulsifying an acrylic rubber monomer component comprising a monomer containing at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom, with water and an emulsifier; and
[0128] An emulsion polymerization process that initiates polymerization in the presence of a redox catalyst comprising an organic radical generator and a reducing agent, and continues polymerization by batchly adding a chain transfer agent during polymerization to obtain an emulsion polymerization solution, and
[0129] A coagulation process in which the obtained emulsion polymer is added to a stirring coagulation liquid to coagulate and produce a hydrated crumb, and
[0130] A cleaning process for cleaning the generated function crumb, and
[0131] A dehydration process for dehydrating washed moisture crumbs to a moisture content of 1 to 50 weight percent, and
[0132] Drying process for drying dehydrated crumb to less than 1 weight percent
[0133] Examples include methods for manufacturing acrylic rubber that include [the following].
[0134] (Emulsion process)
[0135] The emulsification process in the method for manufacturing acrylic rubber of the present invention is a process of emulsifying an acrylic rubber monomer component containing a monomer having at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom with water and an emulsifier.
[0136] (Monomer component)
[0137] The monomer component used in the present invention comprises an acrylic rubber monomer component comprising a monomer containing at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, preferably at least one (meth)acrylic acid ester selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, a monomer containing at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, and, if necessary, other monomers capable of copolymerization, which are identical to the examples and preferred ranges of monomer components described above. The amount of monomer component used is also as described above, and in emulsion polymerization, each monomer may be appropriately selected to achieve the above composition of the acrylic rubber of the present invention.
[0138] (Emulsifier)
[0139] The emulsifier used in the present invention is not particularly limited, but examples include anionic emulsifiers, cationic emulsifiers, nonionic emulsifiers, etc., and preferably anionic emulsifiers.
[0140] There are no specific limitations on anionic emulsifiers, and examples include salts of fatty acids such as myristic acid, palmitic acid, oleic acid, and linolenic acid; alkylbenzene sulfonates such as sodium dodecylbenzenesulfonate; sulfate esters such as sodium lauryl sulfate; phosphate esters such as polyoxyalkylenealkyl ether phosphate esters; and alkylsulfosuccinates. Among these anionic emulsifiers, phosphate esters and sulfate esters are preferred, phosphate esters are particularly preferred, and divalent phosphate esters are most preferred, as they can highly balance the water resistance, strength characteristics, mold release properties, and processability of the resulting acrylic rubber. In addition, when these phosphate ester salts or sulfate ester salts are preferably alkali metal salts of phosphate esters or sulfate esters, and more preferably sodium salts of phosphate esters or sulfate esters, the water resistance, strength characteristics, mold release properties, and processability of the acrylic rubber obtained can be highly balanced and are suitable.
[0141] As for the divalent phosphate ester salts, they are not particularly limited as long as they can be used as emulsifiers in emulsion polymerization reactions, but examples include alkyloxypolyoxyalkylene phosphate ester salts, alkylphenyloxypolyoxyalkylene phosphate ester salts, etc. Among these, their metal salts are preferred, their alkali metal salts are more preferred, and their sodium salts are most preferred.
[0142] Examples of the above alkyloxypolyoxyalkylene phosphate ester salts include alkyloxypolyoxyethylene phosphate ester salts, alkyloxypolyoxypropylene phosphate ester salts, etc., and among these, alkyloxypolyoxyethylene phosphate ester salts are preferred.
[0143] Specific examples of alkyloxypolyoxyethylene phosphate ester salts include octyloxydioxyethylene phosphate ester, octyloxytrioxyethylene phosphate ester, octyloxytetraoxyethylene phosphate ester, decyloxytetraoxyethylene phosphate ester, dodecyloxytetraoxyethylene phosphate ester, tridecyloxytetraoxyethylene phosphate ester, tetradecyloxytetraoxyethylene phosphate ester, hexadecyloxytetraoxyethylene phosphate ester, octadecyloxytetraoxyethylene phosphate ester, octyloxypentaoxyethylene phosphate ester, decyloxypentaoxyethylene phosphate ester, dodecyloxypentaoxyethylene phosphate ester, tridecyloxypentaoxyethylene phosphate ester, tetradecyloxypentaoxyethylene phosphate ester, hexadecyloxypentaoxyethylene phosphate ester, octadecyloxypentaoxyethylene phosphate ester. Examples of metal salts include octyloxyhexaoxyethylene phosphate esters, decyloxyhexaoxyethylene phosphate esters, dodecyloxyhexaoxyethylene phosphate esters, tridecyloxyhexaoxyethylene phosphate esters, tetradecyloxyhexaoxyethylene phosphate esters, hexadecyloxyhexaoxyethylene phosphate esters, octadecyloxyhexaoxyethylene phosphate esters, octyloxyoctaoxyethylene phosphate esters, decyloxyoctaoxyethylene phosphate esters, dodecyloxyoctaoxyethylene phosphate esters, tridecyloxyoctaoxyethylene phosphate esters, tetradecyloxyoctaoxyethylene phosphate esters, hexadecyloxyoctaoxyethylene phosphate esters, and octadecyloxyoctaoxyethylene phosphate esters. Among these, their alkali metal salts, especially sodium salts, are suitable.
[0144] Specific examples of alkyloxypolyoxypropylene phosphate ester salts include octyloxydioxypropylene phosphate ester, octyloxytrioxypropylene phosphate ester, octyloxytetraoxypropylene phosphate ester, decyloxytetraoxypropylene phosphate ester, dodecyloxytetraoxypropylene phosphate ester, tridecyloxytetraoxypropylene phosphate ester, tetradecyloxytetraoxypropylene phosphate ester, hexadecyloxytetraoxypropylene phosphate ester, octadecyloxytetraoxypropylene phosphate ester, octyloxypentaoxypropylene phosphate ester, decyloxypentaoxypropylene phosphate ester, dodecyloxypentaoxypropylene phosphate ester, tridecyloxypentaoxypropylene phosphate ester, tetradecyloxypentaoxypropylene phosphate ester, and hexadecyloxypentaoxypropylene phosphate ester. Examples include octadecyloxypentaoxypropylene phosphate esters, octyloxyhexaoxypropylene phosphate esters, decyloxyhexaoxypropylene phosphate esters, dodecyloxyhexaoxypropylene phosphate esters, tridecyloxyhexaoxypropylene phosphate esters, tetradecyloxyhexaoxypropylene phosphate esters, hexadecyloxyhexaoxypropylene phosphate esters, octadecyloxyhexaoxypropylene phosphate esters, octyloxyoctaoxypropylene phosphate esters, decyloxyoctaoxypropylene phosphate esters, dodecyloxyoctaoxypropylene phosphate esters, tridecyloxyoctaoxypropylene phosphate esters, tetradecyloxyoctaoxypropylene phosphate esters, hexadecyloxyoctaoxypropylene phosphate esters, octadecyloxyoctaoxypropylene phosphate esters, and their metal salts, and among these, their alkali metal salts, Sodium salts are particularly suitable.
[0145] Specific examples of alkylphenyloxypolyoxyalkylene phosphate ester salts include alkylphenyloxypolyoxyethylene phosphate ester salts and alkylphenyloxypolyoxypropylene phosphate ester salts, and among these, alkylphenyloxypolyoxyethylene phosphate ester salts are preferred.
[0146] Specific examples of alkylphenyloxypolyoxyethylene phosphate ester salts include methylphenyloxytetraoxyethylene phosphate ester, ethylphenyloxytetraoxyethylene phosphate ester, butylphenyloxytetraoxyethylene phosphate ester, hexylphenyloxytetraoxyethylene phosphate ester, nonylphenyloxytetraoxyethylene phosphate ester, dodecylphenyloxytetraoxyethylene phosphate ester, octadecyloxytetraoxyethylene phosphate ester, methylphenyloxypentaoxyethylene phosphate ester, ethylphenyloxypentaoxyethylene phosphate ester, butylphenyloxypentaoxyethylene phosphate ester, hexylphenyloxypentaoxyethylene phosphate ester, nonylphenyloxypentaoxyethylene phosphate ester, dodecylphenyloxypentaoxyethylene phosphate ester, methylphenyloxyhexaoxyethylene phosphate ester, ethylphenyloxyhexaoxyethylene phosphate ester, and butylphenyloxyhexaoxyethylene phosphate ester. Examples of metal salts include hexylphenyloxyhexaoxyethylene phosphate ester, nonylphenyloxyhexaoxyethylene phosphate ester, dodecylphenyloxyhexaoxyethylene phosphate ester, methylphenyloxyhexaoxyethylene phosphate ester, ethylphenyloxyoctaoxyethylene phosphate ester, butylphenyloxyoctaoxyethylene phosphate ester, hexylphenyloxyoctaoxyethylene phosphate ester, nonylphenyloxyoctaoxyethylene phosphate ester, and dodecylphenyloxyoctaoxyethylene phosphate ester. Among these, their alkali metal salts, especially sodium salts, are suitable.
[0147] Specific examples of alkylphenyloxypolyoxypropylene phosphate ester salts include methylphenyloxytetraoxypropylene phosphate ester, ethylphenyloxytetraoxypropylene phosphate ester, butylphenyloxytetraoxypropylene phosphate ester, hexylphenyloxytetraoxypropylene phosphate ester, nonylphenyloxytetraoxypropylene phosphate ester, dodecylphenyloxytetraoxypropylene phosphate ester, methylphenyloxypentaoxypropylene phosphate ester, ethylphenyloxypentaoxypropylene phosphate ester, butylphenyloxypentaoxypropylene phosphate ester, hexylphenyloxypentaoxypropylene phosphate ester, nonylphenyloxypentaoxypropylene phosphate ester, dodecylphenyloxypentaoxypropylene phosphate ester, methylphenyloxyhexaoxypropylene phosphate ester, ethylphenyloxyhexaoxypropylene phosphate ester, butylphenyloxyhexaoxypropylene phosphate ester. Examples of metal salts include hexylphenyloxyhexaoxypropylene phosphate ester, nonylphenyloxyhexaoxypropylene phosphate ester, dodecylphenyloxyhexaoxypropylene phosphate ester, methylphenyloxyoctaoxypropylene phosphate ester, ethylphenyloxyoctaoxypropylene phosphate ester, butylphenyloxyoctaoxypropylene phosphate ester, hexylphenyloxyoctaoxypropylene phosphate ester, nonylphenyloxyoctaoxypropylene phosphate ester, and dodecylphenyloxyoctaoxypropylene phosphate ester. Among these, their alkali metal salts, particularly sodium salts, are suitable.
[0148] As for the phosphate ester salt, monovalent phosphate ester salts such as di(alkyloxypolyoxyalkylene)phosphate ester sodium salt can be used alone or in combination with divalent phosphate ester salts.
[0149] Examples of sulfate ester salts include sodium lauryl sulfate, potassium lauryl sulfate, ammonium lauryl sulfate, sodium myristyl sulfate, sodium polyoxyethylene alkyl sulfate, sodium polyoxyethylene alkylaryl sulfate, etc., and preferably sodium lauryl sulfate.
[0150] Examples of cationic emulsifiers include alkyltrimethylammonium chloride, dialkylammonium chloride, benzylammonium chloride, etc.
[0151] Examples of nonionic emulsifiers include polyoxyalkylene fatty acid esters such as polyoxyethylene stearic acid ester; polyoxyalkylene alkyl ethers such as polyoxyethylene dodecyl ether; polyoxyalkylene alkylphenol ethers such as polyoxyethylene nonylphenyl ether; and polyoxyethylene sorbitan alkyl esters. Polyoxyalkylene alkyl ethers and polyoxyalkylene alkylphenol ethers are preferred, and polyoxyethylene alkyl ethers and polyoxyethylene alkylphenol ethers are more preferred.
[0152] These emulsifiers can each be used alone or in combination of two or more types, and the amount used is typically in the range of 0.01 to 10 parts by weight, preferably 0.1 to 5 parts by weight, and more preferably 1 to 3 parts by weight, per 100 parts by weight of monomer components.
[0153] The method of mixing the monomer component, water, and emulsifier (mixing method) may follow conventional methods, for example, a method of mixing the monomer, emulsifier, and water using a stirrer such as a homogenizer or a disc turbine. The amount of water used is typically in the range of 1 to 1,000 parts by weight, preferably 5 to 500 parts by weight, more preferably 4 to 300 parts by weight, particularly preferably 3 to 150 parts by weight, and most preferably 20 to 80 parts by weight, per 100 parts by weight of the monomer component.
[0154] (Emulsion polymerization process)
[0155] The emulsion polymerization process in the method for manufacturing acrylic rubber of the present invention is a process of initiating polymerization in the presence of a redox catalyst consisting of an organic radical generator and a reducing agent, and continuing the polymerization by adding a chain transfer agent in batches during the polymerization to obtain an emulsion polymerization solution.
[0156] (Organic radical generator)
[0157] The polymerization catalyst used in the present invention is characterized by using a redox catalyst composed of an organic radical generator and a reducing agent, which is suitable as it can highly improve the injection moldability and strength characteristics of the resulting acrylic rubber. In particular, it is suitable as it can highly improve the injection moldability of the acrylic rubber produced by using an organic radical generator.
[0158] As for organic radical generators, there are no specific limitations as long as they are commonly used in emulsion polymerization, and examples include organic peroxides, azo compounds, etc.
[0159] As for organic peroxides, there are no particular limitations as long as they are known types used in emulsion polymerization, for example, 2,2-di(4,4-di-(t-butylperoxy)cyclohexyl)propane, 1-di-(t-hexylperoxy)cyclohexane, 1,1-di-(t-butylperoxy)cyclohexane, 4,4-di-(t-butylperoxy)n-butyl valeric acid, 2,2-di-(t-butylperoxy)butane, t-butylhydroperoxide, cumenehydroperoxide, diisopropylbenzenehydroperoxide, paramethanhydroperoxide, benzoyl peroxide, 1,1,3,3-tetraethylbutylhydroperoxide, t-butylcumyl peroxide, di-t-butylperoxide, di-t-hexylperoxide, Di(2-t-butylperoxyisopropyl)benzene, dicumyl peroxide, diisobutyryl peroxide, di(3,5,5-trimethylhexanoyl)peroxide, dilauroyl peroxide, disuccinic acid peroxide, dibenzoyl peroxide, di(3-methylbenzoyl)peroxide, benzoyl(3-methylbenzoyl)peroxide, diisobutyryl peroxydicarbonate, di-n-propylperoxydicarbonate, di(2-ethylhexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, 1,1,3,3-tetramethylbutylperoxyneodecanate, t-hexylperoxypivalate, t-butylperoxyneodecanate, t-hexylperoxypivalate, t-butylperoxypivalate, Examples include 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanate, t-hexylperoxy-2-ethylhexanate, t-butylperoxy-3,5,5-trimethylhexanate, t-hexylperoxyisopropylmonocarbonate, t-butylperoxyisopropylmonocarbonate, t-butylperoxy-2-ethylhexylmonocarbonate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxyacetate, t-hexylperoxybenzoate, t-butylperoxybenzoate, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, etc., and among these, diisopropylbenzene hydroperoxide, cumene hydroperoxide, Paramethan hydroperoxide, benzoyl peroxide, etc. are preferred.
[0160] Examples of azo compounds include azobis(isobutyronitrile), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis[2-(2-imidazoline-2-yl)propane, 2,2'-azobis(propane-2-carbomidine), 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropanamide], 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazoline-2-yl]propane}, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane), and 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propanamide}.
[0161] These organic radical generators can be used individually or in combination of two or more types, and the amount used is typically in the range of 0.0001 to 5 parts by weight, preferably 0.0005 to 1 part by weight, and more preferably 0.001 to 0.5 parts by weight, per 100 parts by weight of the monomer component.
[0162] (reducing agent)
[0163] The reducing agent used in the present invention is not specifically limited as long as it is one commonly used in emulsion polymerization, but preferably at least two types of reducing agents are used, and combining a metal ion compound in a reduced state with other reducing agents is suitable as it can further highly balance the injection moldability and strength characteristics of the acrylic rubber obtained.
[0164] Metal ion compounds in a reduced state are not particularly limited, but examples include ferrous sulfate, sodium ferric acetate hexamethylenediamine tetraacetate, and copper(I) naphthenate, and among these, ferrous sulfate is preferred. These metal ion compounds in a reduced state can each be used individually or in combination of two or more types, and the amount used is typically in the range of 0.000001 to 0.01 parts by weight, preferably 0.00001 to 0.001 parts by weight, and more preferably 0.00005 to 0.0005 parts by weight, per 100 parts by weight of monomer components.
[0165] The reducing agents used in the present invention, other than metal ion compounds in a reduced state, are not particularly limited but include, for example, ascorbic acid or its salts such as ascorbic acid, sodium ascorbate, potassium ascorbate; erythorbic acid or its salts such as erythorbic acid, sodium erythorbate, potassium erythorbate; sulfinates such as sodium hydroxymethanesulfinate; sulfites of sodium sulfite, potassium sulfite, sodium bisulfite, sodium aldehyde bisulfite, potassium bisulfite; pyrosulfites such as sodium pyrosulfite, potassium pyrosulfite, sodium bisulfite, potassium bisulfite; thiosulfates such as sodium thiosulfate, potassium thiosulfate; phosphoric acid or its salts such as phosphoric acid, sodium phosphite, potassium phosphite, sodium biphosphite, and potassium biphosphite. Examples include pyrophosphoric acid or its salts, such as pyrophosphoric acid, sodium pyrophosphoric acid, potassium pyrophosphoric acid, sodium hydrogen pyrophosphoric acid, and potassium hydrogen pyrophosphoric acid; sodium formaldehyde sulfoxylate, etc. Among these, ascorbic acid or its salt, sodium formaldehyde sulfoxylate, etc. are preferred, and ascorbic acid or its salt is particularly preferred.
[0166] Reducing agents other than metal ion compounds in a reduced state can be used individually or in combination of two or more types, and the amount used is typically in the range of 0.001 to 1 part by weight, preferably 0.005 to 0.5 parts by weight, and more preferably 0.01 to 0.1 parts by weight, per 100 parts by weight of monomer components.
[0167] A preferred combination of a metal ion compound in a reduced state and other reducing agents is a combination of ferrous sulfate and ascorbic acid or its salt and / or sodium formaldehyde sulfoxylate, more preferably a combination of ferrous sulfate and ascorbic acid or its salt. The amount of ferrous sulfate used is typically in the range of 0.000001 to 0.01 parts by weight, preferably 0.00001 to 0.001 parts by weight, more preferably 0.00005 to 0.0005 parts by weight, per 100 parts by weight of the monomer component, and the amount of ascorbic acid or its salt and / or sodium formaldehyde sulfoxylate used is typically in the range of 0.001 to 1 part by weight, preferably 0.005 to 0.5 parts by weight, more preferably 0.01 to 0.1 parts by weight, per 100 parts by weight of both components.
[0168] The amount of water used in the emulsion polymerization reaction may be the same as the amount used when emulsifying the monomer component, but is adjusted to a range of typically 10 to 1000 parts by weight, preferably 50 to 500 parts by weight, more preferably 80 to 400 parts by weight, and most preferably 100 to 300 parts by weight per 100 parts by weight of the monomer component used for polymerization.
[0169] The method of the emulsion polymerization reaction may follow conventional methods and may be batch, semi-batch, or continuous. The polymerization temperature and polymerization time are not particularly limited and can be appropriately selected from the type of polymerization initiator used. The polymerization time is typically 0.5 to 100 hours, preferably 1 to 10 hours.
[0170] Emulsion polymerization is an exothermic reaction, and if not controlled, the temperature may rise and shorten the polymerization reaction. However, in the present invention, controlling the emulsion polymerization reaction temperature to typically 35°C or lower, preferably 0°C to 35°C, more preferably 5°C to 30°C, and particularly preferably 10°C to 25°C results in a highly balanced and suitable balance between the strength characteristics of the acrylic rubber produced and the processability during mixing with Banbury.
[0171] (Post-addition of chain transfer agent)
[0172] The present invention is characterized by not adding a chain transfer agent initially but adding it in batches during polymerization, thereby enabling the production of acrylic rubber in which high molecular weight and low molecular weight components are separated, and furthermore, the strength characteristics and injection moldability of the produced acrylic rubber are highly balanced and suitable.
[0173] The chain transfer agent used is not particularly limited as long as it is commonly used in emulsion polymerization, and for example, mercaptan compounds can be suitably used.
[0174] As for the mercaptan compound, typically an alkyl mercaptan compound having 2 to 20 carbon atoms, preferably an alkyl mercaptan compound having 5 to 15 carbon atoms, and more preferably an alkyl mercaptan compound having 6 to 14 carbon atoms can be used.
[0175] As for the alkyl mercaptan compound, any of n-alkyl mercaptan compounds, sec-alkyl mercaptan compounds, or t-alkyl mercaptan compounds may be used, but preferably n-alkyl mercaptan compounds or t-alkyl mercaptan compounds, and more preferably n-alkyl mercaptan compounds, the effect of the chain transfer agent can be stably exerted and the injection moldability of the acrylic rubber being manufactured can be highly improved, making it suitable.
[0176] Specific examples of alkyl mercaptan compounds include n-pentyl mercaptan, n-hexyl mercaptan, n-heptyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, n-tridecyl mercaptan, n-tetradecyl mercaptan, n-hexadecyl mercaptan, n-octadecyl mercaptan, sec-pentyl mercaptan, sec-hexyl mercaptan, sec-heptyl mercaptan, sec-octyl mercaptan, sec-decyl mercaptan, sec-dodecyl mercaptan, sec-tridecyl mercaptan, sec-tetradecyl mercaptan, sec-hexadecyl mercaptan, sec-octadecyl mercaptan, t-pentyl mercaptan, t-hexyl mercaptan, t-heptyl mercaptan, t-octyl mercaptan, t-decyl mercaptan. Examples include t-dodecyl mercaptan, t-tridecyl mercaptan, t-tetradecyl mercaptan, t-hexadecyl mercaptan, t-octadecyl mercaptan, etc., preferably n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, more preferably n-octyl mercaptan, n-dodecyl mercaptan.
[0177] These chain transfer agents can be used individually or in combination of two or more types. Although the amount of chain transfer agent used is not particularly limited, when the amount is typically in the range of 0.0001 to 1 part by weight, preferably 0.0005 to 0.5 parts by weight, more preferably 0.001 to 0.5 parts by weight, particularly preferably 0.005 to 0.1 parts by weight, and most preferably 0.01 to 0.06 parts by weight per 100 parts by weight of monomer components, the strength characteristics and injection moldability of the acrylic rubber produced are highly balanced and suitable.
[0178] The present invention is characterized by not adding the chain transfer agent at the beginning of polymerization but adding it in batches during polymerization, thereby producing high molecular weight and low molecular weight components of the acrylic rubber being manufactured, and also by setting the molecular weight distribution to a specific range, which allows for a high balance of strength characteristics and injection moldability, making it suitable.
[0179] The number of batch post-additions of the chain transfer agent is not specifically limited and is appropriately selected according to the purpose of use; typically, when it is 1 to 5 times, preferably 2 to 4 times, more preferably 2 to 3 times, and particularly preferably 2 times, the strength characteristics and injection moldability of the acrylic rubber produced can be highly balanced and is suitable.
[0180] The timing for initiating batch post-addition of the chain transfer agent is not specifically limited and is appropriately selected according to the purpose of use. It is suitable for achieving a high balance between the strength characteristics and injection moldability of the acrylic rubber produced when it is typically 20 minutes after the start of polymerization, preferably 30 minutes after the start of polymerization, more preferably 30 to 200 minutes after the start of polymerization, particularly preferably 35 to 150 minutes after the start of polymerization, and most preferably 40 to 120 minutes after the start of polymerization.
[0181] The amount of chain transfer agent added per batch is not specifically limited and is appropriately selected according to the purpose of use. When the amount is in the range of typically 0.00005 to 0.5 parts by weight, preferably 0.0001 to 0.1 parts by weight, more preferably 0.0005 to 0.05 parts by weight, particularly preferably 0.001 to 0.03 parts by weight, and most preferably 0.002 to 0.02 parts by weight per 100 parts by weight of monomer components, the strength characteristics and injection moldability of the acrylic rubber produced can be highly balanced and is suitable.
[0182] After the addition of the chain transfer agent, there are no specific limitations, but the polymerization reaction can be continued for at least 30 minutes, preferably at least 45 minutes, and more preferably at least 1 hour, and then terminated.
[0183] (Post-addition of reducing agent)
[0184] In the present invention, the reducing agent of the redox catalyst can be added later during polymerization, and thereby the strength characteristics and injection moldability of the acrylic rubber produced can be highly balanced, making it suitable.
[0185] As for the reducing agent added later during polymerization, the examples and preferred ranges of the reducing agents described above are the same. In the present invention, ascorbic acid or its salt is suitable as the reducing agent added later.
[0186] The amount of reducing agent added later during polymerization is not particularly limited and can be appropriately selected according to the purpose of use. When the amount is in the range of typically 0.0001 to 1 part by weight, preferably 0.0005 to 0.5 parts by weight, more preferably 0.001 to 0.5 parts by weight, particularly preferably 0.005 to 0.1 parts by weight, and most preferably 0.01 to 0.05 parts by weight per 100 parts by weight of monomer components, the productivity of acrylic rubber manufacturing is excellent, and the strength characteristics and injection moldability of the manufactured acrylic rubber can be highly balanced, making it suitable.
[0187] The reducing agent added later during polymerization may be either continuous or batch, but is preferably batch. There is no particular limitation on the number of times the reducing agent is added later in batches during polymerization, but it is typically 1 to 5 times, preferably 1 to 3 times, and more preferably 1 to 2 times.
[0188] When the reducing agent added later during the initial and intermediate stages of polymerization is ascorbic acid or its salt, the ratio of the amount of ascorbic acid or its salt added later to the amount of ascorbic acid or its salt added later is not particularly limited, but is typically in the range of 1 / 9 to 8 / 2, preferably 2 / 8 to 6 / 4, and more preferably 3 / 7 to 5 / 5 in weight ratio of "initial added ascorbic acid or its salt" / "batch later added ascorbic acid or its salt", which is suitable for producing acrylic rubber with excellent productivity and at the same time allows for a high balance of strength characteristics and injection moldability of the produced acrylic rubber.
[0189] There is no specific limitation on the timing of the subsequent addition of the reducing agent, and it is appropriately selected according to the purpose of use. When it is typically 1 hour after the start of polymerization, preferably 1 to 3 hours after the start of polymerization, and more preferably 1.5 to 2.5 hours after the start of polymerization, it is suitable because it allows for excellent productivity in manufacturing acrylic rubber while also highly balancing the strength characteristics and injection moldability of the manufactured acrylic rubber.
[0190] The amount of reducing agent added per batch is not specifically limited and is appropriately selected according to the purpose of use. When the amount is typically in the range of 0.00005 to 0.5 parts by weight, preferably 0.0001 to 0.1 parts by weight, more preferably 0.0005 to 0.05 parts by weight, and particularly preferably 0.001 to 0.03 parts by weight per 100 parts by weight of monomer components, the strength characteristics and injection moldability of the acrylic rubber produced can be highly balanced and is suitable.
[0191] The operation after the addition of the reducing agent is not specifically limited, but the polymerization reaction can be continued for at least 30 minutes, preferably at least 45 minutes, and more preferably at least 1 hour, and then the polymerization reaction can be terminated.
[0192] The polymerization conversion rate of the emulsion polymerization reaction is 90% by weight or more, preferably 95% by weight or more, and the acrylic rubber produced at this time has excellent strength characteristics and is also suitable as it has no monomer odor. For stopping polymerization, a polymerization stopping agent may be used.
[0193] (Coagulation process)
[0194] The coagulation process in the method for manufacturing acrylic rubber of the present invention is a process of adding the obtained emulsion polymerization solution to a stirring coagulation solution and coagulating it to produce a hydrated crumb.
[0195] The solid content of the emulsion polymer used in the coagulation reaction is not specifically limited, but is typically adjusted to a range of 5 to 50 weight%, preferably 10 to 45 weight%, and more preferably 20 to 40 weight%.
[0196] The coagulant used in the coagulation liquid is not particularly limited, but metal salts are typically used. Examples of metal salts include alkali metals, Group 2 metal salts, and other metal salts. Preferably, when the metal salt is an alkali metal salt, a Group 2 metal salt, more preferably a Group 2 metal salt, and particularly preferably a magnesium salt, the water resistance, strength characteristics, and the fusion, release, and processability of the acrylic rubber obtained can be highly balanced, making it suitable.
[0197] Examples of alkali metal salts include sodium salts such as sodium chloride, sodium nitrate, and sodium sulfate; potassium salts such as potassium chloride, potassium nitrate, and potassium sulfate; and lithium salts such as lithium chloride, lithium nitrate, and lithium sulfate. Among these, sodium salts are preferred, and sodium chloride and sodium sulfate are particularly preferred.
[0198] Examples of Group 2 metal salts of the periodic table include magnesium chloride, calcium chloride, magnesium nitrate, calcium nitrate, magnesium sulfate, calcium sulfate, etc., and preferably calcium chloride and magnesium sulfate.
[0199] Other metal salts include, for example, zinc chloride, titanium chloride, manganese chloride, iron chloride, cobalt chloride, nickel chloride, aluminum chloride, tin chloride, zinc nitrate, titanium nitrate, manganese nitrate, iron nitrate, cobalt nitrate, nickel nitrate, aluminum nitrate, tin nitrate, zinc sulfate, titanium sulfate, manganese sulfate, iron sulfate, cobalt sulfate, nickel sulfate, aluminum sulfate, tin sulfate, etc.
[0200] These coagulants can be used individually or in combination of two or more types, and the amount used is typically in the range of 0.01 to 100 parts by weight, preferably 0.1 to 50 parts by weight, and more preferably 1 to 30 parts by weight, per 100 parts by weight of monomer components. When the coagulant is in this range, it is suitable because it can sufficiently coagulate the acrylic rubber while highly improving the resistance to permanent deformation and water resistance when the acrylic rubber is cross-linked.
[0201] In the coagulation process of the present invention, in particular, by concentrating the particle size of the generated moisture crumbs in a specific area, the cleaning efficiency and the ash removal efficiency during dehydration are significantly increased and suitable. Although there is no particular limitation on the proportion of the generated moisture crumbs in the range of 710 μm to 6.7 mm (passing through 6.7 mm without passing through 710 μm), the water resistance of the acrylic rubber can be significantly improved when the proportion is typically 30 wt% or more, preferably 50 wt% or more, more preferably 60 wt% or more, particularly preferably 70 wt% or more, and most preferably 80 wt% or more relative to the total generated moisture crumbs. In addition, the water resistance of the acrylic rubber can be significantly improved and is suitable when the proportion of the generated water crumb in the range of 710 μm to 4.75 mm (passing through 4.75 mm without passing through 710 μm) is not specifically limited, but is typically 30 wt% or more, preferably 50 wt% or more, more preferably 60 wt% or more, particularly preferably 70 wt% or more, and most preferably 80 wt% or more relative to the total generated water crumb. In addition, the water resistance of the acrylic rubber can be significantly improved and is suitable when the proportion of the generated water crumb in the range of 710 μm to 3.35 mm (passing through 3.35 mm without passing through 710 μm) is not specifically limited, but is typically 20 wt% or more, preferably 30 wt% or more, more preferably 40 wt% or more, particularly preferably 50 wt% or more, and most preferably 60 wt% or more relative to the total generated water crumb.
[0202] There are no specific limitations on the means for generating the particle size of the function crumb within the above range, but for example, the method of contacting the emulsion polymerization solution and the coagulant can be carried out by adding the emulsion polymerization solution to a coagulant solution (aqueous coagulant solution) that is being stirred, or by specifying the concentration of the coagulant in the coagulant solution, the stirring number or circumferential speed of the coagulant solution being stirred.
[0203] The coagulation solution used is typically an aqueous solution, and when the concentration of the coagulant in the aqueous solution is typically in the range of 0.1 to 20 weight%, preferably 0.5 to 15 weight%, more preferably 1 to 10 weight%, and particularly preferably 1.5 to 5 weight%, the particle size of the resulting moisture crumb can also be uniformly concentrated in a specific area, making it suitable.
[0204] Although there is no particular limitation on the temperature of the coagulation solution, a uniform moisture crumb is formed when the temperature is typically 40°C or higher, preferably 40 to 90°C, and more preferably 50 to 80°C.
[0205] As a method for contacting the emulsion polymerization solution and the coagulant, a method of adding the emulsion polymerization solution to the stirred coagulant is selected, and the cleaning and dehydration efficiency of the generated moisture crumbs is significantly excellent, which is suitable as it can highly improve the water resistance and storage stability of the resulting acrylic rubber.
[0206] The stirring speed (rotation speed) of the coagulating liquid being stirred is, that is, the rotation speed of the stirring blade of the stirring device, and although there are no special limitations, it is typically in the range of 100 rpm or more, preferably 200 rpm or more, more preferably 200 to 1000 rpm, particularly preferably 300 to 900 rpm, and most preferably 400 to 800 rpm.
[0207] The rotational speed is preferably a rotational speed at which the mixture is stirred vigorously to some extent, as this allows the resulting hydrated crumb particles to be small and uniform. By keeping the rotational speed above the lower limit, the generation of crumb particles that are excessively large or small can be suppressed, and by keeping it below the upper limit, the control of the coagulation reaction can be made easier.
[0208] The circumferential speed of the coagulating liquid being stirred, that is, the speed of the outer circumference of the stirring blade of the stirring device, is not specifically limited, but stirring vigorously to a certain extent is suitable as it can make the particle size of the resulting moisture crumbs smaller and more uniform, and is typically 0.5 m / s or more, preferably 1 m / s or more, more preferably 1.5 m / s or more, particularly preferably 2 m / s or more, and most preferably 2.5 m / s or more. Meanwhile, the upper limit of the circumferential speed is not specifically limited, but is typically 50 m / s or less, preferably 30 m / s or less, more preferably 25 m / s or less, and most preferably 20 m / s or less, as it is suitable for controlling the coagulation reaction.
[0209] By setting the above conditions of the coagulation reaction (contact method, solid content concentration of the emulsion polymerization solution, concentration and temperature of the coagulant, rotational speed and circumferential speed during stirring of the coagulant, etc.) to a specific range, the shape and diameter of the resulting moisture crumbs are uniform and aggregated, thereby significantly improving the removal of emulsifiers or coagulants during washing and dehydration, and as a result, the water resistance and storage stability of the acrylic rubber produced can be greatly improved, making it suitable.
[0210] (Cleaning process)
[0211] The cleaning process in the method for manufacturing acrylic rubber of the present invention is a process for cleaning the generated moisture crumb.
[0212] The cleaning method is not particularly limited, and, for example, can be performed by mixing the generated hydrate crumb with a large amount of water.
[0213] The amount of water added for washing is not particularly limited, but when the amount per wash per 100 parts by weight of monomer component is typically 50 parts by weight or more, preferably 50 to 15,000 parts by weight, more preferably 100 to 10,000 parts by weight, and even more preferably 500 to 5,000 parts by weight, the amount of ash in the acrylic rubber can be effectively reduced, so it is suitable.
[0214] The temperature of the water used is not particularly limited, but it is preferable to use hot water, typically 40°C or higher, preferably 40 to 100°C, more preferably 50 to 90°C, and is particularly optimal when the cleaning efficiency can be significantly increased at 60 to 80°C. By making the temperature of the water used above the lower limit, the emulsifier or coagulant is released from the water crumb, and the cleaning efficiency is further improved.
[0215] The cleaning time is not specifically limited, but is typically in the range of 1 to 120 minutes, preferably 2 to 60 minutes, and more preferably 3 to 30 minutes.
[0216] The number of washes (washing) is not particularly limited, and is typically 1 to 10 times, preferably 1 to 5 times, and more preferably 2 to 3 times. Meanwhile, from the perspective of reducing the residual amount of coagulant in the acrylic rubber obtained finally, it is preferable to have a large number of washes, but the number of washes can be significantly reduced by setting the shape and diameter of the moisture crumb to a specific range as described above, and / or setting the washing temperature to the above range.
[0217] (Dehydration process)
[0218] The dehydration process in the method for manufacturing acrylic rubber of the present invention is a process of dehydrating the washed moisture crumb to a moisture content of 1 to 50 weight percent.
[0219] Regarding the method for dehydrating the hydrate crumb, there are no specific limitations as long as it is a method capable of squeezing moisture out of the hydrate crumb, and it can typically be carried out using a dehydrator or the like. This is suitable because it reduces the ash content of emulsifiers or coagulants inherent in the hydrate crumb that could not be removed during the washing process, thereby significantly improving the water resistance of the acrylic rubber.
[0220] The dehydrator is not particularly limited and, for example, a centrifuge, a squeezer, or a screw extruder can be used, but a screw extruder is particularly suitable because it can significantly reduce the moisture content of the moisture crumb. With adhesive acrylic rubber, the acrylic rubber adheres between the walls and slits, so it can usually only be dehydrated to about 45 to 55 weight percent. In contrast, a screw extruder is suitable because it has a mechanism to forcibly squeeze out moisture.
[0221] The moisture content of the moisture crumb after dehydration is not limited, but is typically in the range of 1 to 50 weight%, preferably 1 to 40 weight%, more preferably 10 to 40 weight%, and more preferably 15 to 35 weight%. By making the moisture content after dehydration above the lower limit above, the dehydration time can be shortened, thereby suppressing the deterioration of the acrylic rubber, while by making it below the upper limit above, the ash content can be sufficiently reduced.
[0222] (Drying process)
[0223] The drying process in the method for manufacturing acrylic rubber of the present invention is a process of drying the dehydrated moisture crumb to less than 1 weight%.
[0224] The method of drying the moisture crumb after dehydration described above is not particularly limited, but, for example, can be performed using a screw-type twin-screw extrusion dryer. As for the screw-type twin-screw extrusion dryer used, there is no particular limitation as long as it is an extrusion dryer having two screws, but in the present invention, in particular, by using a screw-type twin-screw extrusion dryer having two screws to dry the moisture crumb under high shear conditions, the injection moldability, Banbury processability, and strength characteristics of the acrylic rubber obtained can be highly balanced, making it suitable.
[0225] In the present invention, acrylic rubber can be obtained by melting a moisture crumb in a screw-type twin-screw extrusion dryer and extruding and drying it. The drying temperature (set temperature) of the screw-type twin-screw extrusion dryer can be appropriately selected, but typically, when the temperature is in the range of 100 to 250°C, preferably 110 to 200°C, and more preferably 120 to 180°C, it is suitable because the acrylic rubber can be dried efficiently without deterioration or alteration due to heat.
[0226] In addition, when the hydrated crumb is melt-kneaded and dried under reduced pressure in a screw-type twin-screw extrusion dryer, the storage stability can be highly improved without damaging the injection moldability or strength characteristics of the acrylic rubber, making it suitable. The reduced pressure of the screw-type twin-screw extrusion dryer suitable for removing air contained in the acrylic rubber at this stage to improve storage stability can be appropriately selected, and is typically in the range of 1 to 50 kPa, preferably 2 to 30 kPa, and more preferably 3 to 20 kPa.
[0227] In addition, in the present invention, when a moisture crumb is melt-kneaded and dried in a screw-type twin-screw extrusion dryer in a state where almost all water has been removed, it is suitable for highly improving Banbury processability without damaging the injection moldability or strength characteristics of the acrylic rubber. The state in which almost all water has been removed to highly improve Banbury processability can be appropriately selected, and the moisture content of the acrylic rubber is typically less than 1 weight%, preferably 0.8 weight% or less, and more preferably 0.6 weight% or less. Meanwhile, "melt-kneading" or "melt-kneading and drying" as used in the present invention means that acrylic rubber is kneaded (mixed) in a molten state or extruded in a molten state within a screw-type twin-screw extrusion dryer and dried at that stage, or that acrylic rubber is kneaded in a molten (plasticized) state, extruded, and dried by a screw-type twin-screw extrusion dryer.
[0228] The maximum torque of the screw-type twin-screw extrusion dryer used in the present invention is not particularly limited, but is typically in the range of 5 to 125 N·m, preferably 10 to 100 N·m, more preferably 10 to 50 N·m, and particularly preferably 15 to 45 N·m, which is suitable for highly balancing the injection moldability, Banbury processability, and strength characteristics of the acrylic rubber produced.
[0229] The non-power of the screw-type twin-screw extrusion dryer used in the present invention is not specifically limited, but typically in the range of 0.01 to 0.3 [kw·h / kg] or more, preferably 0.05 to 0.25 [kw·h / kg], and more preferably 0.1 to 0.2 [kw·h / kg], the injection moldability, Banbury processability, and strength characteristics of the acrylic rubber obtained are highly balanced and suitable.
[0230] The specific power of the screw-type twin-screw extrusion dryer used in the present invention is not specifically limited, but typically, when it is in the range of 0.1 to 0.6 [A·h / kg] or more, preferably 0.15 to 0.55 [A·h / kg], and more preferably 0.2 to 0.5 [A·h / kg], the injection moldability, Banbury processability, and strength characteristics of the acrylic rubber obtained are highly balanced and suitable.
[0231] The shear speed of the screw-type twin-screw extrusion dryer used in the present invention is not specifically limited, but typically ranges from 5 to 150 [1 / s] or higher, preferably from 10 to 100 [1 / s], and more preferably from 25 to 75 [1 / s]. When this range is used, the storage stability, injection moldability, Banbury processability, and strength characteristics of the acrylic rubber obtained are highly balanced and suitable.
[0232] The shear viscosity of the acrylic rubber in the screw-type twin-screw extrusion dryer used in the present invention is not specifically limited, but is typically in the range of 4000 to 8000 [Pa·s] or less, preferably 4500 to 7500 [Pa·s], and more preferably 5000 to 7000 [Pa·s]. When this range is obtained, the storage stability, injection moldability, Banbury processability, and strength characteristics of the acrylic rubber are highly balanced and suitable.
[0233] In the present invention, the acrylic rubber is cooled after melt mixing and drying. When the cooling rate is typically 40°C / hr or higher, preferably 50°C / hr or higher, more preferably 100°C / hr or higher, and particularly preferably 150°C / hr or higher, the storage stability, injection moldability, Banbury processability, strength characteristics, water resistance, and resistance to permanent deformation of the acrylic rubber are excellent, and scorch stability can be significantly improved.
[0234] The acrylic rubber of the present invention obtained in this way has excellent injection moldability, Banbury processability, strength characteristics, and water resistance, and can be used for various purposes. The shape of the acrylic rubber of the present invention is not particularly limited and is selected according to the purpose of use; for example, powder, crumb, strand, sheet, bale, etc., may be used, but the sheet or bale shape is suitable because it has excellent workability and storage stability.
[0235] (Method for manufacturing sheet or bale-shaped acrylic rubber)
[0236] The method for manufacturing sheet-like or bale-like acrylic rubber according to the present invention is not particularly limited, but the moisture crumb after washing can be easily manufactured by using a screw-type twin-screw extrusion dryer having a dehydration barrel with a dehydration slit, a drying barrel under reduced pressure, and a die at the tip to dehydrate the moisture content to 1 to 40 weight% in the dehydration barrel, and then drying it to less than 1 weight% in the drying barrel to extrude the sheet-like dried rubber from the die. Additionally, bale-like acrylic rubber can be easily manufactured by laminating the extruded sheet-like dried rubber and baling it.
[0237] In the present invention, it is preferable that the moisture crumb supplied to the screw-type twin-screw extrusion dryer has had free water removed (moisture removed) after washing.
[0238] (Moisture removal process)
[0239] In the present invention, providing a moisture removal process that separates free water from the moisture crumb after washing using a moisture remover is suitable for increasing dehydration efficiency.
[0240] As for the moisture remover, known types may be used without special limitations, such as wire mesh, screens, and electric screens, and preferably wire mesh or screens.
[0241] The mesh size of the moisture remover is not specifically limited, but is typically in the range of 0.01 to 5 mm, preferably 0.1 to 1 mm, and more preferably 0.2 to 0.6 mm, as this results in less moisture crumb loss and allows for efficient moisture removal.
[0242] The moisture content of the moisture crumb after moisture removal, that is, the moisture content of the moisture crumb fed into the dehydration and drying process, is not particularly limited, but is typically in the range of 50 to 80 weight%, preferably 50 to 70 weight%, and more preferably 50 to 60 weight%.
[0243] The temperature of the moisture crumb after moisture removal, that is, the temperature of the moisture crumb introduced into the dehydration and drying process, is not particularly limited, but is typically in the range of 40°C or higher, preferably 40°C to 100°C, more preferably 50°C to 90°C, particularly preferably 55°C to 85°C, and most preferably 60°C to 80°C. In this case, the moisture crumb, which is difficult to raise the temperature of due to its high specific heat of 1.5 to 2.5 KJ / kg·K like the acrylic rubber of the present invention, can be efficiently dehydrated and dried using a screw-type twin-screw extrusion dryer, making it suitable.
[0244] (Dehydration of the hydrated crumb in the dehydration barrel)
[0245] Dewatering of the moisture crumb is performed in a dewatering barrel in a screw-type twin-screw extrusion dryer having a dewatering slit. The mesh size of the dewatering slit can be appropriately selected according to the usage conditions, but typically, when it is in the range of 0.01 to 5 mm, preferably 0.1 to 1 mm, and more preferably 0.2 to 0.6 mm, the loss of moisture crumb is small and the moisture crumb can be dewatered efficiently, making it suitable.
[0246] The number of dehydration barrels in a screw-type twin-screw extrusion dryer is not particularly limited, but is typically multiple, preferably 2 to 10, more preferably 3 to 6, which is suitable for efficiently dehydrating adhesive acrylic rubber.
[0247] The removal of water from the moisture crumb in the dehydration barrel can be carried out in two ways: removal in a liquid state through the dehydration slit (drainage) and removal in a vapor state (steaming). However, in the present invention, drainage is defined as dehydration and steaming as pre-drying to distinguish them.
[0248] In the dehydration of a moisture crumb, the water discharged from the dehydration slit may be in either a liquid state (drainage) or a vapor state (exhaust steam). However, when using a screw-type twin-screw extrusion dryer equipped with multiple dehydration barrels, the dehydration of adhesive acrylic rubber can be efficiently achieved by combining drainage and exhaust steam, making it suitable. The selection of whether to use a drainage-type dehydration barrel or an exhaust steam-type dehydration barrel in a screw-type twin-screw extrusion dryer equipped with three or more dehydration barrels can be made appropriately according to the purpose of use. Typically, when reducing the ash content in the manufactured acrylic rubber, the number of drainage-type barrels is increased, and when reducing the moisture content, the number of exhaust steam-type barrels is increased.
[0249] The set temperature of the dehydration barrel is appropriately selected according to the monomer composition, ash content, moisture content, and operating conditions of the acrylic rubber, and is typically in the range of 60 to 150°C, preferably 70 to 140°C, and more preferably 80 to 130°C. The set temperature of the dehydration barrel for dehydration in a drained state is typically 60 to 120°C, preferably 70 to 110°C, and more preferably 80 to 100°C. The set temperature of the dehydration barrel for dehydration in a steamed state is typically in the range of 100 to 150°C, preferably 105 to 140°C, and more preferably 110 to 130°C.
[0250] There is no particular limitation on the moisture content after dewatering in a drainage-type dewatering process that squeezes moisture from a crumb, but typically, when it is 1 to 40 weight%, preferably 5 to 35 weight%, and more preferably 10 to 35 weight%, productivity and ash removal efficiency are highly balanced and suitable.
[0251] Dehydration of adhesive acrylic rubber having reactive groups is almost impossible to perform using a centrifuge or the like, as the acrylic rubber adheres to the dehydration slit (water content up to about 45 to 55 weight%), but in the present invention, by using a screw-type twin-screw extrusion dryer that is forcibly squeezed with a screw and has a dehydration slit, the water content can be reduced to this level.
[0252] In the case of having a drainage-type dewatering barrel and a steam-type dewatering barrel, the dewatering of the moisture crumb is such that the moisture content after draining in the drainage-type dewatering barrel section is typically 5 to 40 weight%, preferably 10 to 40 weight%, more preferably 15 to 35 weight%, and the moisture content after pre-drying in the steam-type dewatering barrel section is typically 1 to 30 weight%, preferably 3 to 20 weight%, more preferably 5 to 15 weight%.
[0253] By making the moisture content after dehydration above the lower limit, the dehydration time can be shortened, thereby suppressing the deterioration of acrylic rubber, and by making it below the upper limit, the ash content can be sufficiently reduced.
[0254] (Drying of moisture crumbs in the drying barrel section)
[0255] The drying of the moisture crumb after the above dehydration is characterized by being performed in a drying barrel section under reduced pressure by a screw-type twin-screw extrusion dryer having a drying barrel section. By performing the drying of acrylic rubber under reduced pressure, the production efficiency of the drying is increased, and furthermore, air contained within the acrylic rubber is removed, making it suitable for producing acrylic rubber with a high specific gravity and excellent storage stability. In the present invention, the storage stability of the acrylic rubber can also be highly enhanced by melting the acrylic rubber under reduced pressure and extrusion drying. The storage stability of acrylic rubber can be controlled largely in relation to the specific gravity of the acrylic rubber; when high storage stability is controlled by a high specific gravity, it can be controlled by the degree of reduced pressure during extrusion drying, etc.
[0256] The degree of vacuum in the drying barrel can be selected appropriately, but typically when it is 1 to 50 kPa, preferably 2 to 30 kPa, and more preferably 3 to 20 kPa, the moisture crumb can be dried efficiently and the preservation stability of the acrylic rubber can be significantly improved by removing air from the acrylic rubber, making it suitable.
[0257] The set temperature of the drying barrel can be appropriately selected, but typically in the range of 100 to 250°C, preferably 110 to 200°C, and more preferably 120 to 180°C, it is suitable for efficiently drying acrylic rubber without thermal deterioration or alteration, and also for reducing the gel amount of methyl ethyl ketone insoluble components in sheet or bale acrylic rubber.
[0258] The number of drying barrels in a screw-type twin-screw extrusion dryer is not particularly limited, but is typically multiple, preferably 2 to 10, and more preferably 3 to 8. When there are multiple drying barrels, the degree of pressure reduction may be approximate for all drying barrels or may be varied. When there are multiple drying barrels, the set temperature may be approximate for all drying barrels or may be varied, but it is suitable to make the temperature of the discharge section (closer to the die) higher than the temperature of the inlet section (closer to the dehydration barrel) in order to increase drying efficiency.
[0259] The moisture content of the dried rubber after drying is typically less than 1 weight%, preferably 0.8 weight% or less, and more preferably 0.6 weight% or less. In the present invention, melt extrusion is particularly suitable when the moisture content of the dried rubber is set to this value (a state in which almost all water is removed) in a screw-type twin-screw extrusion dryer, as this can reduce the gel amount of the methyl ethyl ketone insoluble component of the sheet-type or bale-type acrylic rubber. In the present invention, the acrylic rubber, preferably the sheet-type or bale-type acrylic rubber, which is melt-kneaded or melt-kneaded and dried in a screw-type twin-screw extrusion dryer, is suitable because both strength characteristics and Banbury processability characteristics are highly balanced. Meanwhile, "melt-kneading" or "melt-kneading and drying" as used in the present invention refers to the process of mixing (mixing) the acrylic rubber in a molten state or extruding it in a molten state within a screw-type twin-screw extrusion dryer and drying it at that stage, or mixing the acrylic rubber in a molten (plasticized) state and extruding it using a screw-type twin-screw extrusion dryer and drying it.
[0260] In the present invention, the shear rate applied in the drying barrel of a screw-type twin-screw extrusion dryer while the acrylic rubber is substantially free of water is not specifically limited, but is typically in the range of 5 [1 / s] or more, preferably 10 to 400 [1 / s], and more preferably 20 to 250 [1 / s], and the storage stability, injection moldability, Banbury processability, strength characteristics, and resistance to permanent deformation of the sheet-like or bale-like acrylic rubber obtained therefrom are highly balanced and suitable.
[0261] The shear viscosity of the acrylic rubber in the screw-type twin-screw extrusion dryer used in the present invention, particularly in the drying barrel, is not specifically limited, but is typically 12,000 [Pa·s] or less, preferably 1,000 to 12,000 [Pa·s], more preferably 2,000 to 10,000 [Pa·s], particularly preferably 3,000 to 7,000 [Pa·s], and most preferably 4,000 to 6,000 [Pa·s]. When this range is obtained, the storage stability, injection moldability, Banbury processability, and strength characteristics of the sheet-like or bale-like acrylic rubber are highly balanced and suitable.
[0262] (Extrusion of dry rubber from the die)
[0263] The dried rubber, dehydrated and dried by the screw section of the dehydration barrel and drying barrel mentioned above, is sent to a screwless die section and extruded from the die section into a desired shape. A breaker plate or a wire mesh may or may not be installed between the screw section and the die section.
[0264] The extruded dry rubber is suitable because it is extruded in a sheet form with a roughly rectangular die shape, which reduces air entrainment and yields dry rubber with high specific gravity and excellent storage stability.
[0265] The resin pressure in the die is not particularly limited, but when it is typically in the range of 0.1 to 10 MPa, preferably 0.5 to 5 MPa, and more preferably 1 to 3 MPa, the incorporation of air into the sheet-like or bale-like acrylic rubber is low (specific gravity is high) and productivity is excellent, making it suitable.
[0266] (Screw-type twin-screw extrusion dryer and operating conditions)
[0267] The screw length (L) of the screw-type twin-screw extrusion dryer used can be appropriately selected according to the purpose of use, typically in the range of 3,000 to 15,000 mm, preferably 4,000 to 10,000 mm, and more preferably 4,500 to 8,000 mm.
[0268] The screw diameter (D) of the screw-type twin-screw extrusion dryer used can be appropriately selected according to the purpose of use, typically in the range of 50 to 250 mm, preferably 100 to 200 mm, and more preferably 120 to 160 mm.
[0269] The ratio (L / D) of the screw length (L) and screw diameter (D) of the screw-type twin-screw extrusion dryer used is not particularly limited, but is typically in the range of 10 to 100, preferably 20 to 80, and more preferably 30 to 60. This allows the moisture content to be less than 1 weight% without causing a decrease in the molecular weight of the dried rubber or deterioration due to heat.
[0270] The rotational speed (N) of the screw-type twin-screw extrusion dryer used can be appropriately selected according to various conditions, but typically 10 to 1000 rpm, preferably 50 to 750 rpm, more preferably 100 to 500 rpm, and most preferably 120 to 300 rpm, is suitable because it can efficiently reduce the water content and gel amount of methyl ethyl ketone insoluble components of sheet-like or bale-like acrylic rubber.
[0271] The extrusion rate (Q) of the screw-type twin-screw extrusion dryer used is not particularly limited, but is typically in the range of 100 to 1500 kg / hr, preferably 300 to 1200 kg / hr, more preferably 400 to 1000 kg / hr, and most preferably 500 to 800 kg / hr.
[0272] The ratio (Q / N) of the extrusion volume (Q) and rotational speed (N) of the screw-type twin-screw extrusion dryer used is not particularly limited, but is typically in the range of 2 to 10, preferably 3 to 8, and more preferably 4 to 6.
[0273] The maximum torque of the screw-type twin-screw extrusion dryer used is not particularly limited, but is typically in the range of 5 to 125 N·m, preferably 10 to 100 N·m, more preferably 10 to 50 N·m, and particularly preferably 15 to 45 N·m, which is suitable for achieving a high balance of injection moldability, Banbury processability, and strength characteristics of the sheet-like or bale-like acrylic rubber produced.
[0274] The specific power of the screw-type twin-screw extrusion dryer used is not specifically limited, but typically ranges from 0.01 to 0.3 [kw·h / kg] or higher, preferably from 0.05 to 0.2 [kw·h / kg], and more preferably from 0.1 to 0.2 [kw·h / kg]. When this range is used, the injection moldability, Banbury processability, and strength characteristics of the sheet-like or bale-like acrylic rubber obtained are highly balanced and suitable.
[0275] The specific power of the screw-type twin-screw extrusion dryer used is not specifically limited, but typically ranges from 0.1 to 0.6 [A·h / kg] or higher, preferably from 0.15 to 0.55 [A·h / kg], and more preferably from 0.2 to 0.5 [A·h / kg]. When this range is high, the injection moldability, Banbury processability, and strength characteristics of the sheet-like or bale-like acrylic rubber obtained are well-balanced.
[0276] The shear speed of the screw-type twin-screw extrusion dryer used is not specifically limited, but typically ranges from 5 to 150 [1 / s] or higher, preferably from 10 to 100 [1 / s], and more preferably from 25 to 75 [1 / s]. When this range is used, the storage stability, injection moldability, Banbury processability, and strength characteristics of the sheet-like or bale-like acrylic rubber obtained are highly balanced and suitable.
[0277] The shear viscosity of the acrylic rubber in the screw-type twin-screw extrusion dryer used is not specifically limited, but is typically in the range of 4000 to 8000 [Pa·s] or less, preferably 4500 to 7500 [Pa·s], and more preferably 5000 to 7000 [Pa·s]. When this range is obtained, the storage stability, injection moldability, Banbury processability, and strength characteristics of the sheet-like or bale-like acrylic rubber are highly balanced and suitable.
[0278] In this way, the present invention is suitable because it enables dehydration, drying, and molding under high shear conditions by using an extrusion dryer having two screws.
[0279] (Sheet-type dry rubber)
[0280] The shape of the dried rubber extruded from the screw-type twin-screw extrusion dryer is sheet-like, and since air is not incorporated at this time, the specific gravity can be increased, and storage stability is highly improved and suitable. The sheet-like dried rubber extruded from the screw-type twin-screw extrusion dryer is typically cooled and cut to be used as sheet-like acrylic rubber.
[0281] The thickness of the sheet-like dried rubber extruded from a screw-type twin-screw extrusion dryer is not subject to any particular limitations, but is typically suitable for workability and productivity when it is in the range of 1 to 40 mm, preferably 2 to 35 mm, more preferably 3 to 30 mm, and most preferably 5 to 25 mm. In particular, since the thermal conductivity of the sheet-like dried rubber is low at 0.15 to 0.35 W / mK, the thickness of the sheet-like dried rubber in the case where the cooling efficiency is increased to significantly improve productivity is typically in the range of 1 to 30 mm, preferably 2 to 25 mm, more preferably 3 to 15 mm, and particularly preferably 4 to 12 mm.
[0282] The width of the sheet-like dried rubber extruded from a screw-type twin-screw extrusion dryer is appropriately selected according to the purpose of use, typically in the range of 300 to 1200 mm, preferably 400 to 1000 mm, and more preferably 500 to 800 mm.
[0283] The temperature of the dried rubber extruded from the screw-type twin-screw extrusion dryer is not particularly limited, but is typically in the range of 100 to 200°C, preferably 110 to 180°C, and more preferably 120 to 160°C.
[0284] The moisture content of the dried rubber extruded from the screw-type twin-screw extrusion dryer is not specifically limited, but is typically less than 1 weight%, preferably 0.8 weight% or less, more preferably 0.6 weight% or less.
[0285] The complex viscosity ([η] at 100°C) of sheet-like dried rubber extruded from a screw-type twin-screw extrusion dryer is not particularly limited, but is typically in the range of 1500 to 6000 [Pa·s], preferably 2000 to 5000 [Pa·s], more preferably 2500 to 4500 [Pa·s], and most preferably 3000 to 4000 [Pa·s], at which point the extrudability as a sheet and shape retention are highly balanced and suitable. That is, by setting it above the lower limit, the extrudability can be made better, and by setting it below the upper limit, the collapse or breakage of the shape of the sheet-like dried rubber can be suppressed.
[0286] Sheet-shaped dried rubber extruded from a screw-type twin-screw extrusion dryer can be folded and used as is, but normally, it can be cut and used.
[0287] Although there are no specific limitations on the cutting of the sheet-shaped dried rubber, since the acrylic rubber of the present invention has strong adhesive properties, it is preferable to perform the cutting after cooling the sheet-shaped dried rubber in order to cut it continuously without incorporating air.
[0288] There is no particular limitation on the cutting temperature of sheet-type dried rubber, but when it is typically 60°C or lower, preferably 55°C or lower, and more preferably 50°C or lower, the cutting performance and productivity are highly balanced and suitable.
[0289] The complex viscosity ([η]60℃) of sheet-type dry rubber at 60℃ is not particularly limited, but is typically in the range of 15,000 [Pa·s] or less, preferably 2,000 to 10,000 [Pa·s], more preferably 2,500 to 7,000 [Pa·s], and most preferably 2,700 to 5,500 [Pa·s], which is suitable for continuous cutting without incorporating air.
[0290] The ratio of the complex viscosity at 100°C ([η]100°C) and the complex viscosity at 60°C ([η]60°C) of sheet-type dry rubber ([η]100°C / [η]60°C) is not subject to any particular limitation and can be appropriately selected according to the purpose of use, but is typically 0.5 or higher, preferably 0.6 or higher, more preferably 0.7 or higher, and the ratio of the complex viscosity at 100°C ([η]100°C) and the complex viscosity at 60°C ([η]60°C / [η]60°C) of sheet-type dry rubber is also typically in the range of 0.5 to 0.99, preferably 0.55 to 0.95, more preferably 0.6 to 0.9, particularly preferably 0.65 to 0.85, and most preferably 0.7 to 0.8, when air entrainment is low and cutability and productivity are highly balanced. Register.
[0291] There are no specific limitations on the cooling method for sheet-type dried rubber, and it may be left at room temperature. However, since the thermal conductivity of sheet-type dried rubber is very low (0.15 to 0.35 W / mK), forced cooling methods such as air cooling under airflow or cooling, water spraying, or immersion in water are desirable because they increase productivity, and air cooling under airflow or cooling is particularly suitable.
[0292] In the air cooling method for sheet-type dried rubber, for example, sheet-type dried rubber can be extruded from a screw-type extruder onto a conveyor such as a belt conveyor and cooled by conveying it while spraying cold air. The temperature of the cold air is not particularly limited, but is typically in the range of 0 to 25°C, preferably 5 to 25°C, and more preferably 10 to 20°C. The length of the cooling is not particularly limited, but is typically in the range of 5 to 500 m, preferably 10 to 200 m, and more preferably 20 to 100 m.
[0293] The cooling rate of the sheet-type dried rubber is not particularly limited, but is typically 40°C / hr or higher, preferably 50°C / hr or higher, more preferably 100°C / hr or higher, and particularly preferably 150°C / hr or higher, at which time it is easy to cut and suitable. In addition, in the present invention, when the cooling rate of the sheet-type dried rubber is typically 40°C / hr or higher, preferably 50°C / hr or higher, more preferably 100°C / hr or higher, and particularly preferably 150°C / hr or higher, the processing stability of the acrylic rubber composition is excellent and suitable.
[0294] The cutting length of the sheet-type dried rubber is not specifically limited and is appropriately selected according to the purpose of use, but is typically in the range of 100 to 800 mm, preferably 200 to 500 mm, and more preferably 250 to 450 mm.
[0295] The sheet-like acrylic rubber obtained in this way has excellent workability compared to crumb-like acrylic rubber, and also has excellent injection moldability, crosslinkability, strength characteristics, and resistance to permanent deformation of compression, while also having excellent storage stability, Banbury processability, and water resistance, and can be used as is or laminated and baled.
[0296] (Lamination process)
[0297] The method for manufacturing bale-shaped acrylic rubber according to the present invention is not particularly limited, but by laminating the sheet-shaped acrylic rubber, a bale-shaped acrylic rubber with excellent storage stability and low air entrainment is obtained and is suitable.
[0298] The lamination temperature of the sheet-type acrylic rubber is not particularly limited, but is typically 30°C or higher, preferably 35°C or higher, and more preferably 40°C or higher, as this allows air incorporated during lamination to escape. The number of layers can be appropriately selected according to the size or weight of the bale-type acrylic rubber. The bale-type acrylic rubber of the present invention is integrated by the self-weight of the laminated sheet-type acrylic rubber.
[0299] The bale-shaped acrylic rubber of the present invention obtained in this way has excellent maneuverability compared to crumb-shaped acrylic rubber, and also has excellent injection moldability, crosslinkability, strength characteristics, and resistance to permanent deformation of compression, while also having excellent storage stability, Banbury processability, and water resistance. The bale-shaped acrylic rubber can be used as is or cut into the required amount and fed into a mixer such as a Banbury or a roll.
[0300] <Rubber Composition>
[0301] The rubber composition of the present invention is characterized by comprising a rubber component including the acrylic rubber, a filler, and a crosslinking agent.
[0302] As for the rubber component that serves as the main component of the rubber composition of the present invention, the acrylic rubber of the present invention may be used alone, or, if necessary, the acrylic rubber of the present invention may be used in combination with other rubber components. The content of the acrylic rubber of the present invention among the rubber components may be selected according to the purpose of use, for example, typically 30 weight% or more, preferably 50 weight% or more, and more preferably 70 weight% or more.
[0303] Other rubber components combined with the acrylic rubber of the present invention are not particularly limited and may include, for example, natural rubber, polybutadiene rubber, polyisoprene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, silicone rubber, fluororubber, olefin-based elastomer, styrene-based elastomer, vinyl chloride-based elastomer, polyester-based elastomer, polyamide-based elastomer, polyurethane-based elastomer, polysiloxane-based elastomer, etc.
[0304] These other rubber components may each be used individually or in combination of two or more types. The shape of these other rubber components may be crumb-like, strand-like, bale-like, sheet-like, powder-like, or any other shape. The content of the other rubber components in the total rubber components is appropriately selected within a range that does not impair the effects of the present invention, for example, typically 70 weight% or less, preferably 50 weight% or less, more preferably 30 weight% or less.
[0305] There are no specific limitations on the fillers included in the rubber composition, but examples include reinforcing fillers and non-reinforcing fillers. Preferably, when a reinforcing filler is used, the injection moldability, Banbury processability, and short-term crosslinking properties of the rubber composition are excellent, and furthermore, the strength characteristics and resistance to permanent deformation of the crosslinked material are highly excellent, and furthermore, water resistance is also excellent, so it is suitable.
[0306] Examples of reinforcing fillers include carbon blacks such as furnace black, acetylene black, thermal black, channel black, and graphite; silicas such as wet silica, dry silica, and colloidal silica; etc. Examples of non-reinforcing fillers include quartz powder, diatomaceous earth, zinc oxide, basic magnesium carbonate, activated calcium carbonate, magnesium silicate, aluminum silicate, titanium dioxide, talc, aluminum sulfate, calcium sulfate, barium sulfate, etc.
[0307] These fillers can be used individually or in combination of two or more types, and the amount of each is appropriately selected within a range that does not impair the effects of the present invention, and is typically in the range of 1 to 200 parts by weight, preferably 10 to 150 parts by weight, more preferably 20 to 100 parts by weight, per 100 parts by weight of rubber component.
[0308] There are no specific limitations on the crosslinking agent used in the rubber composition, and conventionally known crosslinking agents are selected according to the purpose of use. Examples include inorganic crosslinking agents such as sulfur compounds or organic crosslinking agents, and preferably, organic crosslinking agents. As for the crosslinking agent, it may also be either a polyvalent compound or a monovalent compound, but preferably, a polyvalent compound having two or more reactive groups is suitable. As for the crosslinking agent, it may also be either an ionic crosslinkable compound or a radical crosslinkable compound, but preferably, an ionic crosslinkable compound is suitable.
[0309] As for the organic crosslinking agent, there are no particular limitations, but an ionic crosslinkable organic compound is preferred, and a polyvalent ionic organic compound is particularly preferred. When the crosslinking agent is a polyvalent ionic organic compound (polyvalent ionic crosslinkable compound), the injection moldability, Banbury processability, and short-term crosslinking properties of the rubber composition are excellent, and furthermore, the water resistance, strength characteristics, and resistance to permanent compression deformation of the crosslinked product are highly excellent and suitable. As for the "ion" of the ionic crosslinkable or polyvalent ion, it is an ionicly reactive ion, and for example, there are no particular limitations as long as it reacts ionically with the reactive group of the reactive group-containing monomer of the acrylic rubber, but preferably, an ionic crosslinkable organic compound having an ionicly reactive group such as an amine group, an epoxy group, a carboxyl group, or a thiol group may be cited.
[0310] Specific examples of polyvalent ionic organic compounds include polyvalent amine compounds, polyvalent epoxy compounds, polyvalent carboxylic acid compounds, polyvalent thiol compounds, etc., preferably polyvalent amine compounds or polyvalent thiol compounds, more preferably polyvalent amine compounds.
[0311] Polyvalent amine compounds include, for example, aliphatic polyvalent amine compounds such as hexamethylenediamine, hexamethylenediamine carbamate, and N,N'-disinnamylidene-1,6-hexanediamine; aromatic polyvalent amine compounds such as 4,4'-methylenedianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-(m-phenylenediisopropylidene)dianiline, 4,4'-(p-phenylenediisopropylidene)dianiline, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminobenzanilide, 4,4'-bis(4-aminophenoxy)biphenyl, m-xylylenediamine, p-xylylenediamine, and 1,3,5-benzenetriamine; Examples include the above. Among these, hexamethylenediaminecarbamate and 2,2'-bis[4-(4-aminophenoxy)phenyl]propane are preferred. As polyvalent amine compounds, their carbonates can also be used appropriately. These polyvalent amine compounds are particularly well used in combination with carboxyl group-containing acrylic rubber or epoxy group-containing acrylic rubber.
[0312] As polyvalent thiol compounds, triazinethiol compounds are suitably used, examples of which include 6-trimercapto-s-triazine, 2-anilino-4,6-dithiol-s-triazine, 1-dibutylamino-3,5-dimercaptotriazine, 2-dibutylamino-4,6-dithiol-s-triazine, 1-phenylamino-3,5-dimercaptotriazine, 2,4,6-trimercapto-1,3,5-triazine, 1-hexylamino-3,5-dimercaptotriazine, etc. These triazinethiol compounds are particularly suitably used in combination with acrylic rubber containing chlorine atoms.
[0313] Other polyvalent organic compounds include polyvalent carboxylic acid compounds such as tetradecane-2 acid, and metal salts of dithiocarbamates such as zinc dimethyl dithiocarbamate. These other polyvalent organic compounds are particularly well-suited for use in combination with acrylic rubber containing epoxy groups.
[0314] These crosslinking agents can be used individually or in combination of two or more types, and the amount of the agent is typically 0.001 to 20 parts by weight, preferably 0.1 to 10 parts by weight, and more preferably 0.1 to 5 parts by weight, per 100 parts by weight of the rubber component. By setting the amount of the crosslinking agent within this range, it is possible to achieve sufficient rubber elasticity while ensuring excellent mechanical strength as a rubber crosslinked material, which is suitable.
[0315] The rubber composition of the present invention may incorporate an anti-aging agent as needed. The type of anti-aging agent is not particularly limited, but examples include 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butylphenol, butylhydroxyanisole, 2,6-di-t-butyl-α-dimethylamino-p-cresol, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, styrenephenol, 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol), 4,4'-methylenebis(2,6-di-t-butylphenol), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), 2,4-bis[(octylthio)methyl]-6-methylphenol, 2,2'-thiobis-(4-methyl-6-t-butylphenol), Other phenolic antioxidants such as 4,4'-thiobis-(6-t-butyl-o-cresol) and 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol; phosphite ester antioxidants such as tris(nonylphenyl)phosphite, diphenylisodecylphosphite, and tetraphenyldipropylene glycol diphosphite; sulfur ester antioxidants such as dilauryl thiodipropionate; Examples include amine-based anti-aging agents such as phenyl-α-naphthylamine, phenyl-β-naphthylamine, p-(p-toluenesulfonylamide)-diphenylamine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, N,N-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, butylaldehyde-aniline condensate; imidazole-based anti-aging agents such as 2-mercaptobenzimidazole; quinoline-based anti-aging agents such as 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline; and hydroquinone-based anti-aging agents such as 2,5-di-(t-amyl)hydroquinone. Among these, amine-based anti-aging agents are particularly preferred.
[0316] These anti-aging agents can each be used alone or in combination of two or more types, and the amount of the agent is in the range of 0.01 to 15 parts by weight, preferably 0.1 to 10 parts by weight, more preferably 1 to 5 parts by weight, per 100 parts by weight of the rubber component.
[0317] The rubber composition of the present invention comprises a rubber component including the acrylic rubber of the present invention, a filler, and a crosslinking agent as essential components, and optionally an anti-aging agent. Additionally, optionally, other additives commonly used in the art, such as crosslinking aids, crosslinking accelerators, crosslinking retarders, silane coupling agents, plasticizers, processing aids, lubricants, pigments, colorants, antistatic agents, foaming agents, etc., may be incorporated. These other additives may each be used individually or in combination of two or more, and their amounts are appropriately selected within a range that does not impair the effects of the present invention.
[0318] A method for manufacturing the rubber composition of the present invention may include mixing a rubber component containing the acrylic rubber of the present invention, a filler, a crosslinking agent, and an anti-aging agent or other compounding agent that may be included as needed. Any means used in the conventional rubber processing field, such as an open roll, a Banbury mixer, or various types of kneaders, may be used for mixing. The mixing order of each component may be carried out in the usual order practiced in the rubber processing field. For example, it is preferable to sufficiently mix a component that is difficult to react or decompose by heat, and then mix a crosslinking agent, which is a component that is easily reacted or decomposed by heat, in a short time at a temperature where no reaction or decomposition occurs.
[0319] Rubber crosslinker
[0320] The rubber crosslinker of the present invention is formed by crosslinking the rubber composition.
[0321] The rubber crosslinked material of the present invention can be manufactured by using the rubber composition of the present invention to perform molding using a molding machine corresponding to a desired shape, such as an extruder, injection molding machine, compressor, or roll, and by performing a crosslinking reaction by heating to fix the shape as a rubber crosslinked material. In this case, crosslinking may be performed after molding in advance, or crosslinking may be performed simultaneously with molding. The molding temperature is typically 10 to 200°C, preferably 25 to 150°C. The crosslinking temperature is typically 100 to 250°C, preferably 130 to 220°C, more preferably 150 to 200°C, and the crosslinking time is typically 0.1 minutes to 10 hours, preferably 1 minute to 5 hours. As for the heating method, a method used for crosslinking rubber, such as press heating, steam heating, oven heating, and hot air heating, may be appropriately selected.
[0322] Depending on the shape, size, etc., of the rubber crosslinked material of the present invention, it may be further heated to perform secondary crosslinking. The secondary crosslinking is preferably performed for 1 to 48 hours, although this varies depending on the heating method, crosslinking temperature, shape, etc. The heating method and heating temperature may be appropriately selected.
[0323] The rubber crosslinked material of the present invention maintains basic rubber characteristics such as tensile strength, elongation, and hardness, while possessing excellent resistance to permanent compression and water resistance.
[0324] The rubber crosslinked material of the present invention, utilizing the above characteristics, is suitably used as sealing materials such as, for example, O-rings, packings, diaphragms, oil seals, shaft seals, bearing seals, mechanical seals, wellhead seals, seals for electrical and electronic devices, seals for air compressors; various gaskets such as rocker cover gaskets mounted on the connection part between a cylinder block and a cylinder head, oil pan gaskets mounted on the connection part between an oil pan and a cylinder head or transmission case, gaskets for fuel cell separators mounted between a pair of housings that insert a unit cell having a positive electrode, an electrolyte plate, and a negative electrode, and gaskets for top covers of hard disk drives; cushioning materials, anti-vibration materials; wire insulation materials; industrial belts; tubes and hoses; sheets; etc.
[0325] The rubber crosslinked material of the present invention is also suitable for use in various types of hoses, such as extruded products and crosslinked products used for automobiles, for example, fuel oil-based hoses such as fuel tank hoses, filler neck hoses, vent hoses, paper hoses, oil hoses, etc., air-based hoses such as turbo air hoses, transmission control hoses, radiator hoses, heater hoses, brake hoses, air conditioner hoses, etc.
[0326] <Configuration of the device used in the manufacture of acrylic rubber>
[0327] Next, the configuration of an apparatus used for manufacturing acrylic rubber according to one embodiment of the present invention will be described. FIG. 1 is a schematic diagram showing an example of an acrylic rubber manufacturing system having an apparatus configuration used for manufacturing acrylic rubber according to one embodiment of the present invention. For example, the acrylic rubber manufacturing system (1) shown in FIG. 1 may be used for manufacturing acrylic rubber according to the present invention.
[0328] The acrylic rubber manufacturing system (1) shown in FIG. 1 is composed of an emulsion polymerization reactor (not shown), a coagulation device (3), a cleaning device (4), a moisture remover (43), and a screw-type twin-screw extrusion dryer.
[0329] The emulsion polymerization reactor is configured to perform the treatment related to the emulsion polymerization process described above. Although not shown in FIG. 1, this emulsion polymerization reactor comprises, for example, a polymerization reactor, a temperature control unit for controlling the reaction temperature, and a stirring device equipped with a motor and stirring blades. In the emulsion polymerization reactor, water and an emulsifier are mixed with a monomer component for forming acrylic rubber and emulsified while stirring appropriately with a stirrer, and an emulsion polymerization reaction is initiated in the presence of a redox catalyst consisting of an organic radical generator and a reducing agent, and a chain transfer agent is added in batches during the polymerization to obtain an emulsion polymerization liquid. The emulsion polymerization reactor may be any of a batch type, a semi-batch type, or a continuous type, and may be any of a tank-type reactor or a tubular reactor.
[0330] The coagulation device (3) shown in FIG. 1 is configured to perform processing related to the coagulation process described above. As schematically illustrated in FIG. 1, the coagulation device (3) has, for example, a stirring tank (30), a heating unit (31) that heats the inside of the stirring tank (30), a temperature control unit not shown that controls the temperature inside the stirring tank (30), a stirring device (34) equipped with a motor (32) and a stirring blade (33), and a driving control unit not shown that controls the number of rotations and rotational speed of the stirring blade (33). In the coagulation device (3), a hydrated crumb can be produced by contacting the emulsion polymerization liquid obtained from the emulsion polymerization reactor with the coagulation liquid and coagulating it.
[0331] In the coagulation device (3), for example, the contact between the emulsion polymerization liquid and the coagulation liquid is achieved by adding the emulsion polymerization liquid into the coagulation liquid that is being stirred. That is, the coagulation liquid is filled into the stirring tank (30) of the coagulation device (3), and the emulsion polymerization liquid is added to and brought into contact with this coagulation liquid to coagulate the emulsion polymerization liquid, thereby producing a hydrated crumb.
[0332] The heating unit (31) of the coagulation device (3) is configured to heat the coagulation liquid filled in the stirring tank (30). In addition, the temperature control unit of the coagulation device (3) is configured to control the temperature inside the stirring tank (30) by controlling the heating operation by the heating unit (31) while monitoring the temperature inside the stirring tank (30) measured by a thermometer. The temperature of the coagulation liquid inside the stirring tank (30) is controlled by the temperature control unit to be typically 40°C or higher, preferably 40 to 90°C, and more preferably 50 to 80°C.
[0333] The stirring device (34) of the coagulation device (3) is configured to stir the coagulation liquid filled in the stirring tank (30). Specifically, the stirring device (34) is equipped with a motor (32) that generates rotational power and a stirring blade (33) that extends perpendicularly to the rotation axis of the motor (32). The stirring blade (33) can cause the coagulation liquid to flow within the coagulation liquid filled in the stirring tank (30) by rotating around the rotation axis by the rotational power of the motor (32). The shape, size, and number of stirring blades (33) are not particularly limited.
[0334] The drive control unit of the coagulation device (3) is configured to control the rotational drive of the motor (32) of the stirring device (34) to set the rotational speed and rotational speed of the stirring blade (33) of the stirring device (34) to a predetermined value. The rotation of the stirring blade (33) is controlled by the drive control unit so that the stirring speed of the coagulation liquid is, for example, typically 100 rpm or more, preferably 200 to 1000 rpm, more preferably 300 to 900 rpm, and particularly preferably 400 to 800 rpm. The rotation of the stirring blade (33) is controlled by the drive control unit so that the circumferential speed of the coagulation liquid is typically 0.5 m / s or more, preferably 1 m / s or more, more preferably 1.5 m / s or more, particularly preferably 2 m / s or more, and most preferably 2.5 m / s or more. In addition, the rotation of the stirring blade (33) is controlled by the drive control unit so that the upper limit of the circumferential speed of the coagulating liquid is typically 50 m / s or less, preferably 30 m / s or less, more preferably 25 m / s or less, and most preferably 20 m / s or less.
[0335] The cleaning device (4) shown in FIG. 1 is configured to perform the processing related to the cleaning process described above.
[0336] As schematically illustrated in FIG. 1, the cleaning device (4) has, for example, a cleaning tank (40), a heating unit (41) for heating the inside of the cleaning tank (40), and a temperature control unit not illustrated for controlling the temperature inside the cleaning tank (40). In the cleaning device (4), the amount of ash in the acrylic rubber finally obtained can be effectively reduced by mixing the hydrate crumb generated by the coagulation device (3) with a large amount of water and cleaning it.
[0337] The heating unit (41) of the cleaning device (4) is configured to heat the inside of the cleaning tank (40). In addition, the temperature control unit of the cleaning device (4) is configured to control the temperature inside the cleaning tank (40) by controlling the heating operation by the heating unit (41) while monitoring the temperature inside the cleaning tank (40) measured by a thermometer. As described above, the temperature of the cleaning water inside the cleaning tank (40) is typically controlled to be in the range of 40°C or higher, preferably 40 to 100°C, more preferably 50 to 90°C, and most preferably 60 to 80°C.
[0338] The moisture crumb cleaned by the cleaning device (4) is supplied to a screw-type twin-screw extrusion dryer (5) that performs a dehydration process and a drying process. At this time, it is preferable that the moisture crumb after cleaning is supplied to the screw-type twin-screw extrusion dryer (5) after passing through a moisture remover (43) capable of separating free water. For example, a wire mesh, screen, or electric sieve can be used for the moisture remover (43).
[0339] In addition, when the moisture crumb after washing is supplied to the screw-type twin-screw extrusion dryer (5), it is preferable that the temperature of the moisture crumb be 40°C or higher, and furthermore 60°C or higher. For example, the temperature of the water used for washing in the washing device (4) may be set to 60°C or higher (e.g. 70°C) so that the temperature of the moisture crumb when supplied to the screw-type twin-screw extrusion dryer (5) can be maintained at 60°C or higher, or the temperature of the moisture crumb may be heated so that the temperature of the moisture crumb is 40°C or higher, preferably 60°C or higher, when it is returned from the washing device (4) to the screw-type twin-screw extrusion dryer (5). By doing so, it becomes possible to effectively perform the subsequent dehydration and drying processes, and it becomes possible to significantly reduce the moisture content of the finally obtained dried rubber.
[0340] The screw-type twin-screw extrusion dryer (5) shown in FIG. 1 is configured to perform the dehydration and drying processes described above. Meanwhile, FIG. 1 shows a screw-type twin-screw extrusion dryer (5) as a suitable example, but a centrifugal separator or a squeezer may be used as the dehydrator for performing the dehydration process, and a hot air dryer, a vacuum dryer, an expander dryer, a kneader dryer, etc. may be used as the dryer for performing the drying process.
[0341] The screw-type twin-screw extrusion dryer (5) is configured to mold and discharge dried rubber obtained through a dehydration process and a drying process into a predetermined shape. Specifically, the screw-type twin-screw extrusion dryer (5) is configured to have a dehydration barrel section (53) that functions as a dehydrator for dehydrating a moisture crumb cleaned by a cleaning device (4), and a drying barrel section (54) that functions as a dryer for drying a moisture crumb. Additionally, the screw-type twin-screw extrusion dryer (5) is configured to have a die (59) that functions as a molding function for molding a moisture crumb on the downstream side of the screw-type twin-screw extrusion dryer (5).
[0342] Hereinafter, with reference to FIG. 2, the configuration of a screw-type twin-screw extrusion dryer (5) will be described.
[0343] FIG. 2 shows the configuration of a suitable embodiment of the screw-type twin-screw extrusion dryer (5) shown in FIG. 1. The dehydration and drying process described above can be performed suitablely by this screw-type twin-screw extrusion dryer (5).
[0344] The screw-type twin-screw extrusion dryer (5) shown in FIG. 2 is a twin-screw type extrusion dryer formed by having a pair of screws not shown within a barrel unit (51). The screw-type twin-screw extrusion dryer (5) has a drive unit (50) that rotates and drives the pair of screws within the barrel unit (51). This configuration is suitable for drying acrylic rubber by applying an optimal shear. The drive unit (50) is mounted on the upstream end (left end in FIG. 2) of the barrel unit (51). Additionally, the screw-type twin-screw extrusion dryer (5) has a die (59) at the downstream end (right end in FIG. 2) of the barrel unit (51).
[0345] The barrel unit (51) has a supply barrel section (52), a dehydration barrel section (53), and a drying barrel section (54) extending from the upstream side to the downstream side (from left to right in FIG. 2).
[0346] The supply barrel section (52) is composed of two supply barrels, namely the first supply barrel (52a) and the second supply barrel (52b).
[0347] Additionally, the dehydration barrel section (53) is composed of three dehydration barrels, namely the first dehydration barrel (53a), the second dehydration barrel (53b), and the third dehydration barrel (53c).
[0348] Additionally, the drying barrel section (54) is composed of eight drying barrels, namely the first drying barrel (54a), the second drying barrel (54b), the third drying barrel (54c), the fourth drying barrel (54d), the fifth drying barrel (54e), the sixth drying barrel (54f), the seventh drying barrel (54g), and the eighth drying barrel (54h).
[0349] In this way, the barrel unit (51) is configured such that 13 divided barrels (52a~52b, 53a~53c, 54a~54h) are connected from the upstream side to the downstream side.
[0350] Additionally, the screw-type twin-screw extrusion dryer (5) has a heating means not illustrated for individually heating each of the barrels (52a~52b, 53a~53c, 54a~54h) and heating the moisture crumbs in each of the barrels (52a~52b, 53a~53c, 54a~54h) to a predetermined temperature. The heating means is provided in a number corresponding to each of the barrels (52a~52b, 53a~53c, 54a~54h). As such heating means, for example, a configuration such as supplying high-temperature steam from a steam supply means to a steam distribution jacket formed in each of the barrels (52a~52b, 53a~53c, 54a~54h) is employed, but is not limited thereto. Additionally, the screw-type twin-screw extrusion dryer (5) has a temperature control means not shown for controlling the set temperature of each heating means corresponding to each barrel (52a~52b, 53a~53c, 54a~54h).
[0351] Meanwhile, the number of supply barrels, dehydration barrels, and drying barrels that constitute each barrel section (52, 53, 54) in the barrel unit (51) is not limited to the embodiment shown in FIG. 2, and can be set according to the amount of moisture in the liquid of the acrylic rubber crumb being dried.
[0352] For example, the number of supply barrels installed in the supply barrel section (52) is, for example, 1 to 3. In addition, the number of dewatering barrels installed in the dewatering barrel section (53) is, for example, 2 to 10, and is more preferable to have 3 to 6, as this allows for efficient dewatering of the moisture crumb of the adhesive acrylic rubber. In addition, the number of drying barrels installed in the drying barrel section (54) is, for example, 2 to 10, and is more preferable to have 3 to 8.
[0353] A pair of screws within the barrel unit (51) are rotated by a driving means, such as a motor, housed in the driving unit (50). The pair of screws extend from the upstream side to the downstream side within the barrel unit (51) and, by being rotated, can convey the moisture crumb supplied to the supply barrel section (52) to the downstream side while mixing. It is preferable that the pair of screws be of a two-axis interlocking type in which the peaks and valleys interlock with each other, thereby increasing the dewatering efficiency and drying efficiency of the moisture crumb.
[0354] In addition, the rotation direction of the pair of screws may be the same or different, but for self-cleaning performance, it is preferable for them to rotate in the same direction. The screw shape of the pair of screws is not particularly limited and can be any shape required for each barrel section (52, 53, 54).
[0355] The supply barrel section (52) is a region that supplies the functional crumb into the barrel unit (51). The first supply barrel (52a) of the supply barrel section (52) has a feed port (55) that supplies the functional crumb into the barrel unit (51).
[0356] The dehydration barrel section (53) is an area that separates and discharges a liquid (serum water) containing a coagulant, etc., from the hydrate crumb.
[0357] The first to third dewatering barrels (53a to 53c) constituting the dewatering barrel section (53) each have a dewatering slit (56a, 56b, 56c) that discharges moisture from the hydrated crumb to the outside. Each dewatering slit (56a, 56b, 56c) is formed in multiple places in each dewatering barrel (53a to 53c).
[0358] The slit width, or mesh size, of each dewatering slit (56a, 56b, 56c) can be appropriately selected according to usage conditions and is typically 0.01 to 5 mm. In terms of minimizing loss of moisture crumbs and efficiently dewatering moisture crumbs, it is preferably 0.1 to 1 mm, and more preferably 0.2 to 0.6 mm.
[0359] The removal of moisture from the moisture crumb in each dehydration barrel (53a to 53c) of the dehydration barrel section (53) can be done in two ways: in a liquid form through each dehydration slit (56a, 56b, 56c) and in a vapor form. In the dehydration barrel section (53) of this embodiment, the case where moisture is removed in a liquid form is defined as drainage, and the case where it is removed in a vapor form is defined as drainage steam to distinguish them.
[0360] In the dewatering barrel section (53), the moisture content of the adhesive acrylic rubber can be reduced efficiently by combining drainage and steaming, so it is suitable. In the dewatering barrel section (53), which dewatering barrel among the first to third dewatering barrels (53a to 53c) is used for drainage or steaming can be set appropriately according to the purpose of use. If the amount of ash in the acrylic rubber being manufactured normally is reduced, the number of dewatering barrels used for drainage can be increased. In that case, for example, as shown in FIG. 2, drainage is performed in the first and second dewatering barrels (53a, 53b) on the upstream side, and steaming is performed in the third dewatering barrel (53c) on the downstream side. Also, for example, if the dewatering barrel section (53) has four dewatering barrels, an embodiment can be conceived in which drainage is performed in three dewatering barrels on the upstream side and steaming is performed in one dewatering barrel on the downstream side. On the other hand, to reduce the moisture content, the number of dewatering barrels performing steaming should be increased.
[0361] The set temperature of the dewatering barrel section (53) is typically in the range of 60 to 150°C, preferably 70 to 140°C, more preferably 80 to 130°C, as described in the dewatering and drying process described above; the set temperature of the dewatering barrel for dewatering in a drained state is typically in the range of 60°C to 120°C, preferably 70 to 110°C, more preferably 80 to 100°C; and the set temperature of the dewatering barrel for dewatering in a steamed state is typically in the range of 100 to 150°C, preferably 105 to 140°C, more preferably 110 to 130°C.
[0362] The drying barrel section (54) is a region for drying the moisture crumb after dehydration under reduced pressure. Among the first to eighth drying barrels (54a to 54h) constituting the drying barrel section (54), the second drying barrel (54b), the fourth drying barrel (54d), the sixth drying barrel (54f), and the eighth drying barrel (54h) each have vent ports (58a, 58b, 58c, 58d) for degassing. Each vent port (58a, 58b, 58c, 58d) is connected to a vent pipe not shown.
[0363] A vacuum pump not shown is connected to the end of each vent pipe, and the inside of the drying barrel section (54) is reduced to a predetermined pressure by the operation of the vacuum pumps. The screw extruder (5) has a pressure control means not shown that controls the degree of pressure reduction inside the drying barrel section (54) by controlling the operation of the vacuum pumps.
[0364] The pressure reduction in the drying barrel section (54) can be selected appropriately, and as described above, is typically set to 1 to 50 kPa, preferably 2 to 30 kPa, more preferably 3 to 20 kPa.
[0365] In addition, the set temperature in the drying barrel section (54) can be appropriately selected, and as described above, it is typically set to 100 to 250°C, preferably 110 to 200°C, and more preferably 120 to 180°C.
[0366] In each drying barrel (54a~54h) constituting the drying barrel section (54), the set temperature within all drying barrels (54a~54h) may be set to an approximate value or different, but it is desirable to set the temperature on the downstream side (die (59) side) higher than the temperature on the upstream side (dehydration barrel section (53) side) so that the drying efficiency is improved.
[0367] The die (59) is a mold positioned at the downstream end of the barrel unit (51) and has a discharge port of a predetermined nozzle shape. The acrylic rubber, which has been dried in the drying barrel section (54), is extruded into a shape according to the predetermined nozzle shape by passing through the discharge port of the die (59). The acrylic rubber passing through the die (59) can be formed into various shapes such as granular, columnar, rod-shaped, or sheet-shaped depending on the nozzle shape of the die (59), but in the present invention, it is formed into a sheet shape. A breaker plate or a wire mesh may or may not be installed between the screw and the die (59).
[0368] The liquid crumb of acrylic rubber obtained through the washing process is supplied from the feed port (55) to the supply barrel section (52). The liquid crumb supplied to the supply barrel section (52) is sent from the supply barrel section (52) to the dewatering barrel section (53) by the rotation of a pair of screws within the barrel unit (51). In the dewatering barrel section (53), as described above, the moisture contained in the liquid crumb is drained or steamed from the dewatering slits (56a, 56b, 56c) installed in the first to third dewatering barrels (53a to 53c), respectively, and the liquid crumb is dewatered.
[0369] The moisture crumb dehydrated in the dehydration barrel section (53) is sent to the drying barrel section (54) by the rotation of a pair of screws in the barrel unit (51). The moisture crumb sent to the drying barrel section (54) is plasticized and mixed to become a molten body, and is transported downstream while generating heat and increasing temperature. Then, the moisture contained in the molten acrylic rubber is vaporized, and the moisture (steam) is discharged to the outside through vent pipes not shown, each connected to a vent port (58a, 58b, 58c, 58d).
[0370] As described above, by passing through the drying barrel section (54), the hydrate crumb is dried and becomes a molten acrylic rubber, and the acrylic rubber is supplied to the die (59) by the rotation of a pair of screws in the barrel unit (51) and extruded from the die (59).
[0371] Here, an example of the operating conditions of the screw-type twin-screw extrusion dryer (5) according to the present embodiment is given.
[0372] The rotational speed (N) of a pair of screws in the barrel unit (51) can be appropriately selected according to various conditions and is typically 10 to 1000 rpm, and is preferably 50 to 750 rpm, more preferably 100 to 500 rpm, and most preferably 120 to 300 rpm in order to efficiently reduce the amount of acrylic rubber and the amount of methyl ethyl ketone insoluble.
[0373] In addition, the extrusion amount (Q) of the acrylic rubber is not particularly limited, but is typically 100 to 1500 kg / hr, preferably 300 to 1200 kg / hr, more preferably 400 to 1000 kg / hr, and most preferably 500 to 800 kg / hr.
[0374] The ratio (Q / N) of the extrusion amount (Q) of acrylic rubber and the rotational speed (N) of the screw is not particularly limited, but is typically 1 to 20, preferably 2 to 10, more preferably 3 to 8, and particularly preferably 4 to 6.
[0375] The maximum torque in the barrel unit (51) is not particularly limited, but is typically in the range of 5 to 125 N·m, preferably 10 to 100 N·m, more preferably 10 to 50 N·m, and particularly preferably 15 to 45 N·m.
[0376] The non-power in the barrel unit (51) is not specifically limited, but is typically in the range of 0.01 to 0.3 [kw·h / kg] or more, preferably 0.05 to 0.25 [kw·h / kg], and more preferably 0.1 to 0.2 [kw·h / kg].
[0377] The non-electric power in the barrel unit (51) is not specifically limited, but is typically in the range of 0.1 to 0.6 [A·h / kg] or more, preferably 0.15 to 0.55 [A·h / kg], and more preferably 0.2 to 0.5 [A·h / kg].
[0378] The shear rate in the barrel unit (51) is not specifically limited, but is typically in the range of 5 to 150 [1 / s] or more, preferably 10 to 100 [1 / s], and more preferably 25 to 75 [1 / s].
[0379] The shear viscosity of the acrylic rubber in the barrel unit (51) is not specifically limited, but is typically in the range of 4000 to 8000 [Pa·s] or less, preferably 4500 to 7500 [Pa·s], and more preferably 5000 to 7000 [Pa·s].
[0380] The cooling device (6) shown in FIG. 1 is configured to cool the dried rubber obtained through a dehydration process using a dehydrator and a drying process using a dryer. Various cooling methods using the cooling device (6) may be adopted, including air cooling under blowing air or cooling, a splashing method using water spraying, and an immersion method using water. Additionally, the dried rubber may be cooled by leaving it at room temperature.
[0381] As described above, depending on the nozzle shape of the die (59), the dry rubber discharged from the screw-type extruder (5) is extruded into various shapes such as granular, columnar, rod-shaped, and sheet-shaped forms, but in the present invention, it is formed into a sheet shape. Hereinafter, with reference to FIG. 3, a conveying cooling device (60) for cooling the sheet-shaped dry rubber (10) formed into a sheet shape will be described as an example of a cooling device (6).
[0382] FIG. 3 shows the configuration of a conveying cooling device (60) suitable as the cooling device (6) shown in FIG. 1. The conveying cooling device (60) shown in FIG. 3 is configured to cool sheet-shaped dried rubber (10) discharged from the discharge port of the die (59) of a screw-type extruder (5) by an air cooling method while conveying it. By using this conveying cooling device (60), the sheet-shaped dried rubber discharged from the screw-type extruder (5) can be cooled effectively.
[0383] The return cooling device (60) shown in FIG. 3 is used by being directly connected to the die (59) of the screw-type extruder (5) shown in FIG. 2, for example, or by being installed near the die (59).
[0384] The return cooling device (60) has a conveyor (61) that returns sheet-shaped dried rubber (10) discharged from the die (59) of a screw-type extruder (5) in the direction of the arrow (A) in Fig. 3, and a cooling means (65) that sprays cold air onto the sheet-shaped dried rubber (10) on the conveyor (61).
[0385] The conveyor (61) has rollers (62, 63) and a conveyor belt (64) that is wound over the rollers (62, 63) and on which a sheet of dry rubber (10) is placed. The conveyor (61) is configured to continuously convey the sheet of dry rubber (10) discharged from the die (59) of the screw-type extruder (5) to the downstream side (right side in FIG. 3) on the conveyor belt (64).
[0386] The cooling means (65) is not particularly limited, but may be configured to spray cooling air sent from a cooling air generating means not shown on the surface of the sheet-like dry rubber (10) on the conveyor belt (64).
[0387] The length (length of the portion where cooling air can be sprayed) (L1) of the conveyor (61) and cooling means (65) of the conveying cooling device (60) is not particularly limited, but is, for example, 10 to 100 m, and preferably 20 to 50 m. In addition, the conveying speed of the sheet-shaped dried rubber (10) in the conveying cooling device (60) can be appropriately adjusted according to the length (L1) of the conveyor (61) and cooling means (65), the discharge speed of the sheet-shaped dried rubber (10) discharged from the die (59) of the screw-type extruder (5), the target cooling speed or cooling time, etc., for example, 10 to 100 m / hr, and more preferably 15 to 70 m / hr.
[0388] According to the conveying cooling device (60) shown in FIG. 3, the sheet-shaped dried rubber (10) discharged from the die (59) of the screw-type extruder (5) is conveyed to the conveyor (61), and cooling air is sprayed from the cooling means (65) onto the sheet-shaped dried rubber (10), thereby cooling the sheet-shaped dried rubber (10).
[0389] Meanwhile, the return cooling device (60) is not specifically limited to a configuration having one conveyor (61) and one cooling means (65) as shown in FIG. 3, but may also be configured to have two or more conveyors (61) and two or more corresponding cooling means (65). In that case, the total length of each of the two or more conveyors (61) and cooling means (65) should be within the above range.
[0390] The baling device (7) shown in FIG. 1 is configured to process dry rubber, which is extruded from a screw-type extruder (5) and cooled by a cooling device (6), to produce a bale, which is a block of one mass. As described above, the screw-type extruder (5) can extrude dry rubber into various shapes, such as granular, columnar, rod-shaped, and sheet-shaped forms, and the baling device (7) is configured to bale the dry rubber formed into these various shapes. The weight and shape of the bale-shaped acrylic rubber produced by the baling device (7) are not particularly limited, but for example, a bale-shaped acrylic rubber of approximately 20 kg in a roughly rectangular shape is produced.
[0391] The baling device (7) may, for example, be equipped with a baler and manufacture bale-shaped acrylic rubber by compressing cooled dry rubber with the baler.
[0392] In addition, when sheet-shaped dried rubber (10) is manufactured by a screw-type extruder (5), bale-shaped acrylic rubber can be manufactured by laminating sheet-shaped dried rubber (10). For example, a cutting mechanism for cutting sheet-shaped dried rubber (10) may be installed in a baling device (7) positioned downstream of the conveying cooling device (60) shown in FIG. 3. Specifically, the cutting mechanism of the baling device (7) is configured to continuously cut the cooled sheet-shaped dried rubber (10) at predetermined intervals, for example, to process it into cut sheet-shaped dried rubber (16) of a predetermined size. By laminating multiple cut sheet-shaped dried rubbers (16) cut to a predetermined size by the cutting mechanism, bale-shaped acrylic rubber can be manufactured by laminating cut sheet-shaped dried rubber (16).
[0393] When manufacturing a bale-shaped acrylic rubber by laminating cut sheet-shaped dried rubber (16), it is preferable to laminate cut sheet-shaped dried rubber (16) at a temperature of 40°C or higher. By laminating cut sheet-shaped dried rubber (16) at a temperature of 40°C or higher, good air leakage is achieved through additional cooling and compression by self-weight.
[0394] Examples
[0395] The present invention will be described in more detail below with reference to examples and comparative examples. In each example, "parts," "%," and "ratios" are based on weight unless otherwise specified. Meanwhile, various physical properties, etc., were evaluated according to the following methods.
[0396] [Monomer Composition]
[0397] Regarding the monomer composition in acrylic rubber, the monomer composition of each monomer unit in the acrylic rubber is 1 It was confirmed by H-NMR, and the activity of reactive groups remaining in the acrylic rubber and the content of each reactive group were confirmed by the following method. In addition, the content ratio of each monomer unit in the acrylic rubber was calculated from the amount of each monomer used in the polymerization reaction and the polymerization conversion rate. Specifically, since the polymerization reaction was an emulsion polymerization reaction and the polymerization conversion rate was approximately 100%, in which no unreacted monomers could be identified, the content ratio of each monomer unit in the rubber was set to be equal to the amount of each monomer used.
[0398] [Reactive group content]
[0399] The content of reactive groups in acrylic rubber was measured by the following method.
[0400] (1) The amount of carboxyl groups was calculated by dissolving a rubber sample in acetone and performing potentiometric titration with a potassium hydroxide solution.
[0401] (2) The amount of epoxy groups was calculated by dissolving the sample in methyl ethyl ketone, adding a specified amount of hydrochloric acid to react with the epoxy groups, and titrating the remaining amount of hydrochloric acid with potassium hydroxide.
[0402] (3) The amount of chlorine was calculated by completely burning the sample in a combustion flask, absorbing the chlorine generated into water, and titrating it with silver nitrate.
[0403] [Servings]
[0404] The ash content (%) contained in the acrylic rubber was measured in accordance with JIS K6228 Method A.
[0405] [Amount of Ash]
[0406] The amount of each component (%) in the acrylic rubber ash was calculated by pressing the ash collected during the above ash amount measurement onto a suitable Φ20 mm filter paper, measuring the component amount (ppm) using ZSX Primus (manufactured by Rigaku), and determining the ratio in the above ash.
[0407] [Molecular Weight and Molecular Weight Distribution]
[0408] The molecular weight (Mw, Mn, Mz) and molecular weight distribution (Mw / Mn and Mz / Mw) of acrylic rubber are the absolute molecular weight and absolute molecular weight distribution measured by the GPC-MALS method using a solution in which lithium chloride at a concentration of 0.05 mol / L and 37% concentrated hydrochloric acid at a concentration of 0.01% were added to dimethylformamide as a solvent, respectively. Here, the "GPC-MALS method" is defined as follows. Gel permeation chromatography (GPC) is a type of liquid chromatography that performs separation based on differences in molecular size. Specifically, it is a method that combines a multi-angle laser light scattering photometer (MALS) and a differential refractive index meter (RI) with a Gel Permeation Chromatography (GPC) device, and by measuring the difference in light scattering intensity and refractive index of the molecular chain solution separated by size by the GPC device over time, sequentially calculates the molecular weight of the solute and its content, and finally obtains the absolute molecular weight distribution and absolute average molecular weight value of the polymer material.
[0409] The configuration of the gel permeation chromatography multi-angle light scattering photometer, which is the device, consists of a pump (LC-20ADOpt manufactured by Shimadzu Corporation), a detector, a differential refractive index meter (Optilab rEX manufactured by Wyatt Technology), and a multi-angle light scattering detector (DAWN HELEOS manufactured by Wyatt Technology).
[0410] In this way, the molecular weight of the solute and its content were calculated sequentially. The measurement conditions and methods using the GPC device are as follows.
[0411] Column: 2 TSKgel α-M (φ7.8 mm × 30 cm, manufactured by Tosoh)
[0412] Column temperature: 40℃
[0413] Flow rate: 0.8 ml / mm
[0414] Sample preparation: 5 ml of solvent was added to 10 mg of sample (acrylic rubber) and stirred gently at room temperature (dissolution was observed). Afterward, filtration was performed using a 0.5 μm filter.
[0415] [Glass Transition Temperature (Tg)]
[0416] The glass transition temperature (Tg) of acrylic rubber was measured using a differential scanning calorimeter (DSC, product name "X-DSC7000", manufactured by Hitachi High-Tech Science Co., Ltd.).
[0417] [Gel amount]
[0418] The gel amount (%) of acrylic rubber is the amount of insoluble matter relative to methyl ethyl ketone, and was determined by the following method.
[0419] About 0.2 g of acrylic rubber was weighed (Xg), immersed in 100 ml of methyl ethyl ketone, and left at room temperature for 24 hours. Then, the filtrate insoluble in methyl ethyl ketone was filtered and separated using an 80 mesh wire mesh, i.e., the filtrate in which only the rubber component soluble in methyl ethyl ketone was dissolved was evaporated, dried, and solidified to obtain a dry solid content (Yg), which was then calculated using the following formula.
[0420] Gel amount (%) = 100 × (X - Y) / X
[0421] [specific gravity]
[0422] The specific gravity of acrylic rubber was measured in accordance with Method A of JIS K6268 Crosslinked Rubber - Density Measurement.
[0423] The measured value obtained by the following measurement method is density, where the density of water is 1 Mg / m³ 3The specific gravity is determined by [this]. Specifically, the specific gravity of a rubber sample obtained in accordance with Method A of JIS K6268 Cross-linked Rubber Density Measurement is obtained by dividing the mass by the volume containing the voids of the rubber sample, and by dividing the density of the rubber sample measured in accordance with Method A of JIS K6268 Cross-linked Rubber Density Measurement by the density of water (when the density of the rubber sample is divided by the density of water, the numerical value is the same and the unit is eliminated). In detail, the specific gravity of the rubber sample is obtained based on the following sequence.
[0424] (1) A 2.5 g test specimen is cut from a rubber sample that has been left at a standard temperature (23℃±2℃) for at least 3 hours, and the test specimen is suspended from a hook on a chemical balance with a precision of 1 mg using a fine nylon thread with a mass of less than 0.010 g so that the bottom of the test specimen is 25 mm above the chemical balance dispensing dish, and the mass (m1) of the test specimen is measured twice in the atmosphere to the nearest mg.
[0425] (2) Next, 250 cm placed on a chemical balance distribution dish 3 Fill a beaker of a certain volume with distilled water that has been boiled and cooled to a standard temperature, immerse the test specimen in it, remove any bubbles attached to the surface of the test specimen, and observe the movement of the balance pointer for several seconds to confirm that the pointer does not shake slowly due to convection, and measure the mass (m2) of the test specimen in water twice in mg units.
[0426] (3) Also, the density of the test specimen is 1 Mg / m³ 3 When it is less than (when the test specimen floats in the water), a weight is attached to the test specimen and the mass of the weight in the water (m3) and the mass of the test specimen and the weight (m4) are measured twice in mg units.
[0427] (4) The specific gravity of the rubber sample is based on the following formula using the average values of m1, m2, m3, and m4 measured above, and the density (Mg / m³) 3 Calculate ), and the calculated density is the density of water (1.00 Mg / m³3 Calculate by dividing by ).
[0428] (Density of the rubber sample when no weight is used)
[0429] Density = m1 / (m1 - m2)
[0430] (Density of the rubber sample when using a weight)
[0431] Density = m1 / (m1 + m3 - m4)
[0432] [Function Amount]
[0433] The moisture content (%) was measured in accordance with the JIS K6238-1: Oven A (Volatile Content Measurement) method.
[0434] [pH]
[0435] pH was measured using a pH electrode after dissolving 6 g (±0.05 g) of acrylic rubber in 100 g of tetrahydrofuran and adding 2.0 ml of distilled water to confirm complete dissolution.
[0436] [Complex Viscosity]
[0437] The complex viscosity η was determined by using the dynamic viscoelasticity measuring device "Rubber Process Analyzer RPA-2000" (manufactured by Alpha Technology Co., Ltd.), measuring the temperature dispersion (40–120°C) at 1 Hz with a deformation of 473%, and obtaining the complex viscosity η at each temperature. Here, among the dynamic viscoelasticity described above, the dynamic viscoelasticity at 60°C was set as the complex viscosity η (60°C), and the dynamic viscoelasticity at 100°C was set as the complex viscosity η (100°C), and the ratio η (100°C) / η (60°C) was calculated.
[0438] [Moony Viscosity (ML1+4, 100℃)]
[0439] Mooney viscosity (ML1+4, 100℃) was measured according to the physical test method for uncrosslinked rubber of JIS K6300.
[0440] [Injection Moldability]
[0441] Injection moldability was evaluated by observing and scoring shape formability, releaseability, and fusionability using a small injection molding machine (SLIM15-30: manufactured by Daihan Co., Ltd.), and by summing their scores according to the following criteria. For shape formability and releaseability, molds were prepared that mimicked three cylindrical shapes (A: 4 mmφ, B: 3 mmφ, C: 2 mmφ) with different diameters and an axial length of more than 150 mm. A rubber composition was introduced into these molds under conditions of a screw temperature of 90°C, an injection time of 30 seconds, and an injection pressure of 7 MPa. After crosslinking at a mold temperature of 170°C for 1 minute and 30 seconds, the injection-molded cylindrical product was removed, and the cylindrical product and the mold were observed and scored according to the following criteria. For the fusion ability, a mold was prepared that mimicked a fusion observation body with a thickness of 0.5 mm × width of 5 mm × length of 40 mm, with 5 mmφ pipes connected to each of the longitudinal ends. A rubber composition was introduced into the fusion observation body from each of the 5 mmφ pipes under conditions of screw temperature of 90°C, injection time of 30 seconds, and injection pressure of 7 MPa. After crosslinking at a mold temperature of 170°C for 1 minute and 30 seconds, the fusion state of the rubber composition in the fusion observation body was observed and scored according to the following criteria.
[0442] (Shape Formability)
[0443] 5 points: Cylindrical molded articles can be manufactured in all of A, B, and C, and in all of them, the shape of the leading edge of the molded article completely follows the mold, and no burr formation is observed.
[0444] 4 points: Cylindrical molded parts can be manufactured in all of A, B, and C, but in C, a very small portion of the leading edge of the molded part cannot completely follow the mold shape.
[0445] 3 points: Cylindrical molded products can be manufactured in A and B, and more than half of the molded products can be manufactured in C.
[0446] 2 points: Cylindrical molded products can be manufactured in A and B, but less than half of the molded product is produced in C.
[0447] 1 point: A molded product can be manufactured in A, but in B, the molded product is not completely formed.
[0448] 0 points: Cannot manufacture molded product in A
[0449] (Heterogenesis)
[0450] 5 points: Can be easily released from the mold with no mold residue
[0451] 4 points: Can be easily released from the mold, but very minute mold residue is observed.
[0452] 3 points: Can be easily released from the mold, but there is a small amount of mold residue.
[0453] 2 points: Slightly difficult to detach from the mold, but no mold residue.
[0454] 1 point: Slightly difficult to detach from the mold, and mold residue is present.
[0455] 0 points: Difficulty separating from the mold
[0456] (Convergence)
[0457] 5 points: Completely fused
[0458] 0 points: Incomplete fusion (poor fusion)
[0459] Overall evaluation
[0460] ◎: Full score (15 points)
[0461] ○: 14 points
[0462] □: 13 points
[0463] △: 11~12 points
[0464] ×: 10 points or less
[0465] [Banbury Processability]
[0466] The Banbury processability of the rubber sample was evaluated by introducing the rubber sample into a Banbury mixer heated to 50°C and mixing it for 1 minute, then adding compounding agent A of the rubber mixture formulation described in Table 1, and measuring the time until the first stage of the rubber mixture becomes integrated and exhibits a maximum torque value, i.e., the Black Incorporation Time (BIT), and calculating an index with Comparative Example 2 set to 100, and evaluating it according to the following criteria.
[0467] ◎: 20 or less
[0468] ○: Exceeds 20 and is 40 or less
[0469] □: Exceeds 40 and is 60 or less
[0470] △: Exceeds 60 and is 80 or less
[0471] ×: Exceeds 80
[0472] [Preservation Stability Assessment]
[0473] The storage stability of the rubber sample was evaluated by placing the rubber sample into a constant temperature and humidity bath (ESPEC SH-222) at 45℃ × 80% RH, calculating the rate of change in moisture content before and after the test for 7 days, and calculating an index with Comparative Example 2 set to 100, according to the following criteria.
[0474] ◎: 20 or less
[0475] ○: Exceeds 20 and is 50 or less
[0476] □: Exceeds 50 and is 90 or less
[0477] △: Exceeds 90 and is 100 or less
[0478] ×: Exceeds 100
[0479] [Water Resistance Assessment]
[0480] The water resistance of the rubber sample was evaluated by conducting an immersion test in accordance with JIS K6258 by immersing the crosslinked rubber sample in distilled water at a temperature of 85°C for 100 hours, measuring the rate of volume change before and after immersion, and calculating an index with Comparative Example 2 set to 100, based on the following criteria.
[0481] ◎: 1 or less
[0482] ○: More than 1 and 5 or less
[0483] □: More than 5 and 10 or less
[0484] △: Exceeds 10 and is 50 or less
[0485] ×: Exceeds 50
[0486] [Resistance to Compression and Permanent Deformation]
[0487] The compression permanent deformation resistance of the rubber sample was evaluated according to the following criteria by measuring the compression permanent deformation rate after placing the rubber crosslinked material of the rubber sample at 175°C for 90 hours in a state of 25% compression according to JIS K6262.
[0488] ◎: Compressive permanent strain is less than 15%
[0489] ×: Compressive permanent strain is 15% or more
[0490] [Evaluation of State Properties]
[0491] The physical properties of the rubber sample were evaluated by measuring the breaking strength, 100% tensile stress, and breaking elongation of the rubber crosslinked material of the rubber sample according to JIS K6251 and the following criteria.
[0492] (1) Breaking strength was evaluated as ◎ for 10 MPa or more and × for less than 10 MPa.
[0493] (2) 100% tensile stress was evaluated as ◎ for 5 MPa or more and × for less than 5 MPa.
[0494] (3) The elongation at break was evaluated as ◎ for 150% or more and × for less than 150%.
[0495] [Evaluation of Gel Volume Variability]
[0496] The evaluation of the deviation in gel amount of a rubber sample is performed by measuring the gel amount of 20 randomly selected points from 20 parts (20 kg) of the rubber sample and evaluating it based on the following criteria.
[0497] ◎: Calculate the average value of the 20 measured gel samples, and all 20 samples fall within the range of the average value ± 3.
[0498] ○: Calculate the average value of the 20 measured gel samples, and all 20 samples fall within the range of average ± 5 (whereby at least one of the 20 samples falls outside the range of average ± 3, but all 20 samples fall within the range of average ± 5).
[0499] ×: Calculate the average value of the 20 measured gel amounts, and if even 1 point among the 20 measured points deviates from the average value ± 5.
[0500] [Evaluation of Processing Stability by Suppression of Mooney Scotch]
[0501] The cooling rate of sheet-like acrylic rubber extruded from a screw-type twin-screw extrusion dryer as described in Japanese Patent Publication No. 6683189 and the Mooney scorch preservation stability of the acrylic rubber composition were evaluated.
[0502] [Example 1]
[0503] As shown in Table 2-1, a monomer emulsion was obtained by adding 46 parts of pure water, 48.5 parts of ethyl acrylate, 50 parts of n-butyl acrylate and 1.5 parts of monon-butyl fumarate as monomer components, and 1.8 parts of sodium tridecyloxyhexaoxyethylene phosphate ester as an emulsifier to a mixing vessel equipped with a homomixer and stirring.
[0504] 170 parts of pure water and 3 parts of the monomer emulsion obtained above were added to a polymerization reactor equipped with a thermometer and a stirring device, and after cooling to 12°C under a nitrogen stream, 0.00033 parts of ferrous sulfate, 0.02 parts of sodium ascorbate, and 0.0045 parts of diisopropylbenzene hydroperoxide, an organic radical generator, were added to start the polymerization reaction. The temperature inside the polymerization vessel was maintained at 23°C, and the remainder of the monomer emulsion was continuously added dropwise over 3 hours. The polymerization reaction was continued by adding 0.012 parts of n-dodecyl mercaptan after 50 minutes of reaction initiation, 0.012 parts of n-dodecyl mercaptan after 100 minutes, and 0.4 parts of L-sodium ascorbate after 120 minutes. When the polymerization conversion rate reached approximately 100%, hydroquinone was added as a polymerization stopping agent to stop the polymerization reaction, thereby obtaining an emulsion polymerization solution.
[0505] Next, in a coagulation bath equipped with a thermometer and a stirring device, the obtained emulsion polymer solution was heated to 80°C and continuously added to 350 parts of a 2% magnesium sulfate aqueous solution (a coagulation solution using magnesium sulfate as a coagulant) that was heated to 80°C and vigorously stirred with the stirring blades of the stirring device rotating at 600 revolutions (circumferential speed 3.1 m / s) to coagulate the polymer, thereby obtaining a coagulation slurry containing acrylic rubber crumbs as the coagulated product and water. The crumbs were separated by filtration from the obtained slurry, and moisture was discharged from the coagulation layer to obtain hydrated crumbs.
[0506] 194 parts of hot water (70°C) were added to the coagulation tank containing the filtered separated moisture crumb and stirred for 15 minutes to wash the moisture crumb, after which the moisture was drained, and then 194 parts of hot water (70°C) were added again and stirred for 15 minutes to wash the moisture crumb (a total of 2 washes). The washed moisture crumb (moisture crumb temperature 65°C) was supplied to a screw-type twin-screw extrusion dryer (5), dehydrated and dried to extrude a sheet-like dried rubber with a width of 300 mm and a thickness of 10 mm. Next, the sheet-like dried rubber was cooled at a cooling rate of 200°C / hr using a conveying cooling device installed in direct connection to the screw-type twin-screw extrusion dryer (5).
[0507] Meanwhile, the screw-type twin-screw extrusion dryer used in Example 1 is composed of one feed barrel, three dewatering barrels (first to third dewatering barrels), and five drying barrels (first to fifth drying barrels). The first dewatering barrel performs drainage, and the second and third dewatering barrels perform steam drainage. The operating conditions of the screw-type twin-screw extrusion dryer were as follows. Table 2-1 shows the moisture content, maximum torque, specific power, specific wattage, shear rate, and shear viscosity after dewatering (drainage) of the screw-type twin-screw extrusion dryer.
[0508] Function:
[0509] · Moisture content of the crumb after drainage in the first dehydration barrel: 20%
[0510] · Moisture content of the moisture crumb after steaming in the 3rd dehydration barrel: 10%
[0511] · Moisture content of the crumb after drying in the 5th drying barrel: 0.4%
[0512] Rubber temperature:
[0513] · Temperature of the hydrate crumb supplied to the supply barrel: 65℃
[0514] · Temperature of rubber discharged from the screw-type twin-screw extrusion dryer: 140℃
[0515] Set temperature for each barrel:
[0516] · 1st Dehydration Barrel: 100℃
[0517] · 2nd Dehydration Barrel: 120℃
[0518] · 3rd Dehydration Barrel: 120℃
[0519] · 1st drying barrel: 120℃
[0520] · 2nd Drying Barrel: 130℃
[0521] · 3rd Drying Barrel: 140℃
[0522] · 4th Drying Barrel: 160℃
[0523] · 5th Drying Barrel: 180℃
[0524] Driving conditions:
[0525] · Screw diameter (D): 132 mm
[0526] · Total screw length (L): 4620 mm
[0527] ·L / D: 35
[0528] · Screw rotation speed: 135 rpm
[0529] · Depressurization of dry barrel: 10 kPa
[0530] · Rubber extrusion rate from die: 700 kg / hr
[0531] · Resin pressure in the die: 2 MPa
[0532] · Maximum torque in screw-type twin-screw extrusion dryer: 40 N·m
[0533] Extruded sheet-shaped dry rubber was cooled to 50°C and then cut with a cutter, and then laminated to a weight of 20 parts (20 kg) while not falling below 40°C to obtain bale-shaped acrylic rubber (A). The reactive group content, ash content, ash component content, gel content, pH, specific gravity, glass transition temperature (Tg), water content, molecular weight, molecular weight distribution, and complex viscosity at 100°C and 60°C of the obtained bale-shaped acrylic rubber (A) were measured and are shown in Table 2-2. In addition, a storage stability test was performed on the bale-shaped acrylic rubber (A) to determine the rate of change in water content, and the results are shown in Table 2-2.
[0534] Next, using a Banbury mixer, 100 parts of bale-shaped acrylic rubber (A) and compounding agent A of “Formulation 1” listed in Table 1 were added and mixed at 50°C for 5 minutes (1st stage mixing). At this time, the BIT was measured to evaluate the Banbury processability, and the results are shown in Table 2-2. Next, the obtained mixture was transferred to a roll at 50°C, and compounding agent B of “Formulation 1” shown in Table 1 was added and mixed (2nd stage mixing) to obtain a rubber composition. The injection moldability of the obtained rubber composition was evaluated, and the results are shown in Table 2-2.
[0535] [Table 1]
[0536]
[0537] Next, the residual rubber composition was placed into a mold measuring 15 cm in length, 15 cm in width, and 0.2 cm in depth, and subjected to primary crosslinking by pressing at 180°C for 10 minutes while applying a press pressure of 10 MPa. The obtained primary crosslinked material was then subjected to secondary crosslinking by further heating in a gear oven at 180°C for 2 hours, thereby obtaining a sheet-like rubber crosslink. Subsequently, test specimens measuring 3 cm × 2 cm × 0.2 cm were cut from the obtained sheet-like rubber crosslink, and water resistance, resistance to permanent deformation under compression, and state properties were evaluated. The results are shown in Table 2-2.
[0538] [Example 2]
[0539] As shown in Table 2-1, the procedure was carried out in the same manner as in Example 1, except that the monomer components were changed to ethyl acrylate 48.25 parts, n-butyl acrylate 50 parts, and mono-n-butyl fumarate 1.75 parts, to obtain bale-shaped acrylic rubber (B), and each characteristic (the compounding agent was changed to "Formulation 2" (see Table 1)) was evaluated. The results are shown in Table 2-2.
[0540] [Example 3]
[0541] Except for changing the post-addition of n-dodecyl mercaptan to a total of three times—0.008 parts after 50 minutes, 0.008 parts after 100 minutes, and 0.008 parts after 120 minutes—the same procedure as in Example 1 was performed to obtain bale-shaped acrylic rubber (C), and each characteristic was evaluated. The results are shown in Table 2-2.
[0542] [Example 4]
[0543] Except for changing the post-addition of n-dodecyl mercaptan to a total of three times—0.008 parts after 50 minutes, 0.008 parts after 100 minutes, and 0.008 parts after 120 minutes—the same procedure as in Example 2 was performed to obtain bale-shaped acrylic rubber (D) and evaluate each characteristic. The results are shown in Table 2-2.
[0544] [Example 5]
[0545] As shown in Table 2-1, bale-shaped acrylic rubber (E) was obtained by performing the same procedure as in Example 1, except that the maximum torque of the screw-type twin-screw extrusion dryer was changed to 15 N·m, and each characteristic was evaluated. The results are shown in Table 2-2.
[0546] [Example 6]
[0547] Except for changing the maximum torque of the screw-type twin-screw extrusion dryer to 15 N·m, the same procedure as in Example 2 was performed to obtain bale-shaped acrylic rubber (F) and evaluate each characteristic. The results are shown in Table 2-2.
[0548] [Example 7]
[0549] Except for setting the moisture content after dehydration in the dehydration barrel section of a screw-type twin-screw extrusion dryer to 30 wt%, the same procedure as in Example 5 was performed to obtain bale-shaped acrylic rubber (G) and evaluate each characteristic. The results are shown in Table 2-2.
[0550] [Example 8]
[0551] Except for setting the moisture content after dehydration in the dehydration barrel section of a screw-type twin-screw extrusion dryer to 30 wt%, the same procedure as in Example 6 was performed to obtain bale-shaped acrylic rubber (H) and evaluate each characteristic. The results are shown in Table 2-2.
[0552] [Example 9]
[0553] After washing, the moisture crumb was dried to a moisture content of 0.4% using a hot air dryer at 160°C to obtain crumb-like acrylic rubber (I), and then filled into a baler of 300 × 650 × 300 mm and compacted at a pressure of 3 MPa for 25 seconds to obtain bale-like acrylic rubber. Except for these steps, bale-like acrylic rubber (I) was obtained in the same manner as in Example 2. Each characteristic of the bale-like acrylic rubber bale was evaluated, and the results are shown in Table 2-2.
[0554] [Example 10]
[0555] Except for changing the monomer components to 28 parts ethyl acrylate, 38 parts n-butyl acrylate, 27 parts methoxyethyl acrylate, 5 parts acrylonitrile, and 2 parts allylglycidyl ether, the same procedure as in Example 9 was performed to obtain bale-shaped acrylic rubber (J), and each characteristic (the compounding agent was changed to "Formulation 3" (see Table 1)) was evaluated. The results are shown in Table 2-2.
[0556] [Example 11]
[0557] Except for changing the monomer components to 42.2 parts ethyl acrylate, 35 parts n-butyl acrylate, 20 parts methoxyethyl acrylate, 1.5 parts acrylonitrile, and 1.3 parts vinyl chloroacetate, the same procedure as in Example 9 was performed to obtain bale-shaped acrylic rubber (K), and each characteristic (the compounding agent was changed to "Formulation 4" (see Table 1)) was evaluated. The results are shown in Table 2-2.
[0558] [Example 12]
[0559] Except for changing the post-addition of n-dodecyl mercaptan to a total of three times—0.008 parts after 50 minutes, 0.008 parts after 100 minutes, and 0.008 parts after 120 minutes—the same procedure as in Example 11 was performed to obtain bale-shaped acrylic rubber (L) and evaluate each characteristic. The results are shown in Table 2-2.
[0560] [Example 13]
[0561] Except for changing the amount of diisopropylbenzene hydroperoxide to 0.0048 parts and continuously adding 0.024 parts of n-dodecyl mercaptan to the monomer emulsion without further addition, the procedure was carried out in the same manner as in Example 11 to obtain veil-shaped acrylic rubber (M) and evaluate each characteristic. The results are shown in Table 2-2.
[0562] [Comparative Example 1]
[0563] The coagulation reaction was carried out by adding a 0.7% aqueous magnesium sulfate solution to the emulsion polymerization solution (stirring speed 100 rpm, circumferential speed 0.5 m / s) that was being stirred after emulsion polymerization, and the reaction was performed in the same manner as in Example 13, except that crumb-shaped acrylic rubber was obtained without baling by a baler, and crumb-shaped acrylic rubber (N) was obtained and each characteristic was evaluated. The results are shown in Table 2-2.
[0564] [Comparative Example 2]
[0565] The procedure was carried out in the same manner as Comparative Example 1, except that diisopropylbenzene hydroperoxide was changed to 0.005 parts and no chain transfer agent was added, to obtain crumb-like acrylic rubber (O) and evaluate each characteristic. The results are shown in Table 2-2.
[0566] [Table 2-1]
[0567]
[0568] [Table 2-2]
[0569]
[0570] From Table 2-2, it can be seen that the acrylic rubbers (A) to (M) of the present invention, having at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, having a weight average molecular weight (Mw) of 1 million to 5 million, a ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) (Mw / Mn) of 1.5 to 3, a gel content of 50 wt% or less, an ash content of 0.0001 to 0.3 wt%, and a total amount of sodium, sulfur, calcium, magnesium, and phosphorus in the ash of 80 wt% or more, have excellent state properties including injection moldability, Banbury processability, water resistance, resistance to permanent deformation of compression, and strength properties, and also have excellent storage stability (Examples 1 to 13).
[0571] From Table 2-2, it can be seen that the acrylic rubbers (A) to (O) of the embodiments and comparative examples of the present invention have excellent resistance to permanent deformation of compression by having ionic reactive groups such as carboxyl groups, epoxy groups, or chlorine atoms, and that the acrylic rubbers (A) to (O) prepared under the conditions of the embodiments and comparative examples of the present invention all have a weight average molecular weight (Mw) that far exceeds 1 million, and thus have excellent physical properties including strength characteristics (Examples 1 to 13 and Comparative Examples 1 to 2). However, the acrylic rubbers (N) to (O) have poor injection moldability, Banbury processability, water resistance, and storage stability (Comparative Examples 1 to 2).
[0572] From Table 2-2, regarding injection moldability, it is strongly influenced by the molecular weight distribution (Mw / Mn) of the acrylic rubber, and as Comparative Example 2 has Mw / Mn = 1.3 / Injection Moldability: ×, Example 13 has Mw / Mn = 1.55 / Injection Moldability: △, Example 12 has Mw / Mn = 1.99 / Injection Moldability: ○, Examples 3 to 11 have Mw / Mn 2.39 to 2.45 / Injection Moldability: ◎, and Examples 1 to 2 have Mw / Mn = 2.91 to 2.94 / Injection Moldability: ○, it can be seen that the acrylic rubber of the present invention has excellent injection moldability when Mw / Mn is around 2.4. In addition, it can be seen that injection moldability can be improved without damaging strength characteristics when the molecular weight distribution (Mz / Mw) focused on the high molecular weight region is sufficiently wide, the number average molecular weight (Mn), weight average molecular weight (Mw), and z average molecular weight (Mz) are sufficiently large, and the Mw / Mn range of the present invention is also sufficient (comparison of Examples 1 to 13 and Comparative Example 2).
[0573] From Tables 2-1 and 2-2, it can be seen that acrylic rubbers (A) to (M) with a molecular weight distribution (Mw / Mn) in a specific range, which have excellent injection moldability without impairing strength characteristics, can be produced by using a specific amount of organic radical generator and a chain transfer agent, in particular n-dodecyl mercaptan as the chain transfer agent (Examples 1 to 13). From Tables 2-1 and 2-2, it can also be seen that injection moldability without impairing strength characteristics can be improved by adding the chain transfer agent (n-dodecyl mercaptan) in batches afterward rather than adding the chain transfer agent (n-dodecyl mercaptan) continuously (Example 13) (Examples 1 to 12). It is presumed that by initially not adding a chain transfer agent and reducing the organic radical generator to extend a single polymerization chain, and by adding a chain transfer agent during polymerization, a well-balanced mixture of high molecular weight and low molecular weight components is produced without a clear two-mountain structure on the GPC chart, thereby enabling a specific molecular weight distribution (Mw / Mn) and highly balanced strength characteristics and injection moldability. Furthermore, to efficiently broaden the molecular weight distribution (Mw / Mn), the number of batch post-additions has a significant influence, and the molecular weight distribution (Mw / Mn) is broadened when the batch post-addition is performed twice rather than three times (comparison of Examples 9–11 and Example 12). In addition, although not shown in Tables 2-1 and 2-2, in the present embodiment, sodium ascorbate, a reducing agent, is added 120 minutes after the start of polymerization, and by doing so, the formation of high molecular weight components of acrylic rubber is facilitated, thereby increasing the effect of widening the molecular weight distribution (Mw / Mn) of the chain transfer agent after addition.
[0574] From Tables 2-1 and 2-2, it can be seen that when the drying of the hydrate crumb is changed from direct drying to a screw-type twin-screw extrusion dryer and operated under normal conditions, the molecular weight distribution (Mw / Mn) does not change (comparison of Examples 5-8 and Examples 9-11), but when the drying conditions of the screw-type twin-screw extrusion dryer with an optimal shear are set, the molecular weight distribution (Mw / Mn) of the acrylic rubber widens, and the injection moldability of the acrylic rubber can be further improved (comparison of Examples 3-4 and Example 12), but if the molecular weight distribution (Mw / Mn) becomes excessively wide, the effect of injection moldability decreases (comparison of Examples 1-2 and Examples 5-8). In addition, although not shown in the examples and comparative examples of the present invention, it can be seen that if a redox catalyst of an inorganic radical generator is used, the molecular weight distribution (Mw / Mn) of the obtained acrylic rubber becomes excessively wide, and the injection moldability decreases. It is thought that this difference in molecular weight distribution affects injection moldability because, in the case of organic radical generators, the polymerization catalyst is located within the micelles of emulsion polymerization and polymerization is carried out continuously within the micelles, whereas in the case of inorganic radical generators, the polymerization catalyst is located outside the micelles and polymerization takes place outside the micelles.
[0575] From Table 2-2, regarding water resistance, the acrylic rubbers (A) to (M) of the present invention are excellent (comparison of Examples 1 to 13 and Comparative Examples 1 to 2), among them, acrylic rubbers (A) to (F) are particularly significantly excellent in the order of acrylic rubbers (A) to (F) > acrylic rubbers (G) to (H) > acrylic rubbers (I) to (J) > acrylic rubbers (K) to (M) (comparison of Examples 1 to 13), and it can be seen that they are greatly affected by the ash content in the acrylic rubber (comparison of Examples 1 to 13 and Comparative Examples 1 to 2).
[0576] From Tables 2-1 and 2-2, it can be seen that the ash content in acrylic rubber can be significantly reduced by increasing the concentration of the coagulant (2%), changing the method of adding the emulsion polymer to the coagulant while stirring (Lx↓), and increasing the stirring of the coagulant (stirring speed 600 rpm / circumference speed 3.1 m / s) (comparison of Examples 9 to 13 and Comparative Example 1). In particular, the coagulation reaction is carried out by adding the emulsion polymer to the coagulant while stirring very vigorously. Data will be described later, and the diameter of the hydrate crumbs generated in this coagulation reaction is concentrated in a small particle size range of 710 μm to 4.75 mm. It is presumed that this significantly improves the cleaning efficiency with hot water and the removal efficiency of emulsifiers or coagulants during dehydration, thereby reducing the ash content in acrylic rubber and significantly improving water resistance. In addition, regarding water resistance, it can be seen that in Examples 9 to 13, while the ash content is about the same, acrylic rubbers (I) to (J) are superior to acrylic rubbers (K) to (M). This indicates that regarding water resistance, among the ionic reactive groups, acrylic rubbers having carboxyl or epoxy groups rather than chlorine atoms are superior (comparison of Examples 9 to 10 and Examples 11 to 13).
[0577] From Tables 2-1 and 2-2, it can also be seen that regarding water resistance, dewatering (squeezing out moisture) the moisture crumb before drying further significantly reduces the ash content in the acrylic rubber and significantly improves water resistance (comparison of Examples 1-8 and Examples 9-13), and that squeezing out more moisture from the moisture crumb to a moisture content of 20% rather than 30% after dewatering reduces the ash content and significantly improves the water resistance of the acrylic rubber (comparison of Examples 1-6 and Examples 7-8).
[0578] From Tables 2-1 and 2-2, it can be seen that water resistance can be improved if the total amount of phosphorus (P), magnesium (Mg), sodium (Na), calcium (Ca), and sulfur (S) in the ash components of the acrylic rubbers (A) to (M) of the present invention and the acrylic rubbers (N) to (O) of the comparative examples is reduced to 80% by weight or more or 90% by weight or more. In addition, it can be seen that the release properties of the acrylic rubber are significantly excellent when the components in the ash are within this range. From Table 2-2, it can also be seen that the ash components of the acrylic rubbers (A) to (M) of the present invention, which are coagulated by the method of the present invention and then washed and dehydrated, consist of 80% or more or 90% or more of phosphorus (P) and magnesium (Mg) (Examples 1 to 13 and Comparative Examples 1 to 2). This indicates that the ash in acrylic rubber is not simply the emulsifier or coagulant used in manufacturing remaining as is, but rather, during the coagulation reaction, the sodium phosphate ester salt of the emulsifier undergoes salt exchange with the magnesium sulfate (MgSO4) of the coagulant to become a water-repellent magnesium phosphate ester salt that is embedded within the moisture crumb and cannot be sufficiently removed by the washing process, but can be reduced by dehydration (squeezing out moisture from the moisture crumb) in a screw-type twin-screw extrusion dryer (Examples 1-8). It can be seen that squeezing out more moisture from the moisture crumb, such as reducing the moisture content to 20% rather than 30% after dehydration, reduces the amount of ash and significantly improves the water resistance of the acrylic rubber (comparison of Examples 1-6 and Examples 7-8).
[0579] Regarding water resistance, although data was omitted in the embodiments of the present invention, when a phosphate ester salt is used as an emulsifier, it is difficult to reduce it through the washing process; in particular, it can hardly be reduced by washing at room temperature no matter how many times the washing cycle is increased, but it can be improved by washing with hot water. On the other hand, when a sulfate ester salt such as sodium lauryl sulfate is used as an emulsifier, the water resistance is superior to that of ash with a high sulfur (S) or sodium (Na) content, and in particular, for the same amount of ash, the water resistance is more than five times superior. Furthermore, it has been confirmed that even when a sulfate ester salt such as sodium lauryl sulfate is used as an emulsifier, the ash content can be reduced to 0.1 weight% or less and water resistance can be significantly improved by performing the coagulation reaction of the present invention followed by washing with hot water and dehydration. In addition, acrylic rubber produced by emulsion polymerization using a phosphate ester salt or a sulfate ester salt as an emulsifier showed overwhelmingly superior workability, such as mold release properties.
[0580] From Tables 2-1 and 2-2, it can be seen that Banbury processability is related to the gel amount (comparison of Examples 1–13 and Comparative Examples 1–2). The gel amount of the methyl ethyl ketone-insoluble component of the acrylic rubber can be reduced by emulsion polymerization in the presence of a chain transfer agent (comparison of Examples 9–13 and Comparative Example 1 and Comparative Example 2). In particular, since the gel amount increases rapidly when the polymerization conversion rate is increased to enhance strength characteristics, it can be seen that the gel formation of the methyl ethyl ketone-insoluble component can be suppressed in Examples 9–13, in which the chain transfer agent is added later in the polymerization reaction. Furthermore, the gel amount of the acrylic rubber is significantly reduced by drying the moisture crumb using a screw-type twin-screw extrusion dryer, thereby greatly improving Banbury processability without damaging the strength characteristics of the manufactured acrylic rubber (comparison of Examples 1–8 and Examples 9–13). In the present invention, although not shown in this embodiment, it has been confirmed that the gel amount of methyl ethyl ketone insoluble fraction that increased rapidly in emulsion polymerization without adding a chain transfer agent (Comparative Examples 1-2) is lost by melt-kneading in a screw-type twin-screw extrusion dryer in a state that substantially contains no moisture (moisture content less than 1 wt%), thereby significantly improving Banbury processability.
[0581] From Table 2-2, it can be seen that the acrylic rubbers (A) to (M) of the present invention have excellent injection moldability, Banbury processability, water resistance, resistance to permanent deformation under compression, and strength characteristics, as well as excellent storage stability (Examples 1 to 13). Regarding storage stability, it can be seen that the specific gravity of bale-type acrylic rubbers (A) to (M) is much higher than that of crumb-type acrylic rubbers (N) to (O), and that storage stability is determined by the magnitude of the specific gravity, that is, the amount of air incorporated (comparison with Examples 1 to 8, Examples 9 to 13 and Comparative Examples 1 to 2). Bale-type acrylic rubber with a high specific gravity can be obtained by compressing crumb-type acrylic rubber with a baler to bale it (Examples 9 to 13), or more preferably by extruding it into a sheet using a screw-type twin-screw extrusion dryer, laminating it, and baling it (Examples 1 to 8). It can also be seen that regarding the storage stability of acrylic rubber, it is desirable for the ash content to be lower (Examples 1 to 13). Meanwhile, regarding the acrylic rubber (M) of Example 13, when the characteristic values of the crumb-like acrylic rubber as is after direct drying without using a baler were measured, the results were identical to those of Example 13 in Table 2-2, except that the specific gravity was reduced to 0.769. In the present invention, in particular, it can be seen that the storage stability of the bale-like acrylic rubber, which is formed by laminating sheet-like acrylic rubber that has been melt-kneaded and dried under reduced pressure, is significantly improved without damaging the physical properties including injection moldability, Banbury processability, water resistance, resistance to permanent deformation under compression, and strength properties (Examples 1 to 8). In addition, regarding the storage stability of acrylic rubber, it was also important that the pH be 6 or lower.
[0582] [Regarding the particle size of the generated function crumb]
[0583] For the hydrated crumbs generated during the coagulation process in Examples 1 to 13 and Comparative Examples 1 to 2, the proportions of (1) 710 μm to 6.7 mm (passing 6.7 mm without passing 710 μm), (2) 710 μm to 4.75 mm (passing 4.75 mm without passing 710 μm), and (3) 710 μm to 3.35 mm (passing 3.35 mm without passing 710 μm) were measured using JIS sieves. Their results are shown below.
[0584] Example 1: (1) 91 wt%, (2) 91 wt%, (3) 84 wt%
[0585] Example 2: (1) 96 wt%, (2) 95 wt%, (3) 89 wt%
[0586] Example 3: (1) 91 wt%, (2) 85 wt%, (3) 79 wt%
[0587] Example 4: (1) 93 wt%, (2) 90 wt%, (3) 84 wt%
[0588] Example 5: (1) 95 wt%, (2) 93 wt%, (3) 90 wt%
[0589] Example 6: (1) 89 wt%, (2) 85 wt%, (3) 79 wt%
[0590] Example 7: (1) 96 wt%, (2) 94 wt%, (3) 87 wt%
[0591] Example 8: (1) 94 wt%, (2) 93 wt%, (3) 87 wt%
[0592] Example 9: (1) 95 wt%, (2) 94 wt%, (3) 91 wt%
[0593] Example 10: (1) 89 wt%, (2) 86 wt%, (3) 83 wt%
[0594] Example 11: (1) 95 wt%, (2) 94 wt%, (3) 88 wt%
[0595] Example 12: (1) 93 wt%, (2) 93 wt%, (3) 90 wt%
[0596] Example 13: (1) 93 wt%, (2) 89 wt%, (3) 78 wt%
[0597] Comparative Example 1: (1) 17 wt%, (2) 3 wt%, (3) 0 wt%
[0598] Comparative Example 2: (1) 10 wt%, (2) 2 wt%, (3) 0 wt%
[0599] From these results, it can be seen that the amount of ash remaining in the acrylic rubber or in the acrylic rubber differs even with the same cleaning process based on the size of the moisture crumbs generated during the coagulation process, and that the cleaning efficiency is higher for the specific ratios of (1) to (3), the amount of ash is reduced, and the water resistance is excellent (comparison of Examples 9 to 13 and Comparative Examples 1 to 2 in Table 2-2). In addition, the moisture crumbs with a specific ratio of (1) to (3) have a high ash removal rate during dehydration, and the dehydration rate (moisture content) of 20 wt% (Examples 1 to 6) has a lower amount of ash than the dehydration rate (moisture content) of 30 wt% (Examples 7 to 8), which improves the water resistance of the acrylic rubber.
[0600] Meanwhile, for reference, the process was carried out in the same manner as Comparative Example 1 except that an emulsion polymer was added to the coagulation liquid during the coagulation process (Reference Example 1), and the process was carried out in the same manner as Comparative Example 1 except that an emulsion polymer was added to the coagulation liquid and the concentration of the coagulant in the coagulation liquid was changed from 0.7 wt% to 2 wt% (Reference Example 2), and the particle size ratio (1) to (3) of the resulting moisture crumbs and the ash content (4) in the acrylic rubber were measured. The results are shown below.
[0601] Reference Example 1: (1) 91 wt%, (2) 57 wt%, (3) 25 wt%, (4) 0.51 wt%
[0602] Reference Example 2: (1) 92 wt%, (2) 75 wt%, (3) 42 wt%, (4) 0.40 wt%
[0603] For acrylic rubber compositions containing sheet-like acrylic rubbers (A) to (H) of Examples 1 to 8, the Moonyscotch time t5 (min) at a temperature of 125°C was measured according to JIS K 6300 using the method for evaluating processing stability by suppressing Moonyscotch as described above, and the Moonyscotch retention stability was evaluated according to the following criteria. As a result, all were good results of “◎”.
[0604] ◎: Mooney Scotch time t5 exceeds 3.3 minutes
[0605] ○: Mooney Scotch time t5 is 2~3.3 minutes
[0606] ×: Mooney-Scotch time t5 is less than 2 minutes
[0607] Meanwhile, the cooling rate of the sheet-like acrylic rubber (A) to (H) extruded from these screw-type twin-screw extrusion dryers is 40°C / hr or higher, and in reality, the cooling rate is fast at approximately 200°C / hr, as in Example 1.
[0608] In addition, for each rubber sample, the variation in the amount of methyl ethyl ketone insoluble was evaluated using the method described above. Specifically, the variation in the amount of methyl ethyl ketone insoluble in rubber samples was evaluated by measuring the amount of methyl ethyl ketone insoluble at 20 randomly selected points from 20 parts (20 kg) of rubber samples and evaluating it based on the criteria described above.
[0609] When evaluating the variation in gel amount for the acrylic rubbers (A) to (H) obtained in Examples 1 to 8 and the acrylic rubber (O) obtained in Comparative Example 2 as rubber samples, the results for the acrylic rubbers (A) to (H) were all “◎”, and the result for the acrylic rubber (O) was “×”.
[0610] It is presumed that the Banbury processability of acrylic rubbers (A) to (H) could be significantly improved by melt-kneading and drying them in a screw-type twin-screw extrusion dryer, thereby almost eliminating the gel amount of methyl ethyl ketone insoluble components and also eliminating the gel amount variation. Although not shown in this example, it can also be seen from the fact that the gel amount and gel amount variation of the acrylic rubber obtained by extrusion drying a crumb-type acrylic rubber, which had undergone emulsion polymerization and coagulation washing under the conditions for producing the acrylic rubber (O) of Comparative Example 2, by feeding it into a screw-type twin-screw extrusion dryer under the same conditions as Example 1, can be reduced to a level approximately equivalent to that of acrylic rubber (A) and the Banbury processability can be significantly improved.
[0611] [Mold release properties]
[0612] The rubber compositions of acrylic rubber (A) to (H) obtained in Examples 1 to 8 were pressed into a mold of 10 mmφ × 200 mm, and the crosslinked rubber product was removed after crosslinking at a mold temperature of 165°C for 2 minutes. When the mold release properties were evaluated according to the following criteria, all acrylic rubbers (A) to (H) were rated as "◎" and were good.
[0613] ◎: Can be easily released from the mold with no mold residue
[0614] ○: Can be easily released from the mold, but very minute mold residue is observed.
[0615] △: Can be easily released from the mold, but there is a small amount of mold residue.
[0616] ×: Difficulty separating from the mold Explanation of the symbols
[0617] 1 Acrylic Rubber Manufacturing System 3 Coagulation device 4 Cleaning device 5 Screw extruder 6 cooling units 7 Baling device
Claims
Claim 1 An acrylic rubber having at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups, and chlorine atoms, a weight-average molecular weight (Mw) of 1 million to 5 million, a ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn) (Mw / Mn) of 1.5 to 3, and a ratio of z-average molecular weight (Mz) to weight-average molecular weight (Mw) (Mz / Mw) of 1.6 to 2, a gel content of 50 wt% or less, an ash content of 0.0001 to 0.3 wt%, and a total amount of sodium, sulfur, calcium, magnesium, and phosphorus in the ash of 80 wt% or more. Claim 2 The acrylic rubber according to claim 1, comprising at least one bonding unit derived from a (meth)acrylic acid ester selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, a bonding unit derived from a monomer containing at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom, and, optionally, other bonding units derived from monomers. Claim 3 An acrylic rubber according to claim 1 or 2, wherein at least one bonding unit derived from a (meth)acrylic acid ester selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters is 50 to 99.99 weight%, a bonding unit derived from a monomer containing at least one reactive group selected from the group consisting of carboxyl groups, epoxy groups and chlorine atoms is 0.01 to 10 weight%, and a bonding unit derived from other monomers is 0 to 40 weight%. Claim 4 Acrylic rubber according to claim 1 or 2, wherein the reactive group is an ionic reactive group. Claim 5 Acrylic rubber according to claim 1 or 2, having a gel content of 10 weight% or less. Claim 6 Acrylic rubber according to claim 1 or 2, wherein all values of the gel amount measured at 20 random points are within the range of (average value ± 5) weight%. Claim 7 Acrylic rubber according to claim 1 or 2, wherein the gel amount is the amount insoluble in methyl ethyl ketone. Claim 8 Acrylic rubber according to claim 1 or 2, having an ash content of 0.2 weight% or less. Claim 9 Acrylic rubber having a specific gravity of 0.8 or higher in paragraph 1 or 2. Claim 10 Acrylic rubber according to claim 1 or 2, wherein the complex viscosity ([η]100℃) at 100℃ is 15,000[Pa·s] or less. Claim 11 Acrylic rubber having a pH of 6 or less, as in paragraph 1 or 2. Claim 12 Acrylic rubber in the form of a sheet or a bale according to paragraph 1 or 2. Claim 13 Acrylic rubber according to claim 1 or 2, which is emulsion polymerized using a phosphate ester salt or a sulfate ester salt as an emulsifier. Claim 14 Acrylic rubber according to claim 1 or 2, wherein the emulsion polymerized polymerization solution is solidified by using an alkali metal salt or a Group 2 metal salt of the periodic table as a coagulant and dried. Claim 15 In Clause 14, acrylic rubber that has been melt-mixed and dried after solidification. Claim 16 In item 15, the acrylic rubber in which the above melt mixing and drying are performed in a state that substantially does not contain moisture. Claim 17 In item 15, the acrylic rubber in which the above melt mixing and drying are performed under reduced pressure. Claim 18 In item 15, the acrylic rubber cooled at a cooling rate of 40℃ / hr or more after the above-mentioned melt mixing and drying. Claim 19 Acrylic rubber according to claim 1 or 2, wherein the moisture crumb having a proportion of 50 weight% or more of particles with a diameter in the range of 710 μm to 6.7 mm is washed, dehydrated, and dried. Claim 20 A method for manufacturing acrylic rubber as described in claim 1, comprising: an emulsification process of emulsifying an acrylic rubber monomer component containing a monomer having at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom with water and an emulsifier; an emulsion polymerization process of initiating polymerization in the presence of a redox catalyst consisting of an organic radical generator and a reducing agent, and continuing polymerization by adding a chain transfer agent in batches during polymerization to obtain an emulsion polymerization liquid; a coagulation process of adding the obtained emulsion polymerization liquid to a stirring coagulation liquid to coagulate and produce a water crumb; a washing process of washing the produced water crumb; a dehydration process of dehydrating the washed water crumb to a water content of 1 to 50 weight%; and a drying process of drying the dehydrated water crumb to less than 1 weight%. Claim 21 A method for manufacturing acrylic rubber according to claim 20, wherein the dehydration and drying processes involve using a screw-type twin-screw extrusion dryer having a dehydration barrel with a dehydration slit, a drying barrel under reduced pressure, and a die at the leading end to dehydrate the moisture content to 1 to 40 weight% in the dehydration barrel, and then drying it to less than 1 weight% in the drying barrel and extruding the dried rubber from the die. Claim 22 A method for manufacturing acrylic rubber according to claim 20, wherein the stirring speed of the coagulating liquid being stirred is 200 rpm or more. Claim 23 A method for manufacturing acrylic rubber according to claim 20, wherein the circumferential velocity of the coagulating liquid being stirred is 1 m / s or more. Claim 24 A method for manufacturing acrylic rubber according to claim 20, wherein in the emulsion polymerization process, a phosphate ester salt or a sulfate ester salt is used as an emulsifier to perform emulsion polymerization. Claim 25 A method for manufacturing acrylic rubber according to claim 20, wherein the polymerization solution produced in an emulsion polymerization process is solidified and dried by using an alkali metal salt or a Group 2 metal salt of the periodic table as a coagulant. Claim 26 A method for manufacturing acrylic rubber according to claim 20, wherein the polymerization solution produced in the emulsion polymerization process is brought into contact with a coagulant to solidify it, followed by melt mixing and drying. Claim 27 A method for manufacturing acrylic rubber according to claim 26, wherein the above melt mixing and drying are performed in a state that substantially does not contain moisture. Claim 28 A method for manufacturing acrylic rubber according to claim 26, wherein the above melt mixing and drying are performed under reduced pressure. Claim 29 A method for manufacturing acrylic rubber according to claim 26, wherein the acrylic rubber after melt mixing and drying is cooled at a cooling rate of 40℃ / hr or higher. Claim 30 A method for manufacturing acrylic rubber according to claim 20, wherein the proportion of a moisture crumb with a particle diameter in the range of 710 μm to 6.7 mm is 50 weight% or more. Claim 31 A rubber composition comprising a rubber component including the acrylic rubber described in claim 1, a filler, and a crosslinking agent. Claim 32 In Clause 31, a rubber composition in which the filler is a reinforcing filler. Claim 33 In Clause 31, the rubber composition in which the filler is a carbon black type. Claim 34 In Clause 31, a rubber composition in which the filler is a silica. Claim 35 A rubber composition according to any one of claims 31 to 34, wherein the crosslinking agent is an organic crosslinking agent. Claim 36 A rubber composition according to any one of claims 31 to 34, wherein the crosslinking agent is a polyvalent compound. Claim 37 A rubber composition according to claim 31, wherein the crosslinking agent is an ionic crosslinkable compound. Claim 38 A rubber composition in which the crosslinking agent is an ionic crosslinkable organic compound, as described in claim 37. Claim 39 In claim 37, a rubber composition in which the crosslinking agent is a polyvalent ionic organic compound. Claim 40 A rubber composition according to any one of claims 37 to 39, wherein the ion of the ionic crosslinkable compound, ionic crosslinkable organic compound, or polyvalent ionic organic compound as the crosslinking agent is at least one ionic reactive group selected from the group consisting of amino groups, epoxy groups, carboxyl groups, and thiol groups. Claim 41 A rubber composition according to claim 39, wherein the crosslinking agent is at least one polyvalent ionic compound selected from the group consisting of polyvalent amine compounds, polyvalent epoxy compounds, polyvalent carboxylic acid compounds, and polyvalent thiol compounds. Claim 42 A rubber composition according to any one of claims 31 to 34, wherein the content of the crosslinking agent is in the range of 0.001 to 20 parts by weight per 100 parts by weight of the rubber component. Claim 43 A rubber composition comprising an anti-aging agent further comprising any one of claims 31 to 34. Claim 44 In claim 43, a rubber composition in which the anti-aging agent is an amine-based anti-aging agent. Claim 45 A method for preparing a rubber composition comprising mixing a rubber component including the acrylic rubber described in claim 1 or 2, a filler, and, if necessary, an anti-aging agent, and then mixing a crosslinking agent. Claim 46 A rubber crosslinked product formed by crosslinking a rubber composition described in any one of paragraphs 31 to 34. Claim 47 In claim 46, a rubber crosslinked product in which the crosslinking of the above rubber composition is performed after molding. Claim 48 A rubber crosslinked material according to claim 46, wherein the crosslinking of the rubber composition performs primary crosslinking and secondary crosslinking. Claim 49 delete
Citation Information
Patent Citations
High-molecular-weight acrylic polymer, its use and its production
JP1994080735A
Method for manufacturing acrylic rubber
KR1020190077367A
Method for manufacturing acrylic rubber
KR1020190104171A
acrylic rubber
KR1020190112142A
Acrylic rubber and process for producing the same
WO2007114108A1